The Legal Appraisal of the Nature of Liability of Land Transport Operators in Cases of Accidents in Cameroon - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2026)
Land transport operators in Cameroon can be criminally and civilly liable as a result of an accident resulting from their actions. This is provided for in section 289(1) of the penal code1. The criminal liability can be either in tort law, like in negligence, vicarious liability and strict liability, as well as under contract law. The criminal liability can be for an imprisonment term, the payment of a fine, or loss of life or destruction of property. However, the nature of liability in cases of accidents is faced with problems in Cameroon, as the cases suffer from continuous delay before the courts, weak sanctions provided in the penal code and more. This paper sets out to examine the efficiency of the nature of liability of transport operators in cases of accidents in Cameroon. A doctrinal research method has been adopted where the researcher has analyzed both primary and secondary sources of information. The primary sources are the laws and cases decided by courts, while the secondary sources are other write up which the researcher consulted to complete the research paper. Our findings reveal that the laxity of the courts and weak sanctions provided by the Penal code affects the effectiveness of the liability regime for transport operators in cases of accidents. We recommend that the penal code be revised and a more stringent criminal sanction be put in place. Also, a separate court system should be set up for disputes related to accidents to solve the problem of continuous delay before the courts.
Keywords: Accidents; Land Transport Operators; Nature of Liability; Responsabilité; Transport par route; Transporteur

Quels sont les effets des recettes pétrolières sur le capital humain en zone CEMAC ? - Fompehou, Amadou (MPRA Paper, 2026)
This article examines the effects of oil revenues on human capital in CEMAC countries over the period 1995–2020. The study is based on a dynamic panel of five countries (Cameroon, Congo, Gabon, Equatorial Guinea and Chad). The data are sourced from the IMF, the World Bank (WDI), the UNDP and the Worldwide Governance Indicators (WGI). The author employs the Blundell and Bond (1998) GMM system estimator to address the endogeneity and persistence of human capital, supplemented by interaction term models and robustness tests (stationarity, cross-sectional dependence). The analyses reveal a negative or non-significant effect of oil revenues on human capital indicators (school enrolment, life expectancy, HDI-education). Institutional quality acts as a powerful positive moderator, whilst revenue volatility has a detrimental effect. These results highlight the need for better governance, stabilisation funds and a more efficient allocation of oil revenues towards education and health.
Number: 129352
Keywords: Human capital; Institution; Oil revenue

The Role of the Institutions Put in Place to Protect and Promote Land Acquisition in Cameroon: A Critical Analysis - Bate, Racheal Arrah Oben (International Multilingual Journal of Science and Technology, 2026)
The protection and promotion of land acquisition in Cameroon is ensured through a number of legal and administrative institutions established by the State to regulate land ownership, guarantee security of tenure and ensure land transactions are conducted in accordance with the law. These institutions operate within the framework established by the 1974 Land Ordinances, which reorganized the Land tenure system and create mechanisms for the management and allocation of land. Key institutions such as the Ministry of State Property, Surveys and Land Tenure, Land Consultative Boards, local administrative authorities and the courts play significant roles in supervising land registration, resolving disputes and ensuring that the procedures for acquiring both private and public land are respected. Despite the important, the effectiveness of these institutions is sometimes challenged by administrative delays and corruption. Nevertheless, their existence remains fundamental in promoting secure land tenure, facilitating lawful land transactions and strengthening confidence in the administration system in Cameroon. This article is based on the hypothetical premise that the role the institutions put in place to protect and promote land acquisition in Cameroon is ineffective. It seeks to examine the effectiveness of the role of the institutions in protecting and promoting land acquisition. Adopting the Doctrinal research method, the paper concludes that with improved coordination, institutional reforms, greater transparency and stronger enforcement of land laws, these bodies can more effectively fulfil their mandate of ensuring secure land tenure, reducing land disputes and encouraging sustainable land development and investment in Cameroon.
Keywords: Cameroon; Institutions; Land Acquisition; Promotion; Protection

Arbitration and state sovereignty in commercial disputes resolution within ohada laws - Buma, Roland Sigala; Biya, Fabilou (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Long ago before the creation of the state courts, men had resorted to arbitration for the resolution of diputes. Today, based on the principle of monopoly of the state to render justice, the power to judge is given only to the state. Rendering of justice is one of the areas where the state exeercises its sovereign powers. This has made us to ask the question : is arbitration a violation of the sovereignty of the state in the domain of dispute resolution ? Arbitration is not a violation of the sovereign powers of the state because, it is not all disputes that are resolved via arbitration (for example, crimnal, tax disputes etc can not be settled via arbitration) and the state courts intervene in arbitratin when ever it is necessary. The sate courts intervene in arbitration to grant exequatur, order interim mesaures etc. Nonetheless, since OHADA legislator has not given a complete list of all disputes that can not be resolve via arbitration, we recomend that OHADA should provide a list of all disputes whcih can be settle via arbitration as it is the case with the Arbitration Act of Zimbabw. This article aims at identifying those cases that can not be settled by way of arbitration and those instances in which the state courts intervene in arbitration. Avant la création des tribunaux étatiques, les hommes ont eu recours à l'arbitrage pour la résolution des litiges. Aujourd'hui, sur la base du principe du monopole de l'État à rendre la justice, le pouvoir de juger n'est conféré qu'à l'État. Le fait de rendre la justice est l'un des domaines dans lesquels l'État exerce ses pouvoirs souverains. Cela nous a amenés à poser la question : l'arbitrage constitue-t-il une violation de la souveraineté de l'État dans le domaine du règlement des différends ? L'arbitrage n'est pas une violation des pouvoirs souverains de l'État car, d'une part, tous les litiges ne sont pas résolus par voie d'arbitrage (par exemple, les litiges pénaux, fiscaux, etc. ne peuvent pas être réglés par arbitrage) et, d'autre part, les tribunaux étatiques interviennent dans l'arbitrage chaque fois que cela est nécessaire. Les tribunaux étatiques interviennent dans l'arbitrage pour accorder l'exequatur, ordonner des mesures provisoires, etc. Néanmoins, étant donné que le législateur de l'OHADA n'a pas établi une liste exhaustive de tous les litiges qui ne peuvent pas être résolus par arbitrage, nous recommandons que l'OHADA fournisse une liste de tous les litiges qui peuvent être réglés par voie d'arbitrage, comme c'est le cas dans la loi sur l'arbitrage du Zimbabwe. Cet article vise à identifier les litiges qui ne peuvent pas être réglés par voie d'arbitrage ainsi que les situations dans lesquelles les tribunaux étatiques interviennent dans l'arbitrage.
Keywords: Arbitrage; Arbitrage commerciale; Arbitragem; Arbitraje; Arbitration; Commercial disputes; Droit OHADA; Litiges commerciaux; OHADA law; Souveraineté; Sovereignty

A legal appraisal of the minimum wage policy in the private formal sector and sustainable livelihood in urban centres in Cameroon: the case of Buea - Akamin Asonga, Patrick (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
This paper analyses the minimum wage as an instrument to provide a sustainable livelihood for employees and their families. In addressing this topic, the paper questions whether the present- day minimum wage of the country can actually enhance a sustainable livelihood for workers and their families in urban centres in general, and in the Buea municipality in particular. The paper further examines the relevant international and domestic instruments, such as the ILO Minimum Wage Fixing Convention No. 131 and the 1992 Labour Code of Cameroon. Findings reveal that the current minimum wage, which stands at 43,969 FRS, is grossly inadequate and does not match the prices of basic commodities needed for survival in the country as a whole and in Buea specifically. This, therefore, necessitates an increase in the current minimum wage. Given this situation, workers struggle to attain a sustainable livelihood. A new minimum wage policy considering Cameroon’s current economic situation could alleviate the suffering of these workers. Cet article analyse le salaire minimum en tant qu’instrument permettant d’assurer des moyens de substance durable aux travailleurs et leurs familles. Abordant cette problématique, l’étude s’interroge sur la capacité du salaire minimum actuellement en vigueur dans le pays à garantir effectivement un niveau de vie durable aux travailleurs et à leurs familles dans les centres urbains en général, et dans la municipalité de Buea en particulier. L’article examine en outre les instruments internationaux et nationaux pertinents, tel que la Convention (n° 131) de l’OIT sur la fixation des salaires minima et le Code du travail camerounais de 1992. Les résulta révèlent que le salaire minimum actuel, fixé à 43,969 FCFA est largement insuffisant, et ne correspond pas au coût des produits de première nécessité indispensables à la survie, tant a l’échelle nationale qu’à Buea en particulier. Cette situation rend donc nécessaire une revalorisation du salaire minimum en vigueur. Dans ces conditions, les travailleurs éprouvent de sérieuses difficultés à atteindre des moyens de subsistance durables. L’adoption une nouvelle politique de salaires minimum, tenant compte de la situation économique actuelle du Cameroun, pourrait contribuer à atténuer les souffrances de ces travailleurs.
Keywords: Appréciation juridique; Cameroon; Cameroun; Legal Appraisal; Minimum Wage Policy; Moyens de Substance durables; Politique du salaire minimum; Private Formal Sector; Secteur formels privés; Sustainable Livelihood

Combating trafficking in persons in Africa: efforts and enforcement challenges - Tamfuh, Wilson N.; Awa Njoworia, Valerie Adamu (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Recently, human trafficking has been on a rise with African states fighting to put an end to the crime by protecting victims, prosecuting culprits and collaborating with other partners. As a giant step towards fighting this crime, many African states ratified the Palermo Protocol, Ouagadougou Action Plan, domesticated trafficking laws and put in place institutions. Despite these efforts, trafficking in persons remain a persistent crime due to conflicts, poverty, unemployment and corruption, which increase the vulnerability of persons within and from Africa. Adopting a doctrinal research method, this paper questions the effectiveness of African States’ efforts to protect, prosecute and prevent this crime in and from Africa. It concludes that, while African states must be applauded for their efforts to protect, prosecute and collaborate with other states and organizations to combat this crime, much still remains to be done. This is due to the existence of factors like poverty, unemployment that create vulnerabilities and enforcement challenges like corruption, victim identification, delays in cross-border collaboration and weak legal frameworks. African states should therefore address underlying socio-economic factors, strengthen their domestic legal frameworks and enhance international cooperation to fully combat this crime. Récemment, la traite des êtres humains a connu une recrudescence, et les États Africains s'efforcent d'y mettre fin en protégeant les victimes, en poursuivant les auteurs et en collaborant avec d'autres partenaires. Dans le cadre de cette lutte, de nombreux États Africains ont ratifié le Protocole de Palerme et le Plan d'action de Ouagadougou, intégré des lois nationales relatives à la traite et mis en place des institutions spécialisées. Malgré ces efforts, la traite des personnes demeure un crime persistant en raison des conflits, de la pauvreté, du chômage et de la corruption, qui accroissent la vulnérabilité des personnes en Afrique et en provenance d'Afrique. Adoptant une méthode de recherche doctrinale, cet article examine l'efficacité des efforts déployés par les États Africains pour protéger, poursuivre et prévenir ce crime sur leur territoire et à partir de leur territoire. Il conclut que, alors que les États Africains doivent être salués pour leurs efforts de protection, de poursuite et de collaboration avec d'autres États et organisations pour combattre ce crime, il reste encore beaucoup à faire. Ceci s'explique par l'existence de facteurs tels que la pauvreté et le chômage, qui créent des vulnérabilités, et par des difficultés d'application de la loi comme la corruption, l'identification des victimes, les retards dans la collaboration transfrontalière et la faiblesse des cadres juridiques. Les États africains devraient donc s'attaquer aux facteurs socio économiques sous-jacents, renforcer leurs cadres juridiques nationaux et intensifier la coopération internationale afin de lutter pleinement contre ce crime.
Keywords: African States; Corruption; Palermo protocol; Pauvreté; Poverty; Protocole de Palerme; Trafficking in persons; Traite des personnes; États Africains

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - Almestarehi, Ahmad Abdel Rahim; Al-Ababneh, Hassan Ali; Malkaw, Eyad Mohammad (Theoretical and Practical Research in Economic Fields, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.
Number: 2

Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - Yeboah, Michael; Danquah, Benjamin Adjei; Bawuah, Jonas; Nkwantabisa, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

An Assessment of Concurrent Jurisdiction and Claim of Ownership of Trademarks under OAPI Legislation - Dashaco Akuriah, Nelson (International Multilingual Journal of Science and Technology, 2025)
Trademarks are economic tools that aid businesses to communicate with their customers and capture a vast section of the population. Trademarks are only useful when used efficiently in the course of trade, meaning the higher the reputation of the mark, the more consumers want to associate themselves to the products or services the mark is affixed upon. This study examines the criteria to own a trademark and how ownership claims are handled between the African Organisation of Intellectual property as known by its French acronym OAPI and the competent domestic courts found at the level of Member States which has become a breathing ground for confusion in the resolution of disputes. Due to both bodies having concurrent jurisdiction in dispute resolution, the cost has become unbearable on trademark owners or beneficiaries of an exclusive license of exploitation, coupled with inconsistency in judgements from the two structures. The article highlights some key improvements expanding trademark subject matter and provides information on how the two institutions cited above handle matters of jurisdiction based on case law. The article also brings to the limelight how the OAPI administrative litigation bodies can collaborate with the competent domestic courts to arrive at clear and concise decisions. In conclusion the paper provides some recommendations on bridging the gap between both jurisdictions in order to attain the objectives of all parties involved.
Keywords: Concurrent Jurisdiction; Intellectual property; Litigation; Ownership; Registration; Trademarks; Use

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

How the Liberation Day Announcement is Shaping the Global Trade Order: From Free Trade to Fair Trade Agreements - Ojo, Marianne (Journal of Finance Research Letters, 2025)
It may be assumed that all of the United States’ trading partners were impacted by the recent “Liberation Day” announcement – an announcement which constitutes “two distinct tariff actions” – as will be highlighted in this paper. However, despite previous concerns of being targeted by their free trade agreement (FTA) partner, Canada and Mexico – as would have been or should be expected, have been exempted from the tariff imposition. As well as addressing factors which have contributed to the shift from free trade to increasingly and predominantly protectionist stances and most likely, fair trade practices, this paper is aimed at highlighting and explaining the rationales behind the recent historical developments – as well as highlighting those factors that have triggered the build up to the Liberation Day Announcement of the 2nd April 2025. It is remarked that “Trump’s reciprocal tariff doctrine, holds foreign countries accountable”. Against this backdrop of discontent with World Trade Organisation’s dispute resolution mechanisms, which will be further elaborated on, in the paper, the immediate and possible long term impacts of the Announcement, will be considered. As well as exploring the reasons for recent developments – by way of reference to historical developments and data, the paper also considers the underlying frameworks governing the calculations of recent tariff rates and hikes. Whilst there are arguments regarding the validity of such calculations, or whether the current scenario justifies the basis for implementing “national emergency measures”, what can be regarded as an emergency response can be determined through a consideration of underlying and contributory factors. If negotiations, and more specifically, bilateral negotiations, take place as hoped, between those countries impacted by the Liberation Day Announcement, financial stability across global markets is expected to be restored. However, if retaliatory measures follow – with an escalation of trade wars, possible repercussions should be cause for concern. The global trading system is still recovering from the recent crisis which was largely uncontrollable – hence, it is more likely (and hoped) that the recent market turbulence and volatilities will be short term.
Keywords: Deregulation; Dispute resolution mechanisms; Financial stability; Free trade agreements; Manufacturing; Monetary policy; Protectionism; World Trade Organisation

Legal remedies for breach of E-commerce contracts and related offences in Cameroon: a critical analysis - Saidou, Dan Lamy Nouhou (International Multilingual Journal of Science and Technology, 2025)
Avec de plus en plus de transactions commerciales effectuées par voie électronique, les litiges résultant d'intérêts conflictuels ou de malveillance deviennent inévitables, car Internet est devenu un terreau fertile pour divers abus. Ces abus vont de la rupture de contrat et des actes délictuels aux actes criminels. Il en résulte que l'utilisation d'Internet a donné une dimension différente à ces litiges. Cependant, comme le dit la célèbre maxime Ubi Jus Ubi Remedium, là où il y a un droit, il y a un remède. Le Cameroun, suivant cette tendance, a adopté un cadre juridique qui offre une panoplie de recours disponibles pour les victimes de violations du commerce électronique et d'infractions connexes, dans l'intention de rapprocher la partie lésée le plus possible de la position qu'elle aurait occupée s'il n'y avait pas eu d'abus. Le but de cet article est d'évaluer l'efficacité du cadre actuel pour remédier aux victimes de violations du commerce électronique et d'infractions connexes. L'article examine donc les bases des responsabilités en commerce électronique et les recours disponibles pour les victimes, mettant en évidence les difficultés qui rendent ces recours moins efficaces à cet égard. Plusieurs recommandations ont été proposées par cet article pour améliorer le statu quo. With more and more business being conducted through electronic means, disputes stemming from conflicting interests or malice become inevitable, as the internet has become a breeding ground for diverse abuses. These abuses range from contractual breaches and tortious acts to criminal acts. It follows that the use of the internet has given a different dimension to these disputes. However, as the famous maxim Ubi Jus, Ubi Remedium states, where there is a right, there is a remedy. Cameroon, following this trend, adopted a legal framework that provided a panoply of remedies available to victims of breaches of e-commerce contracts and related offenses to bring the aggrieved party as close as possible to the position he would have been in if there had been no abuse. The purpose of this article is to assess the efficiency of the present framework for remedying victims of e-commerce breaches and related offenses. The article thus examines the basis for liabilities in e-commerce and the remedies available to victims, bringing out the difficulties which render these remedies less efficient for the purpose. Several recommendations have been proffer by this article to improve the status quo.
Keywords: Commerce électronique; E-commerce; Electronic transactions; Recours; Remedies; Transactions électroniques

An Organizational Theory of Corporate Law - Aguirre, Emilie; Yen, Julie; Battilana, Julie (The Journal of Corporation Law, 2025)
Corporate law is in a moment of vibrant and contentious discussions about potential reforms. As firms exit Delaware, passive investment predominates, private equity expands, and public markets decline, corporate law faces a growing set of challenges that threaten its stability and efficacy. At the same time, the world faces pressing crises, including climate change, social and economic inequalities, and threats to democracy, though corporate law scholars typically consider these crises to be outside corporate law’s remit. In this Article, we argue that to understand and address the multidimensional crises that face both corporate law and society, we must address shortcomings in corporate law doctrine. We show how modern corporate law, shaped by neoclassical economic theories, provides an incomplete picture of the firm, and we propose an expanded theoretical perspective that draws from organization theory, a field long dedicated to understanding the complexities of the firm. This updated perspective demonstrates how firms actually consist of multiple constituents, including workers, the environment, and shareholders, who invest different forms of capital in the firm: labor capital, natural capital, and financial capital. It further shows that modern corporate law entrenches problematic power imbalances, privileging boards and insider shareholders over workers, the environment, and minority shareholders. Moreover, building on organization theory, we explain how corporate law fundamentally shapes and constrains firm behavior, leading these entrenched power imbalances to generate far-reaching negative consequences. To address these shortcomings, we propose redesigning board representation, fiduciary duties, and executive compensation to empower workers, the environment, and minority shareholders in relation to boards and insider shareholders. Integrating the organizational and economic perspectives can help address problematic power imbalances and ultimately provide a more effective corporate law framework to govern firms and serve society.

Artificial Intelligence in Accounting: Revolutionizing Financial Management in the Digital Landscape - Alnaimat, Mohammad Ahmad; Korsun, Inna; Lutsenko, Kostiantyn; Khodorkovskyi, Oleksandr; Artemchuk, Mykyta (Theoretical and Practical Research in Economic Fields, 2025)
The use of artificial intelligence (AI) builds up the accounting system efficiency, increases data entry accuracy and simplifying the accounting process. The aim of the study is to prove the effectiveness of modern AI-based information technologies (IT) in accounting and the possibilities of AI application for process optimization. The effectiveness and efficiency were proven using comparison methods, statistical analysis, graphical cause-and-effect analysis, modelling using the linear regression method. The assessment was carried out using quantitative and qualitative indicators of labour productivity and process optimization. The results of the study showed that 18 accounting department employees on average are needed to perform standard transactions in the companies studied without AI. With AI, 1 person can handle such a volume of work. Accordingly, with the implementation of AI, the average reduction in Transaction Processing Time per Week is 696.26 hours. Regression analysis confirmed that the implementation of AI increases the companies’ productivity in terms of Transaction Processing Time. Reducing the Data Processing Complexity by one unit leads to a reduction in transaction processing time by 592.69 seconds. Each percent increase in Data Entry Accuracy contributes to a reduction in processing time by 5135.51 seconds. The prospects for implementing AI in accounting include further improving algorithms to increase the accuracy and speed of transaction processing, optimizing material and time consumed.
Keywords: Accounting; Artificial Intelligence; Automation; Data analytics; Digital environment; Financial management; Inteligência artificial; Intelligence Artificielle; Machine learning

Fairness, Digital Markets and Competition Law – Reconciling Fairness Norms in Digital Markets Act, Data Act and AI Act with Competition Law - Kianzad, Behrang (Journal of Law, Market & Innovation, 2025)
The present article explores the implication of fairness as a regulatory and competition law concept applied to digital and Artificial Intelligence markets, in light of recent law and policy developments targeting the interaction between data, market power and competition law. Much of the policy discussions, legislative proposals as well some emerging case law elevate the matter of “fairness” in the context of digital markets and AI, creating both a novel regulatory framework as well as encouraging competition law to curb “unfairness” of said markets and related “unfair practices”. The interface between intellectual property rights and competition law is of utmost importance in this context, where we might find similar analogous insights as we can find regarding the matter of fairness within traditional EU competition law. Further, the question remains whether the “fairness norm” expressed in regulatory acts such Digital Markets Act, EU AI Act and the EU Data Act are akin to the “fairness” norms found in Union competition law, mainly under Article 102 Treaty on the Functioning of the European Union (TFEU).

South Africa judicial review of trade remedies in South Africa - Brink, Gustav Francois (Global Trade and Customs Journal, 2025)
No abstract available.
Keywords: Judicial review; South Africa; Trade remedies

Who can become a Member of a Company under OHADA Law: A Critical Appraisal - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2025)
OHADA Law plays a crucial role in fostering economic growth and regional integration by harmonizing business regulations in the era of globalization and trade liberalization. This study examines the legal framework surrounding company membership under OHADA Law. While certain individuals such as legally incapacitated persons or those facing legal prohibitions cannot become company members, the law provides alternative solutions. The study explores the distinction between members and shareholders and clarifies the eligibility criteria for company membership. Using an analytical approach, this research finds that any natural or corporate entity, unless restricted by legal incapacity, prohibition, or incompatibility, can be a company member under OHADA Uniform Act. Furthermore, the law offers flexibility for incapacitated individuals by allowing legal representatives to act on their behalf.
Keywords: Business law; Company membership; Corporate governance; OHADA Law; Shareholder rights

Money Laundering: New Technologies and Control Challenges (Cryptocurrencies, Blockchain) - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Tackling corruption is a global issue and tackling it effectively requires determination, cooperation and specialised technological knowledge. A significant proportion of global GDP is the sum of the money associated with corruption and fraud. The main objective of this article is to assess how new technologies such as cryptocurrencies and blockchain can combat corruption. The methodology of this article is a literature review. Specifically, scientific articles from databases and international organizations with expertise in new technologies are studied. This article deals with the new ways of corruption and money laundering. New technologies and the knowledge of them are a very important element in order to deal effectively with corruption. Perpetrators of financial crimes are usually ahead of the auditing authorities in terms of techniques and therefore knowledge of the new technology and the possibilities it offers is essential to effectively combat corruption and fraud globally. Cryptocurrencies and blockchain can combat corruption primarily due to their key characteristics of transparency, security, and decentralization. A key prerequisite for the transparency of cryptocurrencies is the application of supervision rules by the responsible authorities and the implementation of blockchain technology. In practice this is often not the case and cryptocurrencies are used as a money laundering tool.
Keywords: Corruption; Cryptocurrencies; Fraud; Money laundering; New technologies

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

Examining the Impact of Remote Work on Employees, Employers, and the State in Nigeria - Adeyinka, Mutiu Abiodun; Gbajumo-sherrif, Mariam A.; Elegbede, S. Tunde (African Journal of Economic and Business Research, 2025)
Abstract The rise of remote work, accelerated by the COVID-19 pandemic, has created significant challenges for employees, employers, and the government, complicating the management of remote teams while striving to maintain productivity and organizational cohesion. The central problem addressed in this study is the deteriorating state of employment relations marked by downsizing and layoffs, particularly in the private sector in Nigeria. This study aims to analyze the impact of remote work on these stakeholders through a systematic and thematic review based on PRISMA guidelines. Twenty four publications from 2013 to 2023 were reviewed, sourced from Google Scholar, DOAJ, Scopus, and Web of Science. The findings indicate that while organizations are beginning to adopt tools for remote work and virtual communication, these resources are primarily accessible to larger companies due to associated costs. Additionally, the study highlights the pressing need for enhanced infrastructure and structural improvements to support remote work at a societal and economic level. In conclusion, the study recommends that the government enhance infrastructural development and that organizations implement better strategies for remote work. Furthermore, individuals should pursue advancements in technology to adapt to the changing landscape. These recommendations aim to promote sustainable employment relations and economic development in Nigeria in light of the evolving digital economy.
Keywords: Employees; Employment Relations; Government; Remote Work

Effects of Dynamic Capabilities and Multichannel Integration Quality on Bank Performance; A Moderated Role of Environmental Dynamism : A Moderated Mediation Model Analysis - Geleta, Negash; Amentie, Chalchissa; Getahun, Misganu (African Journal of Economic and Business Research, 2025)
This study investigates the effects of dynamic capabilities (DCs) and multichannel integration quality (MCIQ) on the performance of banks (BP). It also explores the moderating role of environmental dynamism in the banking industry, using a moderated mediation model. Quantitative analyses were employed to examine data collected from multiple banks. Structural equation modeling (SEM) was used to test the relationships between variables, while moderation and mediation effects were analyzed using SEM-AMOS. The findings reveal that dynamic capabilities and MCIQ significantly enhance bank performance. Furthermore, environmental dynamism (ED) moderates the relationship between these variables, intensifying their effects on performance under high levels of dynamism. The mediation analysis shows that MCIQ partially mediates the impact of dynamic capabilities on bank performance. The study is limited by its cross-sectional design, which restricts causal inferences. Additionally, the findings may not be generalizable to non-banking industries or regions with distinct regulatory frameworks. The results provide actionable insights for bank managers, emphasizing the importance of fostering DCs and enhancing MCIQ to sustain performance in rapidly changing environments. The findings highlight significant social benefits, as improved dynamic capabilities (DCs) and critical information quality (MCIQ) enhance bank performance, fostering economic stability, financial inclusion, and customer trust. By enabling resilience and innovation in dynamic environments, banks contribute to broader societal goals, including sustainable development and socio-economic growth. This research contributes to the literature by integrating DCs and MCIQ in a moderated mediation framework, offering a novel perspective on their interplay with environmental dynamism in the banking sector.
Keywords: Dynamic Capabilities; Environmental Dynamism; Moderated Mediation Model; Multichannel integration quality

Whistleblowers and their role in the fight against corruption. Problems in protecting whistleblowers and suggestions for improvement - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Whistleblower protection is necessary to reduce mismanagement in private and public organisations worldwide. The protection of whistleblowers is a complex and particularly challenging task that it is up to national authorities. The research methodology is the literature review. In this context, reputable scientific journals, reports from international organisations and websites dealing with the research field of whistleblowers are studied. The main conclusions are that there is an institutional framework for the functioning and protection of whistleblowers, but best practices are not fully implemented. Furthermore, the effectiveness of the use of whistleblowers is extremely high in detecting fraud and high public risks compared to other audit techniques. For this reason, the protection and framework of the whistleblower process is increasingly being legislated for by more and more countries as their importance is recognised. Finally, monitoring the use of whistleblowers and applying best practices and criteria for their effectiveness will make their use more effective.
Keywords: Corruption; Criminal activities; Financial Crime; Fraud; Whistleblower

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Emerald Publishing Limited
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

The Limits of Shareholder Ratification - Anabtawi, Iman (The Journal of Corporation Law, 2025)
In this Article, I analyze the expanding common law doctrine of shareholder ratification, whereby shareholder approval can, for all practical purposes, absolve directors of fiduciary liability for their conflicted business decisions. Delaware law now allows a shareholder vote to perform substantially more work than ever before. Under prevailing doctrine, in transactions between a company and any party other than a controlling shareholder, shareholder ratification reinstates the business judgment rule and makes it irrebuttable, other than for waste. Substantive judicial review is effectively avoided for such transactions. Despite its extraordinary importance in corporate governance, the shareholder ratification doctrine’s foundations are feeble and its limits uncertain. Theoretically, there is no well-established basis for equating shareholder approval with either the informed, disinterested, and good-faith decision of a board or judicial review. Doctrinally, shareholder ratification’s expansion beyond its traditional context of self-dealing has been a judicial innovation, rather than an elaboration of precedent. And historically, the shareholder ratification doctrine, which originated in early 20th-century state interesteddirector statutes, was motivated by fairness principles that were lost in translation into the common law. This Article recovers the fairness genealogy of the shareholder ratification doctrine and, in doing so, provides useful guidance for the doctrine’s development, limits, and future application.

The Effectiveness of the Legal Frameworks in the establishment of Liability of Land Transport Operators in cases of Accidents in Cameroon: A Critical Appraisal - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2025)
The liability of land transport operators in Cameroon is guaranteed by a good number of laws including; the constitution of Cameroon, the penal code, the 2001 law governing the Profession of Road Transport Operators, the 2023 law governing the rail sector in Cameroon and more. Such liability can be under the Tort of negligence, vicarious liability, or strict liability as provided for under section 289(1) of the Cameroonian penal code on Unintentional killing. However, the laxity of the courts in handling accident-related disputes, the contradictory and vague nature of the laws on the liability regime and even the lenient nature of the sanctions provided for by these laws do not meet up with the rate of accidents today in Cameroon. This article therefore has as its objective to examine the effectiveness of the legal frameworks in the establishment of liability of land transport operators in cases of accidents in Cameroon. Arguably, the author holds that the legal frameworks establishing the liability of land transport operators in cases of an accident in Cameroon are ineffective. A doctrinal research method has been adopted where both primary and secondary sources of information have been consulted. Our finding reveals that; the ineffectiveness of legal frameworks in the establishment of the liability of land transport operators in cases of accidents is a result of the laxity of the courts in implementing the laws and, the vague and contradictor nature of the law. We, therefore, recommend that; separate court hearings should be set for accident-related disputes and judges trained only on that, the laws should be revised, the sanctions in cases of accidents should be increased and all mitigating circumstances in cases of accidents should not be taken into consideration like a first-time offender, the plea of guilt etc.
Keywords: Accidents; Cameroun; Land Transport Operators; Liability; Opérateurs de transport terrestre; Responsabilité; Transport terrestre

The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management

Internationality overreach in the interpretation of uniform private law conventions: the Contra Proferentem rule and the CISG - Kryla-Cudna, Katarzyna (International and comparative law quarterly, 2025)
This article argues that the rule of contra proferentem is not applicable to international sales contracts governed by the United Nations Convention on Contracts for the International Sale of Goods (CISG). It further argues that the common recognition of the rule of contra proferentem under the CISG is an instance of a broader phenomenon which it calls ‘internationality overreach’. ‘Internationality overreach’ is the tendency to project onto the provisions of a uniform private law instrument doctrines and concepts which are inaccurately presumed to constitute universally recognised principles of private law or the ‘common core’ of various legal systems. This article demonstrates that internationality overreach disrupts the goals underpinning the harmonisation of commercial law in two ways: first, it undermines uniformity in the application of international conventions; and, second, it leads to outcomes that fall short of the agreement reached by the Contracting States during the drafting process. While this article focuses on the CISG, the argument developed in this article is of equal relevance to other uniform private law conventions which follow the principle of autonomous interpretation.
Keywords: INTERNATIONAL SALE OF GOODS; INTERNATIONAL TRADE LAW; UN Convention on Contracts for the International Sale of Goods (1980)

Corporate purpose and governance in Africa: French-influenced OHADA law, local norms, and heterodox pluralism - Minzoto, Bonheur (Journal of Corporate Law Studies, 2025)
This article examines corporate governance in Africa and its significance for corporate repurposing. It relies on the framework of the Organisation for the Harmonisation of Business Law in Africa (OHADA), which unites seventeen African states under one corporate law jurisdiction while exploring how the interpretation and practice of this legal system can be integrated with or influenced by national sectoral laws and cultural norms. The workings of these different legal sources denote the case for heterodox pluralism of corporate purpose, whereby corporate membership is not tethered to shareholding only, but the workforce and neighbouring too and corporate legitimacy is not merely a function of legal arrangements but equally derives from broader society. The governance of corporations in Africa must correspond to such imperatives to ensure that the prevailing shareholder primacy norm does not continue its unencumbered de facto reign and reduce African stakeholderism to comparative impotence and mere scholarly exercise.
Keywords: CSR; Corporate governance; Corporate purpose; DRC mining legislation; Directors’ liability; Directors’ sustainability duties; Local cultures

Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Impact of the Revision of the OHADA Accounting System on the Decision to Grant Bank Credit to Cameroonian Companies: An Interview with Credit Analysts - Sekadjie, Dedy Christelle; Mbohwa, Charles (Journal of Accounting and Finance in Emerging Economies, 2024)
Purpose: The objective of this study is to evaluate the impact of accounting data produced after the revision of the OHADA accounting system on the decision to grant bank credit to Cameroonian companies. Methodology: qualitative approach was used in this study. We conducted semi-structured interviews with eight credit analysts in eight banks based in Cameroon. We used the Nvivo 10 software to carry out the content analysis. Findings: It emerges from the analysis of the content of the speeches collected that the most used ratios by credit analysts are: activity ratios, debt ratios, operating ratios, financial structure and autonomy ratios, debt ratios and net cash. In addition, the information provided by the new accounting system is increasingly fluid, detailed, and precise and facilitates decision-making. However, when it comes to the completeness and sincerity of the information provided, analysts remain wary because, companies always provide information subjectively based on their interests Implication: This study reveals that despite the revision of the accounting system, users still remain wary face of informations provided because of its subjective nature. It is therefore recommended that Member States promote unified information for all stakeholders.
Keywords: Accounting system; Bank credit; Decision-making; Revision

New Public Management Reforms and the Performance of Public Enterprises: An Assessment of Privatization in Nigeria's Telecommunications Sector - Adejuwon, David; Amodu, Akeem; Majekodunmi, Aderonke (African Journal of Politics and Administrative Studies, 2024)
The implementation of New Public Management (NPM) reforms, particularly privatization, has been a significant strategy adopted by governments worldwide to enhance the performance of public enterprises. This article focuses on the telecommunications sector in Nigeria, where privatization was introduced as part of broader economic reforms in the early 2000s. The objective is to assess the influence of privatization on the performance of public enterprises within this sector. The article is anchored on public choice theory. It is qualitative in nature, relying on secondary sources of data, such as, journals, textbooks, official publications and internet materials. It observes that privatization of public enterprises in the telecommunication sector in Nigeria has led to improvements in operational efficiency, increased investment inflows, and expanded service coverage. However, challenges such as regulatory effectiveness, equity in service provision, and the socio-economic impact on marginalized populations remain significant concerns. It contributes to the broader discourse on NPM reforms by providing empirical insights into the complexities and outcomes of privatization within Nigeria's telecommunications sector. It concludes with policy recommendations aimed at optimizing the benefits of privatization while addressing its associated challenges to ensure sustainable and inclusive growth in the sector.
Keywords: New Public Management; Operational Efficiency; Privatisation; Public Enterprises; Public Sector Performance; Service Delivery

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

Nigeria-United States Economic Relations and the Development of the Oil Sector - Okorie, Ikechukwu; Iwuozor, Obialor; Itumo, Anthony (African Journal of Politics and Administrative Studies, 2024)
This study examines Nigeria – United States economic relations from 1999-2018. It was noted that since the Nigeria’s economic relation with United States, the development stride which Nigeria state so desired in the oil sector did not yield any tangible result within the period under study viz opening of new refineries and effective turn around maintenance of the refineries. The specific objectives of this study are: 1. To examine whether Nigeria-United States economic relations has led to opening of new indigenous refineries in Nigeria 2.To determine whether Nigeria–United States economic relations improved the maintenance of refineries in Nigeria within the periods under study 3.To ascertain if Nigeria and United States economic relations had advanced technological transfer in the oil sector industry in Nigeria. The data employed for the study were collected from documentary sources while content analysis was implored for data analysis. The theoretical framework that anchored this study is the Rentier State Theory (RST). After a critical analysis, the following findings were made: 1. it was discovered that Nigeria United States economic relations did not lead to opening of new indigenous refinery 2. The crude oil export to the United States did not improve the maintenance of oil refinery in Nigeria 3. The Nigeria-United States economic relations had not advanced technological transfer in the oil sector industry in Nigeria. In line with the findings the researcher made the following recommendations: 1.That Nigeria government should make a policy that will bring a paradigm shift from net import to net export 2. Nigerian government should make it policy easier as to accommodate and encourage private sector participation in the refining of petroleum products 3. Nigeria government should partner with other countries of the world outside United States that are willing to develop her indigenous technological skills.
Keywords: Crude oil; Development; Economic Relations; Oil sector; Petroleum

Corporate social responsibility performance of property-development firms in Nigerian south-western urban cities - Oyesomo, Oyewole; Oyedeji, Oyewale; Saheed, Omobolaji; Anifowose, Titilayo (Acta Structilia, 2024)
Previous studies on corporate social responsibility (CSR) in the construction and property-development domain have mainly focused on countries in the Global North with very few studies in the Global South. These prior studies have defined the pyramid elements (economic, legal, ethical, and philanthropic) that make up overall CSR, but none of them have assessed how well corporations performed in relation to each pyramid element, particularly in the property-development industry. Consequently, reflecting on the limited CSR studies in the Global South, this study examines the performance of property-development companies regarding the CSR pyramid elements. The study also assesses the barriers and strategic drivers of CSR among property-development companies. The study employed a descriptive survey research, and questionnaires were administered to 43 property-development companies. Descriptive data analysis was done to rank the relative importance of items from the questionnaire. Results showed that, although companies performed ‘well’ in their legal CSR, and ‘average’ in their economic and ethical CSR, companies performed ‘poorly’ in the area of philanthropic CSR. Lack of support by top management, corruption/lack of transparency, lack of knowledge and awareness by professionals, and lack of regulatory framework were identified as significant barriers to CSR implementation among property-development companies. Vision of founders/support by top management, regulatory framework, stakeholder activism, and good relationship-building are potential key strategic drivers of CSR implementation programmes among property-development companies. Given the findings, it is recommended that property-development companies should integrate CSR principles into their vision and mission statement and consider it to be a business function. This can be done by mitigating the barriers identified through the adoption of strategic drivers as postulated by this study.
Keywords: CSR; RSE

SME contractors’ management practices to achieve sustainable business performance in the Eastern Cape province, South Africa - Sogaxa, Athenkosi (Acta Structilia, 2024)
The construction industry in the Eastern Cape province of South Africa plays a crucial role in the region’s economy, yet small and medium enterprise (SME) construction companies face significant challenges in achieving long-term business sustainability. This article aims to provide practical guidelines for SMEs, by investigating the most critical construction management practices adopted by SME contractors. Utilising a quantitative approach, data were collected from 59 purposefully selected participants, including directors, construction managers, quantity surveyors, site agents, and technicians, all registered under the Construction Industry Development Board (CIDB) Grades 1-4 in General Building (GB). The management practices of SME contractors were analysed using the relative importance index (RII) and factor analysis to rank these practices according to their significance. Findings indicate that SME contractors prioritise health and safety strategies, effective resource utilisation, integrated project management systems, competent recruitment, strong leadership skills, and robust health and safety management as essential practices. The principal component analysis identified six key management factors to enhance competitiveness while contributing to the region’s sustainable development goals. These factors include shared knowledge among management, effective project scope planning, comprehensive health and safety management, ownership of construction business knowledge, scope control on projects, and clearly defined goals for management teams. This study is original in its focus on the specific management practices that can strengthen the sustainability of SME contractors within a developing region, providing a valuable framework for enhancing their operational effectiveness.

Intra-Africa trade and the need to rethink the neo-liberal approach - Ngwu, Franklin; Ojah, Kalu (Transnational Corporations Review, 2024)
Notwithstanding past trade reforms, trade in Africa and particularly intra-Africa trade, remain dismal. Africa has even created economic communities, fitted with monetary, fiscal, and socio-political anchors, by way of various Regional Economic Communities (RECs) – now reflected by the African Continental Free Trade Area (AfCFTA). Whilst these have yielded marginal benefits, the persistence of low intra-Africa trade calls into question their suitability. Focused on the realities of institutions targeted by these reforms and Africa's context – i.e., weak linkages between institutions, high informality, and low social capital – we posit that reforms have not elicited the hoped-for high intra-Africa trade because of their near total reliance on the neo-liberal approach, which neglects Africa's context. Drawing on Africa's sociology and new institutional economics, we use a conceptual institutional analysis to evolve a political economy based framework that suggests potential solutions: Linking the formal sector that currently underpins economic/trade policies to the informal institutions that are reflective of Africa's norms, values, cultures and expectations (the informal sector), and scaling up production; via the cooperatives production model, strategic procurement mandates, and effectuation of continental transportation infrastructure network, are our recommended pathways to reversing the current dismal intra-continental trade.
Keywords: Africa; Africa's sociology; Growth and trade policies; Institutional economics; Intra-Africa trade

Diaspora as a Generator of Foreign Direct Investment - Dizdarević, Emina (IUS LAW Journal, 2024)
Focusing on Bosnia and Herzegovina, this study examines how diasporas contribute to the creation of foreign direct investment (FDI) in developing countries. It defines FDI as the acquirement over assets in a foreign nation and highlights how diaspora populations support investment flows. It also examines diaspora investment strategies, such as diaspora portfolio investment (DPI) and diaspora direct investment (DDI), and offers a historical overview of diaspora FDI patterns and how Bosnia and Herzegovina's policies are changing to engage its diaspora more.One case study illustrates the impact of diaspora-led FDI by highlighting the success of Senad Šantić, a Bosnian entrepreneur who returned to his home country to start a tech company. While these investments support development and economic growth, there are still issues, like the possibility of putting one's own interests ahead of the interests of the economy as a whole. Particularly in Bosnia and Herzegovina, where diaspora participation has historically been low, the implementation of effective policies and procedures is crucial, especially from a regulation perspective.The study also looks at the future of FDI, emphasizing the part that digital technology and new investment patterns will play. Opportunities for developing nations can be found in digital FDI, especially in industries like fintech and e-commerce, yet obstacles still exist in luring these investments. According to all the findings, developing nations can improve their chances for economic success by creating an atmosphere that encourages diaspora investment which will shift those nations into the global investment scene. Ultimately, FDI regulations and government programs are needed in order to fully utilize diaspora-led FDI for sustained growth.
Keywords: Bosnia and Herzegovina; Diaspora Engagement; Diaspora Investment; Economic Development; FDI; Foreign direct investment

The Blockchain Data Gatekeepers Limited Liability for Violations of the GDPR - Jusić, Asim (IUS LAW Journal, 2024)
Data gatekeepers (data controllers and processors) that use blockchain for data transfer effectively enjoy limited liability for violations of the GDPR. This is due to the fact that applying the GDPR’s data gatekeeper system of liability to a decentralized technology such as blockchain is difficult for three reasons. Firstly, identifying data gatekeepers on the blockchain can only be done by either assigning data gatekeeper roles to actors on the blockchain, or structuring the blockchain as private or permissioned one, so as to fit with GDPR requirements. Neither of these approaches provides a universally applicable and satisfactory method for privacy protection. Secondly, because of their knowledge and investment in infrastructure, large data gatekeepers such as IBM, Amazon and Microsoft have an informational advantage over data protection authorities (DPAs) and an additional protective layer against liability, as their blockchain infrastructure is used by other businesses and corporations that are primarily liable for data processing. Finally, administrative fines and reputational damages for non-compliance with the GDPR are insufficient deterrents for large data gatekeepers, whereas damages awarded to individual data subjects for data gatekeepers’ violations of GDPR are extremely low and too costly to obtain.
Keywords: Blockchain; Compliance; Data gatekeepers; GDPR; Liability

Business Environment and its Impact on Attracting Foreign Direct Investment - Tanrıverdi, Elif Tanrıverdi (IUS LAW Journal, 2024)
This study provides an in-depth look at the complex relationship between business environments and foreign direct investment. The study examines this critical issue by focusing on emerging economies, such as Kosovo. In this research, analytical and empirical research methods have used to highlight the importance of FDI in promoting economic growth. FDI not only increases production capacity but also supports economic growth by increasing purchasing power and creating employment opportunities, especially in countries in transition. This analysis distinguishes between endogenous and exogenous variables to classify the various elements of the business environment. It is important to emphasize how a supportive business environment plays a vital role in attracting investment. The main factors affecting FDI include infrastructure quality, political stability, workforce skills, market potential and tax incentives. These initiatives are critical to creating a more favorable investment climate.As a result of the variables the study concludes by emphasizing the need for continuous reforms to strengthen the business environment. Such strategic efforts are crucial to optimize FDI flows and advance sustainable economic development. By strengthening regulatory frameworks and improving infrastructure, developing countries can be in better position itself to attract foreign investors. Furthermore, creating a strong business environment can also support the development of local entrepreneurs, increasing economic diversification. As a result, it not only facilitates the flow of capital, but also contributes to the long-term stability and growth of the national economy. Therefore, policymakers and governments need to prioritize these initiatives and develop comprehensive and sustainable strategies to improve the business environment.
Keywords: Business Environment; Economic growth; Foreign direct investment; Investment Incentives; Investments; Political Stability

The role and mandate of the motor industry ombudsman of South Africa : addressing prospects and challenges to enhance consumer protection - Tshabalala, Thapelo; Magau, Phemelo (PER / PELJ, 2024)
The Motor Industry Ombudsman of South Africa (MIOSA) is an industry ombud recognised under the Consumer Protection Act 68 of 2008 (CPA). The MIOSA regulates the interaction and provides for alternative dispute resolution in the automotive and related industries in South Africa. Moreover, the MIOSA is an impartial organisation that focusses on the resolution of disputes where a deadlock has been reached between the automotive and related industries and their customers, as well as relationships among participants in the automotive and related industries to the benefit of the parties. The role of the MIOSA is to make recommendations in cases referred to it where parties cannot reach common ground and are unable to arrive at mutually acceptable agreements following a dispute. This analysis explores and proffers possible solutions to address the challenges that impede the MIOSA from discharging its role and mandate under the CPA effectively in resolving consumer disputes in the South African automotive industry.
Keywords: Automotive industry; Consumer protection; Dispute resolution; MIOSA; Ombuds

Legal Certainty in the Resolution Process of Business Disputes due to Default on Payment with Bank Guarantee through Arbitration - Wijaya, Didit Wijayanto (International Journal of Science and Research, 2024)
Corporations have been established and recognized in Indonesia as entities engaged in business activities since 1602. In these business activities, disputes can occur regarding the non-disbursement of Bank Guarantees through the Indonesian National Arbitration Board (BANI). Therefore, this research uses the Normative Juridical method through a literature review. The research questions considered are (1) What is the guarantee of legal certainty in the process of resolving business disputes regarding Bank Guarantee payments through the Arbitration Board? (20) What can the Supreme Court Decision provide legal certainty for resolving business disputes through arbitration in Indonesia? The process of resolving business disputes in default on Bank Guarantee payments through the Arbitration Court has fulfilled the legal certainty principle. The results showed that the rules were available through different Arbitration and Alternative Dispute Resolution Laws, as well as other laws applied consistently in the BANI Surabaya Decision Number 59/ARB/BANI-SBY/XI/2021. The Supreme Court Decision Number 918 B/Pdt.Sus-Arbt/2023 tried the appeal case and rejected the application for annulment of the arbitration decision from the Applicant. In addition, legal certainty is created for corporate legal efforts to take the arbitration route.
Keywords: Arbitrage; Arbitragem; Arbitration; Business Disputes; Default; Legal Certainty

An Exploration of Selected Anti-Money Laundering Role-Players in Zimbabwe - Chitimira, Howard; Torerai, Elfas; Jana, Vimbai (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Anti-money laundering; Corruption; Financial crimes; Money laundering; Role-players

Attachment Proceedings for Goods Onboard an Aircraft: A Closer Look at the OHADA Law on Simplified Recovery Procedures and Measures of Execution - Atemlefac, Atemnkeng Micheal (Scholars International Journal of Law Crime and Justice, 2024)
The practical application of international conventions like the Montreal Convention of 1999 and the OHADA Uniform Act of 2023 in the context of attaching goods onboard aircraft presents significant challenges. These frameworks do not explicitly address the attachment of such goods, focusing instead on liability and recovery procedures. The OHADA Uniform Act aims to simplify recovery processes but may struggle with conflicting national regulations and regional legal practices. The absence of specific legislation for attaching goods in-flight creates a critical gap, leading to uncertainty and inefficiency in enforcement. Addressing this gap in this paper requires developing targeted legal solutions that align with international standards while addressing the unique demand of air transport.
OpenAlex: https://openalex.org/W4403880779
Keywords: Aircraft; Goods; Measures of Execution; Simplified Recovery Procedures

Lawyers and Non-Lawyers in International Arbitration: Discovering Diminishing Diversity - Nottage, Luke; Teramura, Nobumichi; Tanna, James (Loyola of Los Angeles International and Comparative Law Review, 2024)

Termination of the Mandate of an Agent: An Examination under OHADA Uniform Act on General Commercial Law - Ndekwena Noh, Alison (Scholars International Journal of Law Crime and Justice, 2024)
When an agency relationship is created, it confers on the parties obligations which must be fulfilled by the parties. These obligations do not remain forever as they can come to an end. This can be done under normal circumstances by the act of the parties or by operation of the law and when the conduct of the agent is in contradiction to the mandate agreement as may be the case if the agent is liable for serious misconduct as provided by the OHADA Uniform Act on General Commercial Law. The provisions of the act regarding termination on grounds of serious misconduct is worrisome, as the act talks about termination in such manner only for commercial agents and is silent about the other two types of agents: the broker and the commission agent. The act also, does not tell us what this serious misconduct it mentions by the commercial agent is, nor gives us insights on what constitutes such conduct to warrant termination of the mandate of the agent by the principal. When termination of the agency is done under conditions as such, it has grave consequences on the agent who might not be entitled to certain benefits associated with termination of the contract such as loss of the right to compensatory allowance or indemnity and more importantly may give room to arbitrary or wrongful termination of the mandate of the agent. Through analytical and comparative studies, this paper focuses on termination of the mandate of an agent under the OHADA Uniform Act on General Commercial Law, wherein, the different modes of termination of the mandate of an agent have been discussed, and more specifically makes an attempt in looking at what serious misconduct is and what could amount to such conduct so as to avoid arbitrary or wrongful termination. It is therefore suggested that, statutory guidelines found in other statutes in relation to the subject matter can serve as a lamp light in our context.
OpenAlex: https://openalex.org/W4403198358
Keywords: Mandate

Editorial on Doing business in Africa: Navigating opportunities and challenges in Africa's emerging markets - Adomako, Samuel; Shenkar, Oded; Liu, Xiaohui; Amankwah-Amoah, Joseph; Ahsan, Mujtaba (Journal of International Management, 2024)
This editorial delves into the evolving context of doing business in Africa, tracing its journey from being dubbed the “hopeless continent” to becoming a beacon of hope and opportunity. Drawing on a wealth of scholarly research, it highlights Africa's increasing attractiveness for global investments, underscored by rising FDI inflows and the emergence of a vibrant middle class. Despite these promising trends, the editorial also sheds light on the persistent challenges, including institutional fragility and political instability, coupled with limited representation in the existing international business discourse. We advance a more nuanced understanding of Africa's business environment, emphasizing the need for responsible growth, improved governance, and sustainable development. Thus, the Special Issue offers insights into the complexities and challenges of doing business in Africa, as well as the paradoxes and potential for fostering competitiveness and inclusive growth on the global stage.
Keywords: Africa; Doing business; International business; MNEs

Product liability in an age of development risks : should South Africa reconsider adopting a development risk defence? - Tennant, Sarah-lynn; Van Heerden, C. M. (Corlia) (Journal of African Law, 2024)
To provide protection against harm caused by defective, unsafe products and to promote product safety, the law of product liability has developed as a specialized area of the law of delict (tort). The vexing question is, who should bear such liability? This contribution interrogates the notorious EU development risk defence, which exonerates manufacturers that meet certain stringent requirements for undiscoverable development risks in products that consequently inflict harm on consumers. In particular, it considers the election by South Africa, which recently adopted a “strict” product liability regime with the introduction of the Consumer Protection Act 2008, not to adopt such a defence. The purpose of this contribution is to consider the nature and scope of the development risk defence as contained in article 7(e) of the European Union (EU) Product Liability Directive and to determine whether it was prudent for South Africa to steer clear of incorporating a similar defence in its new statutory product liability regime.
Keywords: Defective product; Developmental risk; Hybrid regime; Product liability; Strict liability

Beyond free trade in raw materials: Reconciling international trade rules with planetary boundaries - Kuppuswamy, Chamundeeswari; Boklan, Daria (The Extractive Industries and Society, 2024)
International trade rules enshrined in agreements like the General Agreement on Tariffs and Trade (GATT) promote free trade, with exceptions for environmental protection. This paper explores the tension between these rules and Earth Systems Science's concept of planetary boundaries, which define environmental tipping points beyond which humanity faces irreversible harm. We analyse GATT's provisions, particularly Article XI's prohibition on trade restrictions and Article XX's exceptions, through the lens of planetary boundaries. Our analysis argues that current interpretations of these articles are inadequate to address the environmental impact of raw material trade. We further examine the concept of permanent sovereignty over natural resources, which grants states autonomy over resource exploitation and trade. We posit that planetary boundaries are not a restriction on sovereignty but a call for modifying state trading behaviour and consequently how international trade rules is structured and interpreted. This analysis demonstrates the complexity of transforming the legal landscape necessary for a global just energy transition, a response to climate change that requires aligning international trade with environmental sustainability.
Keywords: Climate change; GATT Art. XX; No-harm principle; PSNR; Planetary boundaries; WTO trade rules

Anticipation of ratings during crises and investor behaviour: The case of MENA countries - Mahouachi, Noura; Henchiri, Jamel Eddine (African Journal of Economic and Business Research, 2024)
The study explores the reaction of stock markets to anticipated or unexpected rating announcements by the market in a crisis context by conducting an empirical study on the MENA (Middle East and North Africa) stock market over the period from December 2010 to August 2022. The results show that the crisis context support the anticipation of bad ratings and neutral ratings as opposed to good ratings. These results validate the asymmetry in investor reaction to announcements of anticipated rating downgrades compared with announcements of upgrades in times of crisis. This reaction highlights the irrational behave of investors in times of crisis. In fact, when investors detect a risk concerning the financial situation of a stock, they anticipate a downgrade and react quickly, even before the official announcement of the downgrade, by selling their shares on masse. This action will cause the share price to fall. Similarly, the market’s weak reaction to early good announcements is explained by the fact that this type of announcement does not provide them with any unknown information to guide their financial decisions.
Keywords: Abnormal returns; Anticipation; Event study; Expected rating; Stock markets; Unexpected rating

The Impact of Financial Technology (Fin Tech) on Economic Growth: Evidence from Tanzania - Ngeze, Raphael Michael; Seif, Muba (African Journal of Economic and Business Research, 2024)
This research is driven by the rapid spread of fintech, and its contributions to Tanzania’s economic growth. This study uses quantitative quarterly time series data from Tanzania from 2008 to 2022. The Augmented Dicky Fuler (ADF) is used for the stationarity test, Johansen Cointegrations for the hypothesis and Cointegrations test, VAR and VECM for testing both short-run and long-run causality relationships, and Granger Causality for testing variable causality. The Ordinary Least Squares (OLS) regression model is used for parameter estimation, modelling and significance testing. The results show that the model is statistically significant and the independent variables in the regression accounted for around 89% of the overall variation in GDP. Fintech variable subscriptions have a positive impact on Tanzania’s economic growth. Thus, unemployment in Tanzania may be alleviated by the growing sector of financial technology. Fintech has involved many people from all over the world, including Tanzania, and has had a positive impact on both the national economy and per capita growth. Since TTCL and ZANTEL have witnessed a sharp decline in subscriptions, the government, as a fixed-wired broadband service provider, must take the necessary steps to increase the subscriptions.
Keywords: Economic growth; Financial Technology; M-Pesa; OLS; VAR; VECM

Effect of Taxpayer’s Attitudes on Tax Evasion among SMEs in Tanzania: A Case of Singida Tax Region - Chindengwike, James (African Journal of Economic and Business Research, 2024)
Paying taxes is essential to attaining sustainable economic growth and national economic independence, hence tax evasion is a concern for the economies of both wealthy and developing countries. This study examined how tax payer attitudes, particularly in the Singida Tax Region, affect tax evasion in Tanzanian Small and Medium-Sized Enterprises (SMEs). This study employed a survey method in which data collection comprised both qualitative and quantitative research approaches. A multiple regression model was employed in combination with a descriptive study approach to ascertain the outcomes. 145 SMEs taxpayers made up the study's as a sample size. The findings demonstrate that, among SMEs in the Singida Region, peer influence, tax awareness, tax morale, and tax evasion have statistically significant relationships with the taxpayer's attitude. This association is supported by statistics. Consequently, the United Republic of Tanzanian government needs to consider how taxpayer attitudes including peer pressure, tax knowledge, and morale affect tax evasion. This will contribute to the goal of reducing tax avoidance by all taxpayers, including SMEs Taxpayers.
Keywords: SMEs Taxpayers; Tanzania; Tax evasion; Taxpayer’s Attitudes

African Continental Free Trade Area and Regional Trade in ICT and Digital Technologies - Adams, Kweku; Attah-Boakye, Rexford; Yu, Honglan; Chu, Irene; Mali, Dafydd (Journal of International Management, 2024)
This study examines the impact of the African Continental Free Trade Area (AfCFTA) on regional trade in the Information and Communication Technology (ICT) and Digital Technologies (DT) sector across 43 African countries from 2014 to 2021. Employing the augmented gravity model and confidence-level estimations, it highlights AfCFTA's mediating role in enabling ICT&DT trade on the continent. Using hierarchical regression analysis of a panel dataset comprising 5,160 observations, the findings imply that trade openness and productive capacities not only facilitate trade in the ICT&DT sector but also result in positive spillover effects across various economic sectors. This study contributes to the international business literature by refining the application of the gravity model to capture the need for sector-specific analyses to unpack institutional dynamics and dis-enablers of trade. It identifies AfCFTA as a pivotal yet underexplored element in the global trade landscape, highlighting its potential as Africa seeks a more prominent role on the global stage. The research stresses the significance of digital empowerment and policy reforms to maximise the benefits of regional integration under AfCFTA.
Keywords: AfCFTA; ICT and digital technologies; Regional trade; Trade enablers; Trading bloc

Joint and several liability at the interface of national and international law and the FIDIC conditions of contract - Mahasneh, Nisreen (Uniform Law Review, 2024)
The international terms of the 2017 FIDIC Red Book (reprinted and amended in 2022) state that, when the contractor is a joint venture (JV), all members are jointly and severally liable to the employer. These terms also establish certain procedural rules—the most important ones being the submission to the employer of the JV undertaking and the appointment of a leader. However, these international terms do not provide for substantive rules pertaining to the plurality of the JV members. These require reference to the applicable law that governs the construction contract. The applicable law can be domestic law, such as Qatari law, or an international soft law, such as the Unidroit Principles. Comparing these two possibly applicable laws, it becomes evident that there are no significant differences between the two regarding the substantive rules concerning a plurality of obligors. Furthermore, it is argued that the majority of these substantive legal rules, whether national or international, are inoperative in a construction contract incorporating the international terms of the FIDIC Red Book.

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

Cross-border banking and bank stability: evidence from Sub-Saharan Africa - Gondwe, Sopani; Gwatidzo, Tendai; Mahonye, Nyasha (Journal of Banking Regulation, 2024)
Based on bank-level data from 29 Sub-Saharan African countries between 2005 and 2019, we apply panel fixed effects (FE) and two-step system GMM estimators to investigate whether increased cross-border banking affects domestic banking sector stability. We find significant evidence that the stability of banks in host countries declines with an increased presence of foreign banks—and the impact is more pronounced on banks that are small and less efficient. The stability impact of foreign banks is also found to depend on the quality of governance institutional factors in the host country. The findings shed some important insights on the downside of financial liberalisation policy in developing countries and the need for increased cross-border collaboration between home and host supervisory authorities in the SSA region—especially in jurisdictions where the foreign bank affiliates are systemically important. The domestic supervisory authorities thus need to effectively manage the inherent trade-off between reaping the benefits from international financial integration while effectively safeguarding domestic banking systems against cross-border contagion and fragility.
Keywords: Bank stability; Consolidated supervision; Cross-border banks; Home-host countries; Systemically important

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

Characterization (and Registration) of a “BRI Dispute” - Kirkwood, Jamieson (Asian Journal of International Law, 2024)
This article explores the terms “BRI dispute” and “BRI jurisprudence”. It undertakes a practical and theoretical analysis that considers whether “BRI disputes” have distinct and visible characteristics and are capable of being identified in a legal sense. This is important since practitioners – arbitration centres and law firms – use the term broadly and without specific criteria. By exploring the customary usage and the approach of legal scholars to the term, presenting examples of “BRI disputes” and examining their unique features, and constructing a theoretical approach (utilizing the concepts of ratione materiae, ratione loci, ratione temporis, and ratione personae; and considering the jurisprudence of the ICSID), this article moves from a broad to a narrow analysis to develop both a definition and a system of registration of “BRI disputes” for use by academics, practitioners, and policymakers.
Keywords: BRI; Belt and Road; China; Dispute Settlement; ICSID

An overview of the extent of the powers of South African competition authorities in the regulation of price discrimination under the Competition Act 89 of 1998 in the context of digital transformation - Magau, Phemelo (PER / PELJ, 2024)
The purpose of the Competition Act 89 of 1998 as amended (the Competition Act) is, among others, to promote the efficiency, adaptability and development of the economy as well as to provide consumers with competitive prices and product choices. In line with this purpose, the Competition Act provides that a dominant firm is prohibited from engaging in price discrimination if such conduct will likely substantially prevent or lessen competition, which would be to the detriment of consumers. Notably, the Competition Act has established various bodies to regulate competition and act against any conduct prohibited by this Act in South Africa. These bodies include the Competition Commission, the Competition Tribunal, and the Competition Appeal Court. Notwithstanding the prohibition of price discrimination, the Competition Act does not expressly provide adequate enforcement tools for competition authorities to combat uncompetitive practices in the digital era. Moreover, the Competition Act does not expressly grant these statutory bodies clear roles and mandates on providing consumers with adequate and suitable redress when they have been victims of algorithmic price discrimination. With recent technological developments, electronic commerce (e-commerce), and digital transformation, consumers have become vulnerable to various challenges such as excessive pricing, data breaches and algorithmic pricing. The online and digital markets are characterised by complex transactions, innovative technologies and business practices which expose all consumers, including vulnerable consumers, to different risks. As such, the role of the competition authorities needs to be recalibrated to enhance consumer protection on the pricing of goods and services. To this end this paper seeks to investigate the role and ambit of the powers of these competition authorities in the regulation of price discrimination in the context of digital transformation and the digital economy. This is done to assess whether the competition authorities have the necessary tools of enforcement to ensure that markets are competitive and to combat uncompetitive conduct in the digital economy and online markets.
Keywords: Algorithmic pricing; Competition authorities; Consumer protection; Digital transformation; Price discrimination

Multilateralism and Bilateralism in International Trade - Aro, Gilbert; Nwosu, Chiedozie; Ngene, Innocent; Nnadi, Samuel (African Journal of Politics and Administrative Studies, 2024)
The contemporary international system is dominated by international trade. Therefore, it is the fundamental and critical aspect of international economic relations. The study investigated the how African states participate in common bilateral and multilateral trade relations. Its core objective is to study whether trade barriers have been made less cumbersome among the participating countries in African continental region. Common trade and international trade justify the essence of globalization. The wave of globalization has necessitated the flux of multilateralism and bilateralism among the participating nations in the international trade. Methodologically, the study adopted comparative theory of international trade. Its method of data collection is documentary method and analyzed through interpretive studies. As the international trade continues to take the centre stage in the international economic relations; States continue to engage in multilateral and bilateral trade relations. The operations of Transnational Corporations (TNCs) and Multi-national Corporations (MNCs) as non-state actors also engage in multilateral and bilateral agreements with the host states. Several agreements led to the establishment of General Agreement on Tariff and Trade (GATT) and World Trade Organization (WTO) remains conspicuous products of multilateralism and bilateralism in the international trade in the recent time. African Continental Free Trade Area (AFCFTA) is a multilateral agreement enacted by fifty-four members of the African Union (AU) in 2019 to boost trade relations among them. Its core benefit is to facilitate free trade and removal of trade barriers in the region Therefore, this study is set to examine the advantages and impacts of AFCFTA and other multilateral and bilateral agreements in Africa and the world at large.
Keywords: AfCFTA; Bilateralism; International Trade; Multilateralism; Trade agreements; WTO

Termination of Commercial Sale Contracts under the OHADA Uniform Act Relating to General Commercial Law - Ataíde, Rui; Boura, Marta (Centro de Investigação de Direito Privado (CIDP) Research Paper, 2024)
The Uniform Act relating to General Commercial Law of the Organisation for Harmonisation of Business Law in Africa (hereinafter referred to as the OHADA Uniform Act) establishes a commercial sale regime applicable to any trader (natural or legal person), including any commercial companies whose place of business or registered office is located in the territory of a party to the Treaty on the Harmonisation of Business Law in Africa. In this study we propose to analyse the non-performance of commercial sale agreements, focused on its termination regime, by reflecting on the right of termination, the termination by judicial means, its grounds, exemption from liability and the effects of termination. The economic and legal relevance of the commercial sale contract justifies the opportunity to reflect on how legal standardisation process has been achieved overall, particularly with regard to termination regimes. Both OHADA Uniform Act and the Vienna Convention on Contracts for the International Sale of Goods of 1980 (CISG) were conceived as unification mechanisms to circumvent the constraints and legal uncertainty associated with cross-border trade. Therefore, this analysis aims to assess how OHADA rules embody the long process of evolution in French law, as well as the influence of the CISG.
Keywords: CISG; Commercial sale contracts; Comparative law; French law; International Organisations; Legal standardisation; OHADA; Portuguese law; Termination regime; Uniform Act relating to General Commercial Law for Harmonisation of Business Law in Africa

Employee’s Pilferage and Security in Beverage Manufacturing Companies in Lagos State, Nigeria - Attah, Edwin; Abdullahi, Liman; Yusuf, Usman (African Journal of Politics and Administrative Studies, 2024)
The purpose of this paper is to examine the relationship between employee pilferage of pilferage and security in beverage manufacturing companies in Lagos State. The study is anchored on the rational choice theory in order to understand the connection between pilferage and security in beverage manufacturing companies in Lagos State. The researcher adopted a mixed research method involving survey research and historical research designs. The population of this study is 8,595 staff. This comprises all employees of Promasidor Nigeria Ltd, Nigeria Bottling Company (Coca Cola), Cadbury Nigeria Plc, and Guiness Nigeria Plc. The sample size of the study was 400 determined using Rakesh Sample size formula. Data were collected from primary and secondary sources. Primary data were collected using questionnaires, while secondary data were collected from related works on pilferage and security in beverage manufacturing companies. Data collected from questionnaire were analyzed using absolute frequencies and simple percentages, while data from secondary sources were analyzed using relational-content analysis. Among other things, it was found that the higher the level of pilferage, the lower the level of security of employees in beverage manufacturing companies in Lagos State. Among other things, it was recommended that given that there is relationship between pilferage and security in beverage manufacturing companies in Lagos State, beverage manufacturing companies in the state should ensure that stealing is drastically reduced in their various organizations through employment, training and proper motivation of staff who must be full-time staff. This would largely make the employees committed to work and shun pilferage.
Keywords: Pilferage; companies; employee; manufacturing; security

Evaluation of Revenue Effect from Tax Components and Economic Growth in Nigeria - Atuma, Emeka; David, Amarachi; Nwibo, Nneamaka; Nkwagu, Chibuike; Udenta, Blessing; Njim, Sunday; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
This research empirically examined the relationship between tax revenue and economic growth in Nigeria for the period 1994-2021. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates long-run and short-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between tax revenue and economic growth in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally showed that both company income tax and value added tax were statistically significant and positively related to economic growth in Nigeria in both shot-run and long-run periods; whereas personal income tax was statistically insignificant and positively related to economic growth in Nigeria in both short-run and long-run. Based on the findings, the study therefore recommended tax authorities responsible for tax administration should upgrade the tax database to capture all potential tax-payers in order to broaden tax income.
Keywords: Autoregressive Distributed Lag Mode; Economic growth; Nigeria; Tax Revenue

Re-Evaluation of the Effectiveness of Exchange Rate Depreciation on Import Demand in Nigeria - Atuma, Emeka; Ebuka, Bright; Nwibo, Fidelia; Nkwagu, Christain; Nancy, Udenta; Njim, Robert; Ogbonna, Nkemdirim; Uwaeke, Uchechukwu (African Journal of Politics and Administrative Studies, 2024)
The study investigated the impact of exchange rate depreciation on import demand in Nigeria from 1986 to 2021. The data used was sourced from Central Bank of Nigeria. Ex-post facto research design was adopted in the investigation. Multiple regression analysis was employed, in which Auto-Regressive Distributed Lag (ARDL) model as the method of analysis was utilized in the research. The ARDL model evaluates short-run and long-run interactions among the specified variables. The unit root tests conducted using Augmented Dickey-Fuller (ADF) revealed that the time series variables used were stationary at level and the first difference, but none of the variables was stationary at the second difference. The ARDL – Bound test analysis revealed the existence of long-run equilibrium relationship between exchange rate depreciation and import demand in Nigeria within the period of the study. The coefficient of error correction mechanism was statistically significant and also negatively signed. The results equally found that exchange rate depreciation is statistically not significant and negatively impacted on import demand in Nigeria in the short-run. However, in the long-run, exchange rate depreciation is negatively impacted to import demand and statistically significant. Causal relationship does exist between exchange rate depreciation and import demand in Nigeria with causation running from import demand to exchange rate depreciation. On the basis of the findings, the researcher made the following recommendations among others: Government should consider inward looking to strengthen the imports substitution policies that ensure massive production of goods and services.
Keywords: Autoregressive Distributed Lag; Exchange Rate Depreciation; Import Demand; Mode; Nigeria

Nigeria-China Relations and Economic Development - Chiedozie, Nwosu; Aloh, Ngwuta; Ibiam, Okechukwu; Nwankwo, Felix; Ikpolo, Gabriel; Iwuala, Harrison (African Journal of Politics and Administrative Studies, 2024)
This work explored the dynamics of Nigeria-China relations from the political and economic points of view between 1999-2023. The primary concern of this paper is to discern the extent Nigeria-China relations is mutually beneficial and how Nigeria can stand to gain more if the relationship is properly aligned to Nigeria’s national interest. The central argument of this work is that Nigeria stands to gain more from China than from the West bearing in mind the fact that over one hundred years of Africa’s relationship with the West has been largely exploitative and disadvantageous. In this regard, the research employed both primary and secondary sources of data collection. The primary sources relied on first-hand information gathered from the Chinese Embassy as well as key actors within the Nigeria External Affairs Ministry and Key Informant Interviews on experts in Nigeria-China relations. The secondary sources relied on already existing information from libraries, text books, journals and the internet. The theoretical framework employed is the Complex Interdependence Theory. The conclusion drawn from this work is that Nigeria-China relations have not fully developed to the extent of being more beneficial to Nigeria economically and politically. What currently subsists is that China is gaining economically more in terms of trade to Nigeria’s disadvantage. However, politically and socio-culturally, the two countries are mutually benefiting due to various diplomatic protocols and cultural exchanges. The study recommended among others that Nigeria must strive to develop her techno-industrial export-oriented base to ensure more symmetric beneficial relationship with China.
Keywords: Bi-Lateral Relations; China; Development; Economic Development; Nigeria

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Digitalization and Tax Administration in the Gambia - Ogbeta, Oghenekevwe; Ayeni, Oluwadare (African Journal of Politics and Administrative Studies, 2024)
This study extensively explored the potential of digitalization in The Gambia Revenue Authority's tax administration, amidst concerns over the practical application of digital tools and their underutilization, which have hindered the realization of improved revenue mobilization and efficient tax processes in The Gambia. The research, adopting a mixed method design, aimed to understand the intricate relationship between digitalization and tax administration in The Gambia. With specific objectives, including identifying driving factors, examining effects, and evaluating the correlation with GRA's performance, the study adopted quantitative and qualitative analyses. Similarly, the study population is two thousand, one hundred and eighty-eight (2188). Using Krejcie and Morgan (1970) formula, out of 2188 population of the study, three hundred and twenty seven (327) were selected as the sample size. This encompassed individuals drawn from the Ministry of Finance and Economic Affairs, GRA staff, and corporate taxpayers using a stratified and proportionate-to-size sampling approach. Hypotheses analysis revealed a statistically significant and positive effect of digitalization on tax administration, indicating improved efficiency and GRA effectiveness. Also, Spearman's rank-order correlation affirmed a positive relationship between digitalization and tax administration. Furthermore, qualitative insights from stakeholder interviews highlighted drivers such as international financial body stipulations, modernization imperatives, trust-building, accurate record-keeping, and alignment with global standards. Recommendations include training programs for GRA staff, public awareness campaigns, and enhancing user experiences for e-payment systems, among others.
Keywords: Digitalization; Tax Administration; Tax Compliance; Tax Evasion; Taxation

Sustainable development clauses in international contracts through the lens of the Unidroit principles - Pannebakker, Ekaterina (Uniform Law Review, 2024)
Most transactions that leave an imprint on the environment and communities are organized by commercial contracts. However, little is known about the way in which parties reflect sustainable development in contractual clauses. How can parties to international contracts commit to respect sustainable development goals? What are the possible degrees of commitment? Which contractual mechanisms can apply to the monitoring of compliance? How does one establish a link between the failure to meet sustainable development goals and the contractual liability or termination of contract? This article identifies contractual clauses relating to sustainable development and analyses these clauses through the lens of the 2016 International Institute for the Unification of Private Law (Unidroit) Principles of International Commercial Contracts (PICC). Drawing inspiration from open access contracts, the analysis will demonstrate that Article 1.8 of the PICC, precluding inconsistent behaviour, and Articles 5.1.4 and 5.1.5, on the duty of best efforts and the obligation to achieve a specific result, as well as the provisions on liability, can assist contract drafters, judges, and arbitrators in drafting and interpreting such clauses.

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

The Enforcement of Settlement Agreements Under the Ohada Uniform Act on Mediation - Nshom, Kelese George (IUS LAW Journal, 2024)
On 23 November 2017, OHADA member states adopted the Uniform Act on Mediation. The Act lays down rules relating to mediation of disputes which, if successful, ends in a settlement agreement. Settlement agreements that are not freely respected by the parties will have no effect unless they are forcefully executed. Forceful execution is made with the help of a court or notably public who are empowered to insert an executory formula on the agreement after verification of its regularity. These local authorities involved in the enforcement process rely on domestic laws of member states which vary from state to state. This has the effect of tainting the harmonization process intended by the OHADA lawmaker and may be inimical to investors. This raises the problem of the suitability of the Act to dispute settlement as regards enforcement of settlement agreements. With the help of qualitative and comparative analysis, this article brings to limelight the intricacies of the enforcement of settlement agreements underOHADA. It concludes that enforcement of settlement agreements is rendered simple and rapid but faces serious drawbacks which could be alleviated by setting up OHADA mediation institution to oversee the entire mediation process, besides other recommendations.
Keywords: Agreement; Enforcement; Exequatur; MARD; Mediación; Mediation; Mediação; Médiation

The Relevance of IFRS Accounting Information: Evidence from a Pure IFRS Environment - Abu Alia, Muiz; Amarneh, Khairieh; Abdeljawad, Islam (An-Najah University Journal for Research - B (Humanities), 2024)
The International Financial Reporting Standards (IFRS) are supposed to raise the value relevance of accounting information and thus ensure its usefulness for users. Most of the studies on the relevance of IFRS-based accounting information were conducted in countries that had previous accounting standards before the adoption of IFRS. However, the relevance of accounting information is influenced by the accounting traditions inherited from previous practices. This study provides distinctive evidence on the relevance of IFRS accounting information by examining the association between accounting information prepared by Palestinian companies and share prices. Palestine represents a pure IFRS environment since IFRS is its first financial reporting framework. The study estimates the impact of accounting information, including book value of equity per share, earnings per share, and operating cash flow per share, on the market value of the share. Totally, the results show that the accounting numbers prepared by Palestinian companies are relevant. Precisely, earnings per share and book value of equity per share are the important variables in determining the share market value. Notwithstanding, no significant impact of operating cash flow per share has been observed. Moreover, evidence supporting the existence of conformity and predictive relevance is obtained, but the overall predictive relevance is higher. To enhance the relevance of IFRS information, this paper recommends local regulators and policymakers to work on improving the readiness of the Palestinian environment to fully benefit from the adoption of IFRS. On the other hand, the International Accounting Standards Board should adequately consider the circumstances prevailing in underdeveloped countries when issuing its standards. For future research, larger samples from several countries with different prevailing factors should provide insights into the mechanisms of the relationship between book and market values.
Keywords: Conformity Value; IFRS; Predictive Value; The Palestine Exchange; Value Relevance

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

Mobile money and financial inclusion in Africa: Emerging themes, challenges and policy implications - Osabutey, Ellis L. C.; Jackson, Terence (Technological Forecasting and Social Change, 2024)
Mobile money is purported to promote financial inclusion. The growing number of studies have largely focused on transactions and related benefits with limited attention to emerging challenges, policies and initiatives that address the relative needs of different stakeholders. Consequently, little has been done to probe the ‘bottom-of-the-pyramid’ paradigm that underpins these assumptions. There has been inadequate endeavour to examine ways that empirical research could shed more light on these challenges and how to overcome them. To address these gaps, this study reviews the emerging literature on mobile money that explores both benefits and challenges. From our study three main themes emerge that suggest areas where challenges to the efficacy of the mobile money-financial inclusion link still appears not to have been adequately addressed by policymakers: ensuring integrity, privacy and security; addressing resource and infrastructure constraints; and integrating stakeholder benefits. Yet we suggest merely addressing these challenges does not go far enough in safeguarding the needs of local communities, as major stakeholders. Evidence from our study suggests little direct benefit to the poorer sections of local communities, only to the strata above and to elites and external stakeholders. This has implications for development and social change through technology adoption.
Keywords: Africa; Bottom-of-the-pyramid; Financial inclusion; Fintech; Mobile money

Current Issues of the Utilization of Online Dispute Resolution as a Method for International Trade Dispute Settlement - Rohmah, Nuzul Quraniati (Ipso Jure, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring, as well as recognition and execution process of electronic ODR decisions.
Keywords: International Trade; ODR; Online Dispute Resolution; Regulation

Transborder flow of personal data (TDF) in Africa: Stocktaking the ills and gains of a divergently regulated business mechanism - Babalola, Olumide (Computer Law & Security Review, 2024)
Technology-based transactions are inseparable from the routine exchange of data. These exchanges may not pose privacy problems until the movement takes extra-territorial turns thereby facing multiple levels of cross-border regulations. In the 80 s, the frequency of transfer of personal data beyond geographical boundaries in Europe precipitated the regulation of transborder data flows (TDF) beginning with the enactment of the Organization for OECD Guidelines. In Africa, the concept of TDF is more complex than usually viewed by the stakeholders and this is partly because neither the African Union nor other regional bodies have introduced legislation on TDF. Like many concepts in data protection, TDF is bereft of a generally accepted meaning. Regardless of the uncertainty, this paper approaches TDF as the transmission of personal data from one country to another country or international entity for the purpose of processing. The paper discusses some definitions of TDF as understood under African regional and national data protection legislation. In a comparative and normative approach, the paper analyses the barriers to TDF in Africa vis a vis the European experience and then concludes with recommendations for workable TDF within and outside the continent from an African perspective beginning with the harmonization of existing regional framework.
Keywords: Africa; Data Protection; ECOWAS; GDPR; Privacy; Transborder data transfer

The African Continental Free Trade Area (AfCFTA): Taking stock and looking ahead for international business research - Debrah, Yaw A.; Olabode, Oluwaseun E.; Olan, Femi; Nyuur, Richard B. (Journal of International Management, 2024)
The establishment of the African Continental Free Trade Area (AfCFTA) has opened new avenues of research interest in International Business and International Management. However, scholarly work in this fledgling area of research has been disparate and often lacking in the assessment of core international business implications of the emergence of the AfCFTA on member states as well as non-member states. This is because, as yet, no systematic attempt has been made to explore the AfCFTA in the context of IB research, or project future IB research directions. Hence, in this paper, using the PRISMA method we have systematically identified the current published research and scholarly work on the AfCFTA and provided a robust picture of the current state of knowledge and available literature on the AfCFTA while at the same time outlining potential areas for future international business research.
Keywords: AfCFTA; African Continental Free Trade Area; Informal cross-border trade; International business; Regional economic communities (RECs); Systematic literature review

Overview of the role of selected consumer protection bodies in the regulation of prices and access to redress under the Consumer Protection Act 68 of 2008 - Magau, Phemelo; Chitimira, Howard (Acta Universitatis Danubius. Juridica, 2024)
The Consumer Protection Act 68 of 2008 (CPA) seeks to promote the achievement and maintenance of a fair, accessible, efficient, sustainable and responsible market place for consumer products and services in South Africa. Moreover, the CPA seeks to provide an accessible, consistent, harmonised, effective and efficient system of redress for consumers. Notably, the CPA provides that the supplier should not supply or enter into an agreement to supply any goods or services at a price that is unfair, unreasonable, or unjust. This is generally aimed at combating any problems that are suffered by consumers when accessing goods and services in South Africa. Accordingly, various regulatory bodies and related role-players were established to enforce consumer rights and provide redress mechanisms to vulnerable and affected consumers. These consumer protection bodies and related roleplayers include the National Consumer Commission (NCC), the National Consumer Tribunal (NCT), provincial consumer courts, ordinary courts and other alternative dispute resolution agencies. These bodies and role-players are statutorily obliged to resolve consumer disputes in South Africa. However, there are some uncertainty challenges regarding the jurisdiction of ordinary courts and consumer protection regulatory bodies in relation to disputes that relate to the consumers’ right to fair, just and reasonable prices, terms and conditions of goods and services. This article discusses the role of the NCC, the NCT, provincial consumer courts, ordinary courts and other alternative dispute resolution agencies in the regulation of prices for goods, services and access to redress for affected consumers under the CPA. This is done to provide some recommendations that could resolve jurisdictional and regulatory challenges in relation to the price and access to goods and services under the CPA.
Keywords: Consumer Protection Act 68 of 2008 (CPA); Consumer protection; Consumer rights; Prices; Regulatory bodies; Vulnerable consumers

Evaluating bank technical efficiency in SADC region - Abel, Sanderson; Mukarati, Julius; Manenge, Robson; Le Roux, Pierre (Heliyon, 2024)
Efficiency is generally defined as the capacity to deliver desirable results with little effort or input. A bank cannot afford to allocate limited resources at random in a competitive market. Only once the efficiency factors have been identified can resources be allocated in a conscious and effective manner. The study investigates the determinants of technical efficiency of banks in the SADC region. The study is significant in the SADC region as the block is trying to create a robust and stable banking system. This is driven by the desire to stay away from the current global financial system volatility and the region is working to develop an integrated banking system. The results show that the banks are relatively inefficient with the level of inefficiency around 40 percent. The efficiency of the banks is determined by the level of capitalisation, size of the bank, research costs and automation of the banks. The results of the study imply that that there is great scope for the banks in the SADC region to increase their efficiency. Improved efficiency will ensure banks provide services at a lower cost to clients. The study recommends adequately capitalizing banks, increasing the asset base of the banks, investing in research and the automation of the banking systems.
Keywords: Banks; Capitalisation; Data envelopment analysis; Technical efficiency; Tobit

Influence of remuneration on organizational performance in co-operative banks in Kiambu, Kenya - Brian, Kasale; Abuga, Isaac Mokono (African Journal of Social Issues, 2024)
This study investigates the influence of remuneration on organizational performance in cooperative banks in Kiambu County, Kenya. Employing a mixed-methods approach, the research explores how compensation packages, salary reviews, and employee recognition impact performance. The study utilizes a descriptive research design with structured questionnaires to gather data from 94 participants. Findings indicate a significant correlation between competitive remuneration and enhanced organizational performance. The majority ofemployees are satisfied with salary increments and recognize the positive effects of frequent salary reviews on their motivation and job satisfaction. The study also highlights the importance of recognition and praise in boosting employee morale and engagement, contributing to overall organizational success. This research is grounded in Equity Theory, which posits that fair treatment in compensation leads to higher motivation and productivity. The conclusions drawn suggest that cooperative banks should implement equitable and competitive remuneration strategies, along with regular salary reviews and robust recognition programs, to enhance performance. The study provides valuable insights for policymakers andbank managers aiming to improve organizational effectiveness through strategic human resource practices.
Keywords: Co-operative Banks; Employee Motivation; Equity Theory; Organizational Performance; Remuneration

Corporate Income Tax (CIT) and Capital - Agossadou, Stanislas Théodule Médard Dèwanou Comlan (International Journal of Accounting, Finance, Auditing, Management and Economics, 2024)
This research consists of verifying whether CIT has an effect on capital given the financing risk incurred. A review of several capital theories has shown that CIT is one of the main determinants of a firm's capital structure. The inclusion of CIT in capital structure models continues to divide the world of corporate finance. Debt interest deduction in computing CIT reinforces the controversy over the question of the capital structure that optimizes the tax savings provided by this deduction. The consequence is the existence of two opposing groups on the optimum capital structure: on the one hand, the group of those who believe that there is one and only one optimal capital structure, and on the other, the group of those who reject out of hand any possibility of an optimal capital structure. The sample starts with a case study of two hypothetical identical firms, one indebted and the other non-indebted, with the same profitable investment project over a period of time, and ends with 101 pairs of identical firms belonging to different classes of financing risk. The hypothesis of non-gratuity of cost and income is used, and capital markets are assumed to be pure and perfect. The results confirm that CIT has no effect on the structure, value, cost and return of capital for a given financing risk, and reveal the existence of a third source of financing called "public capital", whose cost is the corporate capital tax rate (CCTR). There is no longer any question of thinking about the optimum capital structure, which is a pure financial illusion. This paper is one of the first to show that CIT does not affect capital, and to propose a model that explains capital structure behavior in the presence of CIT. Paper type: Empirical Research Stanislas Théodule Médard Dèwanou Comlan AGOSSADOU, (Researcher) Laboratory for Research on Performance and Development of Organizations (LARPEDO) Faculty of Economics and Management (FASEG) University of Abomey-Calavi (UAC) - Benin,
Keywords: Capital structure; Financial integration of corporate tax; Firm value; Return on investment; Weighted average cost of capital (WACC)

Islamic Law Aspect on in Valuation and Execution Intellectual Property (IP) Asset as Bank Collateral in Creative Economy - Margono, Suyud (International Journal of Social Science Research and Review, 2024)
One of the issues faced by many creative economy actors in this relatively newly established industry is the lack of supporting infrastructure, such as the limited access to financing and one of the prominent issues is banks’ reluctance to accept intellectual property (“IP”) as collateral to secure loans including problems concerning valuation of IP Asset as Collateral which has implications several regulation concerning Intellectual Property. In the spirit of furthering the creative economy, the Government has recently issued Government Regulation Number 24 of 2022 on Intellectual Property-Based Creative Economy Financing. This matters includes in relation with IP assets that are exposed and exploited their product (goods or services) on the basis of exclusivity in financing and loan contractual scheme as collateral. This article normative legal research in which intended for studies that are literary and practical works which is Intellectual Property (IR) system in relation with valuation and execution as bank collateral either Indonesia prevailing law and Islamic (Syariah) Law. The result of this research that IP owners often deal with complex contractual relationships that involve different forms of cooperation in research, production or commercialization. most important aspect concerning capacity and competency with comprehensive knowledge deal with IP Asset as Collateral before Banks, and others financial institution, execution of guarantees as applied to Islamic banking has adopted many syariah law, in the practice, there are still many problems the implementation of guarantees as applied to Islamic banking has adopted many Islamic laws. However, in the practice, there are still many problems that arise from the Islamic law scope the concept of justice and the philosophy of maslahah.
Keywords: Creative Economy Valuation and Execution Asse; Intellectual Property (IP) Collateral; Islamic (Syariah) Law

How can the rule of law under the WTO framework ensure sustainable fishery governance through fishery subsidies? A study from the perspective of special and differential treatment - Bai, Jiayu; Wu, Yuting (Heliyon, 2024)
Background Considering the declining situation of sustainability in global marine fisheries, World Trade Organization (WTO) members successfully concluded the Agreement on Fisheries Subsidies(AFS) after 21 years of negotiations in 2022. As an the integral part of these negotiations, special and differential treatment (SDT) provisions provide developing countries with special rights and developed countries with the possibility to treat developing countries more favorably than other WTO members. Objective This study analyzed the role of SDT for fisheries subsidies in ensuring sustainable fishery governance by the rule of law, as well as the reflection of SDT under the AFS, to explore whether SDT can support sustainable fishery governance under the WTO framework. Methods This study is primarily based on official data and critical legal studies and used normative analysis and historical analysis to expose the essence of the SDT issue in the AFS as a political game in the legal form. Results The practical challenges in the implementation of SDT may affect the compliance willingness of member states. To overcome the obstacles, such as ambiguity and inefficiency, that impede the legalization process of sustainable global marine fishery governance, it is necessary to emphasize the value of SDT for the common interests of the WTO members in marine fisheries legislation. This will benefit the developing countries, especially the small island developing states, in the short term; and the common interests of developed and developing countries in the long term. Policy implications SDT facilitated the consensus between the developing and developed countries on issues such as illegal, unreported, and unregulated fishing subsidies and overfishing subsidies. However, current SDT practices have deviated from the original intention of the fairness and democratic approach of global marine fisheries governance, which should take into consideration the specific situation of developing countries.
Keywords: Agreement on fisheries subsidies; Overfishing; Rule of law; Special and differential treatment; Sustainable fishery governance; World Trade Organization

Articulation between Soft Law and Hard Law in the Award of Public-Private Partnership Contracts through Unsolicited Bids in Burundi: Towards Harmonization with International Practice - Amani, Jean Pierre (Open Journal of Social Sciences, 2024)
The awarding of public-private partnership (PPP) contracts through unsolicited bids is characterized by flexible domestic law, with the involvement of public and private players aiming to achieve the general interest objective of public infrastructure development and, by extension, national development. These players are helping to build the normative framework for PPP project activities by spontaneous offer, given their increasingly widespread use on the bangs of positive law, while their standards are classically deprived of the binding force attached to hard law. Marked by its normative guarantee, the flexible law of unsolicited bids is situated at the threshold of the mandatory, and is essential to PPP law. It produces legal effects by linking up with the hard law of PPP contracts, which is the law of the parties. This link between soft law and hard law has a major legal impact on the transformation of the law and legal certainty, for the benefit of investment confidence, especially international investment confidence. Faced with the limitations of positive law on the award of PPP contracts in unsolicited bids, and the difficulties of interpreting soft law and hard law standards, there is a need for harmonization with international practice. To this end, the instruments of the United Nations Commission on International Trade Law (UNCITRAL) on PPPs are being used to link up with Burundian hard law through a transposition mechanism. It is therefore possible that our positive approach to PPP contracting could be improved, highlighting the principle of competition and the exception of non-competition, while taking into account the win-win principle, risk sharing and performance. Finally, the article considers the adjustments to the hard law that would be necessary if Burundi were to decide to revisit the legal framework to make it more attractive to investment, and thus ensure the completion and financing of PPP contracts by spontaneous bidding.
Number: 1
Keywords: Articulation of Law; Competition Principles; Hard Law; Harmonization Principles; Legal Certainty; Mutation of Law; Soft law; Spontaneous Offer

A bibliometric review of IFRS adoption and compliance research in Africa - Effah, Nana Adwoa Anokye (Journal of Business and Socio-economic Development, 2024)
Purpose This article aims to identify and review existing studies on the adoption and compliance of Internat ional Financial Reporting Standards (IFRS) in Africa. Design/methodology/approach The methodology involves a sole focus on studies conducted with an African sample, using a bibliometric method and data from the Web of Science (WoS) database. Visualizations from VOSViewer and Biblioshiny software are employed to identify the dominant authors, journals and countries contributing to research in the region. Findings The findings reveal existing collaborations among authors in the field. However, the study emphasizes the need for additional research to enhance the intellectual structure of the research domain, as the majority of related documents are concentrated within twenty articles with at least one citation. Practical implications The practical implications underscore the importance of collaboration in practice, emphasizing the need for cooperation among corporations, experts and regulatory agencies involved in IFRS adoption and compliance in Africa. By fostering collaborative efforts and knowledge-sharing among corporations, experts and regulatory agencies, practitioners can enhance their understanding, streamline implementation processes and improve compliance methods. Originality/value This review is one of the few to explicitly conduct a bibliometric review of IFRS adoption and compliance studies in Africa, providing a foundation for future research to determine the current direction of IFRS studies in this region.
Keywords: Africa; IFRS adoption; IFRS compliance; Web of science database

Internationalisation patterns of African sharing economy companies: The role of gateway markets - Ochieng, Irene Achieng; Thornton, Heidi Coral; Owusu, Richard Afriyie (Journal of Business Research, 2024)
Sharing economy companies (sharecoms) have been internationalising rapidly, including entering African markets. Little research has been conducted on the strategies and behaviours of African sharecoms. Questions have been raised as to whether existing theories adequately explain the internationalisation of African firms. Thus, we analyse the internationalisation patterns of six African sharecoms, focusing on time, speed, and scope. The findings indicate that firms apply unique combinations of various internationalisation models. A novel pattern of internationalisation where the firms use “foreign gateway markets” as strategic “launchpads” before rapidly internationalising was also uncovered. Locational advantages, strategic networks, and relative technological advancement characterise the foreign gateway markets. We also propose the concept of “complex regional context” to define the context of emerging regions with many neighbouring countries with the potential for high levels of internationalisation but low levels of international business due to the lack of common enabling frameworks and institutions.
Keywords: Emerging African markets; Foreign gateway markets; Internationalisation; Patterns; Sharing economy

Tax Behavior and Financing Behavior of Corporate Managers: Case of Banks and Decentralized Financial Systems (DFSs) in Benin - Agossadou, Stanislas T. Médard D. C. (Journal of Economics, Finance and Management, 2024)
This paper aims to analyzing the influence of tax behavior on financing (financial leverage) behavior of corporate managers. The paper applies the generalized method of moments (GMM) to dynamic panel data. The sample used covers 21 firms, i.e. 11 banks for the period from 2011 to 2020 and 10 DFSs for the period from 2016 to 2021. It turns out that financial leverage behavior is influenced more positively by corporate income tax (CIT), then by dividends (DIVIDEND); and negatively by interest on debt (INTEREST), by cash flow (CASH_FLOW) and by past financial leverage (LEVERAGE(‑1)). This paper is one of the first to extend the literature by identifying the main determinants of financing behavior, notably the positive effect of corporate income tax (CIT).
Keywords: Corporate income tax behavior; Corporate income tax savings; Financial objectives; Leverage behavior; Tax objectives

Evaluating the International Arbitration of Oil and Gas Investment Dispute Settlement in Nigeria - Bisina, Lucky N. (African Journal of International Energy & Environmental Law, 2024)
This paper examined international arbitration as a tool for resolving investment disputes in Nigeria’s oil and gas sector, a critical industry that contributes significantly to Nigeria’s Gross Domestic Product (GDP), foreign exchange earnings and government revenues. This sector is marked by high-risk investments and complexity and often faces disputes arising from regulatory changes, fluctuating global prices, environmental concerns and contractual breaches. Arbitration, particularly in cross-border investments, provides a neutral, efficient and flexible mechanism for resolving such disputes. Using a doctrinal research methodology, the study analysed statutes, case law, international treaties, and academic sources. Findings revealed that while arbitration offers benefits such as neutrality and enforceability, there are still some challenges that must be addressed as a matter of urgency. Issues include resistance to enforcement of arbitral awards by Nigerian courts on grounds of national interest, high arbitration costs and biases favouring foreign investors. Nigeria’s legal framework, including the Arbitration and Mediation Act 2023 and the Petroleum Industry Act 2021, supports arbitration but lacks procedural clarity, leading to delays and inefficiencies. The paper concluded that legal reforms are essential to strengthen arbitration processes, enhance enforcement mechanisms and align Nigeria’s framework with international standards. Such reforms would foster investment stability and improve Nigeria’s attractiveness as an investment destination by reducing legal uncertainties. The paper recommended legislative and judicial improvements in order to achieve these goals.
Keywords: Dispute Settlement; International Arbitration; Investment Dispute; Oil and Gas Investment

Arbitration in the era of e-commerce: A comprehensive overview - Buhuri, Kristi (World Journal of Advanced Research and Reviews, 2024)
Technology is continuously evolving and has changed human interaction. It is consequently changing the ways disputes are solved. International dispute resolution procedures, and international arbitration, more specifically, are considerably influenced by the rapid expansion of innovative technologies. Years after the dot-com boom, Online Dispute Resolution (ODR) emerged and evolved considerably. Due to the digitalization of ODR methods, remote arbitration (or e-arbitration) is expanding. Arbitration is of particular interest due to its formal and binding nature, from a theoretical perspective. E-arbitration, as other ODR methods have attractive features as well as drawbacks, which are addressed in this document. The purpose of this paper is three-fold: providing an overview of e-arbitration and the different considerations of this method, presenting the e-arbitration models of the European Union (EU), the United States (US), and the People’s Republic of China (PRC) and suggesting recommendations to improve international e-commerce arbitration, notably through a revision of the UNCITRAL Model Law on International Commercial Arbitration (UNCITRAL Model Law).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Digitalization; Innovative Technologies; ODR; Online Dispute resolution; e-Arbitration

(R)evolution of insolvency law under the impact of artificial intelligence (AI): transformative technologies - challenges and perspectives - Didea, Ionel; Ilie, Diana Maria (Legal and administrative studies, 2024)
Keywords: AI; Artificial Intelligence; Bankruptcy; Cross-border Insolvency; Insolvency; Inteligência artificial; Intelligence Artificielle; Technology; UNCITRAL Model Law on Cross-Border Insolvency (1997)

ISDS 2.0: Time for a Doctrine of Precedent? - Jarrett, Martin (Journal of international economic law, 2024)

A comprehensive outline towards conciliation in the contemporary world of E-commerce - N, Vinod; Gupta, Poonam (World Journal of Advanced Research and Reviews, 2024)
Since the start of the millennial era, technical advancements have led to exponential growth in electronic commerce, or e-commerce. According to the United Nations Conference on Trade and Development (UNCTAD), e-commerce sales reached about US$25 trillion globally in 2021 [1] and are expected to grow at a compound annual growth rate of 9% through 2027, which is twice as fast as the 4% annual growth rate predicted for traditional in-person retail [2]. Online dispute resolution (ODR) techniques that aim to settle disagreements and lower the likelihood of expensive lawsuits are becoming more and more necessary as both individuals and corporations use online shopping platforms. Due of its legally binding nature, arbitration is the most formal method, as was briefly discussed [3]. Online arbitration is carried out using electronic methods, like email and digital tools designed to make the duties of arbitrators and parties to a dispute easier. It adheres to the same rules and processes as traditional arbitration. On the plus side of e-arbitration, advancements in technology allow for time and cost savings without sacrificing the ease of remote filing. The conclusion of e-arbitration agreements raises several negative issues, including privacy and data protection issues for the consumer signing the agreements and power imbalances between corporate entities and the consumer. The degree to which artificial intelligence (AI) is effectively and sufficiently analysing a dispute between parties is up for debate because it's unclear how new this adjudication process is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Artificial Intelligence; Conciliation; E-Commerce; Inteligência artificial; Intelligence Artificielle; ODR; OECD

Summary survey on publishing contract in the OAPI space - Ngombé, Laurier Yvon (The Journal of World Intellectual Property, 2024)
The OAPI member states constitute a space for theharmonization of copyright in Africa. This harmonizationis yet to be completed, as attested by the conventionalrules relating to the publishing contract. In addition,investigating about the publishing contract in the OAPIspace requires an examination of both the text of theBangui Agreement and that of the national laws of the 17member states. Some differences must be pointed outkeeping in mind the question of possible conflict of laws.
Published by John Wiley & Sons Ltd.
Keywords: ARIPO; Conflict of laws; Contract; Copyright

Concurrent Investor-State Claims Before Domestic Courts and Investment Treaty Arbitration Tribunals: Philip Morris, Vattenfall and Beyond - Nottage, Luke; Stendel, Robert (Virginia journal of international law, 2024)
Keywords: Arbitrage; Arbitragem; Arbitration

Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
https://rgu-repository.worktribe.com/output/2085489/blockchain-and-smart-contracts-a-game-changer-in-mediation https://rgu-repository.worktribe.com/output/2085489
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Business climate and global value chains: Insights from Africa - Ajide, Folorunsho M. (Transnational Corporations Review, 2023)
This paper provides insights on how business climate affect global value chains (GVC) participation in the panel of African nations. The study explores country-level data spanning over a period of 2006–2018. Using the novel method of moments (MM)-Quantile regression, system generalized methods of moments (SYSGMM) and Panel spatial consistent correlation (PSCC) techniques, the study finds that all aspects of business environment have significant impacts on GVC participation in Africa. In specific, information and communication facilities, getting electricity, getting credit, trading across border, enforcing contract, protecting investors and business start-up registration have positive and significant impact on GVC. We also discover that tariff reduces GVC participation while strong political institutions enhance participation. The study concludes that business environment factors are fundamental to ensure high level of GVC participation. Political institutional framework needs to be strengthened to further encourage GVC participation in Africa.
Keywords: Africa; Business environment; Climate; GMM; Global value chains

Terms of trade, governance and household income in selected African countries - Edeme, Richardson Kojo; Mumuni, Sulemana (Sustainable Futures, 2023)
As African countries grapple with the challenges of terms of trade occasioned by economic uncertainty, there is a need for a study on the effect of terms of trade on household income in Africa. Also, as African countries continue to commit to the role of institutional quality in improving terms of trade, this study further reinforces the role of governance on household income in Africa. The study employs the Two-stage Least Squares (2SLS) fixed effects estimation technique based on data spanning 2002–2021 for 36 selected African countries. This study provides more robust evidence by employing household final consumption expenditure as a measure of household income. Findings suggest that improvement in the terms of trade stimulates household income. Similarly, the results indicate that governance plays a critical role in enhancing household income status in Africa. Specifically, government effectiveness, control of corruption, regulatory quality, rule of law, and political stability positively and statistically significantly influence household income levels in Africa. Furthermore, GDP per capita growth positively impacts household income, albeit the effect is statistically insignificant. On the contrary, higher inflation rates, exchange rate volatility, and foreign direct investment (net inflows) have a limiting effect on household income, although, the effect of currency depreciation is generally not statistically significant. Sequel to these findings, the study calls for strong institutional quality and export promotion strategies in Africa.
Keywords: 2SLS; Governance; Household income; Terms of trade

Nigeria’s Contribution to Africa’s Regional Integration: Assessment of its recent Performance - Garba, Dimas (African Journal of Politics and Administrative Studies, 2023)
This paper investigates the recent performance of Nigeria towards Africa’s regional integration as a major power in Africa. The main objective of the research is to determine the extent of Nigeria’s commitment to the realization of the African Union’s vision of becoming a fully integrated, prosperous and peaceful Africa; and a dynamic force at the global level. Since her independence in 1960, Nigeria has been widely acknowledged as a leading power in Africa (The Giant of Africa) by several studies because of its preponderant political, economic and militarily power; influence; and benevolent contributions regarding to the liberation and progress of Africa. However, there are hardly substantive assessments of its recent performance towards Africa’s integration. The study adopts the Hegemonic Stability Theory; and descriptive analysis method to analyze data obtained from secondary sources. Analysis of the 2016 and 2019 Regional Integration Index (ARII) reports covering the period from 2010-2019 reveals that Nigeria has performed poorly towards the continent’s integration among its peers, both at the continental and sub-regional levels. The paper concludes that Nigeria’s poor performance would significantly slow the acceleration of Africa’s integration; and the country risks losing its leadership position in Africa to its rivals, especially South Africa. It recommends that the Nigerian government should take deliberate steps in formulating and implementing policies that would improve its performance across the five dimensions of the regional integration; and it should strengthen its commitment to consolidate its leadership position in Africa, and motivate smaller countries to contribute their best.

The Challenges of Regional Integration and Effective Implementation of African Continental Free Trade Area (AfCFTA) Policy in Africa - Garba, Dimas; Wancelous, Avong (African Journal of Politics and Administrative Studies, 2023)
The paper is an investigation of the challenges of regional integration in Africa and their effects on the implementation of the African Continental Free Trade Area (AfCFTA) policy. The major objective of the paper is to proffer solutions to the challenges for the effective actualization of the policy. The assumptions of the neo-liberal theory were used to support the AfCFTA initiative to promote economic growth and development in Africa. The data used to advance the argument were obtained from secondary sources of data collection. The study finds that language barrier, multiple currencies, porosity of borders, foreign interference, political instability and insecurity, poor human development, over-lapping of membership of sub-regional organizations, poor state of infrastructure, and state-centric nature of integration initiatives are some of the core challenges hindering the effective execution of the AfCFTA policy. The study recommends that the African Union (AU) should intensify effort at realizing a single currency policy for Africa; design comprehensive regional security architecture to include high technological surveillance, joint air and ground border patrol among member states of Regional Economic Communities (RECs) to address trans-border crimes and insecurity. There should also be institutionalization of counterpart funding among AU member-states for infrastructural development; and encouragement of private and civil society participation in the integration initiative, among others. In concludes that if the challenges identified are not effectively addressed, it will be very difficult for the AU to successfully realize the objectives of the AfCFTA policy.
Keywords: AfCFTA Policy; Africa; Challenges; Implementation; Regional integration

Corruption and its Impact on Socio-Economic Development in Selected Countries of Africa - Muhammad, Ibrahim; Wasiu, Sanusi; Ahmad, Muddassir (African Journal of Politics and Administrative Studies, 2023)
Africa is indeed a continent blessed with an abundance of natural resources, ranging from valuable minerals like gold, diamonds, copper, and oil. These resources hold immense potential for fostering economic growth and development across the continent. However, Africa continues to grapple with extreme poverty and underdevelopment, with corruption being identified as a major impediment to progress. This paper focuses on the pervasive issue of corruption in Africa, with Nigeria, Uganda, and Zimbabwe as case studies. The research employs a descriptive and analytical method of historical research, grounded in the Prebendal Theory as its theoretical framework. The findings of this study reveal the staggering impact of corruption on Africa's development, with annual losses of approximately $60 to $100 billion due to illicit financial flows. These flows divert resources away from political and socio-economic advancement, exacerbating widespread impoverishment. In conclusion, the paper underscores the corrosive effect of corruption on Africa's development and offers several recommendations to address this issue. These include promoting merit-based leadership selection, enforcing stronger legal actions against corruption, empowering anti-corruption agencies, engaging citizens and civil society in the fight against corruption, and strengthening the rule of law and judicial independence. These recommendations aim to pave the way for a more transparent and accountable future in Africa.
Keywords: Corruption; Government; Infrastructure Africa; Socio-Economic Development

The impacts of IFRS 16 on airlines - Ribeiro, José; Ribeiro, Francisco; Ribeiro, Fernando (Accounting and Management Review | Revista de Contabilidade e Gestão, 2023)
This study addresses the effects of the adoption of IFRS 16 on the passenger air transport sector. With practical effects for financial years beginning on or after 1 January 2019, IFRS 16 established the standardisation of a single accounting modelfor all leases, whether operating or financial. With this new adoption, IFRS 16 aims to increase the transparency and quality of the information that is presented in the financial statements for the most diverse stakeholders. This study aimed to assess the effects of adopting this new international standard in a specific sector and to identify whether the changes in some of the financial indicators are felt in the same way by all companies, this being the main focus of this study. Based on a sample of 12 airlines from various countries in Europe and South America, the financial indicators were interpreted by analysing the reports and accounts before and after the application of IFRS 16. The main conclusions obtained are: i) the adoption of IFRS 16 led to an increase in assets, liabilities and EBITDA, however in different proportions for each of these items; ii) companies with negative equity and, therefore, with greater risks of bankruptcy or greater information asymmetry, tend to resort more to leasing as a way of financing their assets; iii) the financial autonomy and solvency ratios showed significant variations for companies that resort more to operating leasing.
Keywords: Airline industry; Finance leases; IFRS 16; Information asymmetry.

An In-Depth Analysis of Choice of Law Rules in Consumer Contracts: A Focus on the African Continental Free Trade Area - Fiattor, Ethel (Journal of Law, Society and Development, 2023)
Choice of law is a perplexing concept due to the importance of party autonomy, the diversity of connecting factors, and the variety of different contractual issues. The problem of choosing a governing law is complicated in consumer contracts by industrialised mechanisms depriving consumers of negotiation rights. The core mandate of the African Continental Free Trade Area (AfCFTA) is to establish a single market for goods and services associated with the free movement of legal persons for economic integration. This objective requires a harmonised consumer protection policy to resolve the diverse consumer protection regimes applicable in state parties within AfCFTA member states. This policy should provide suitable consumer protection mechanisms generally and in the context of choice of law specifically. Implementing a draft competition policy bestows a legitimate mandate on the AfCFTA to negotiate a continental framework on consumer protection as both fields of law complement each other to safeguard consumer rights in cross-border trade. This article argues the dynamics of providing adequate choice of law rules on consumer contracts to inform suitable mechanisms on consumer interest within the AfCFTA. The article discusses the abuse of choice of law clauses in consumer contracts, affecting consumers’ rights in cross-border contracts within the AfCFTA. It suggests a harmonised consumer protection policy to regulate and mitigate these clauses. The article also examines trends in Global North jurisdictions like the European Union to inform a context-specific institutional framework for the AfCFTA’s choice of law rules.
Keywords: AfCFTA; Applicable law; Choice of law; Consumer protection; Economic integration; Harmonisation; International law; ZLECAf

South African controlled foreign companies' rules and the digital economy - Sengwane, Khodani (Potchefstroom Electronic Law Journal, 2023)
South Africa's controlled foreign company ("CFC") rules were enacted more than two decades ago before most of today's business models existed. These are anti-avoidance rules that ensure the South African taxation of profits diverted offshore by South African residents. In terms of the CFC rules, the profits of a non-resident company may also be subject to tax in South Africa at the hands of its South African resident shareholder if such non-resident company is considered to be a CFC. Advances in technology developments and the use of information communication and technology ("ICT") have given rise to what is referred to as the digital economy. The term refers to economic activities hinged on the use of ICT and the internet. Digitalisation has made it possible for a business to carry on economic activity without the need for a multitude of offices, staff, equipment, and other resources. As a result, new business models like Uber and Shien have emerged. This paper argues that the current South African CFC rules have not kept pace with these new business models and do not effectively regulate the new business models and the digital economy. This paper recommends that the CFC rules be updated to address the digital economy and new business models by amending the rules, incorporating the provisions of Electronic Communications and Transactions Act 25 of 2002 into the rules, using country-by-country reporting, and even considering implementing a regime alternative to CFC rules.
Keywords: Anti-avoidance; Controlled foreign company; Deemed source; Digital Economy; Digitalisation; Direct tax; Foreign business establishment exemption

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Tacit Choice of Law in International Commercial Contracts. An Analysis of Future Instruments of Developmental Organisations - Bouwers, Garth J. (Potchefstroom Electronic Law Journal, 2023)
This article examines the various regional and supranational organisations of emerging countries that could benefit from a codification of private international law rules. They include the Organisation for the Harmonisation of Business Law in Africa (OHADA), the African Union (AU) and the Association of Southeast Asian Nations (ASEAN). In addition, the article analyses the envisaged instruments that may be especially relevant in the context of the abovementioned organisations. These include the Preliminary Draft Uniform Act on the Law of Obligations in the OHADA Region, the proposed African Principles on the Law Applicable to International Commercial Contracts and the Asian Principles of Private International Law. More specifically, the article focusses on the provisions regarding the determination of the law applicable, particularly those rules relating to a tacit choice of law in international commercial contracts.
Keywords: ASEAN; African Union; Asian Principles of Private International Law; Choice of Law; International Commercial Law; OHADA; Private International Law; Tacit choice of law

Infringement of Brand Rights on Different Products Is an Illegal ACT - Fahdia, Khamada Wafi; Roisah, Kholis (International Journal of Social Science Research and Review, 2023)
The study aims to find out how the provisions of the law are in violation of brand rights to nongender products and their protective forms, as well as how legal efforts should be made in violation of their laws. Legal protection for legitimate brands' owners is regulated within brand laws intended to give their owners exclusive rights. Legal measures that rights holders can make on broken brands can be made either by civil law or criminal law. Indonesia's brand registration system is a constituent system, and it is recommended that all efforts be quick to register a trademark or service brand for the creditor of intellectual property rights. The holding of a brand would be wise to appeal to the court immediately if there is any indication that a brand offense is committed by another and the cost is not greater.
Keywords: Brands Infringement; Products of No Kind; Unlawful Conduct

Vulnerability Theory as a Paradigm Shift in International Investment Law: Reimagining the Role of the State - Küçüksu, Aysel; Ünüvar, Günes (Business and Human Rights Journal, 2023)
This article argues for a fundamental raison d'être reconceptualization of international investment law (IIL) through Martha Fineman's 'vulnerability theory'. The theory helps identify the structural sources of IIL's shortcomings, whilst philosophically challenging the one-sided view that foreign investors are entitled to protections, but are free from obligations vis-à-vis the communities affected by their undertakings. Emphasizing the productive power of the state to take positive action that acknowledges ordinary citizens' embeddedness within, and dependence upon, surrounding structures, the vulnerability theory challenges the hegemonic perception of the state as a source of danger - a view which has hitherto undermined both the potency and the enforceability of investor obligations. Used as a heuristic device in studying both IIL's existing structures and the potential avenues for reimagining it, Fineman's theory not only shines a novel light on the foundational premises of IIL, but also grants theoretical traction to existing ideas about improving the system.

Corporate Criminal Sanctions for Human Rights Abuses: A Legal Appraisal of This Liability Under Cameroonian Business Law - Nyiloh Bavoh, Frankline (International Multilingual Journal of Science and Technology, 2023)
Criminal responsibility for corporate related human rights violations is a challenging and complex question in today’s world, this is partly because of the individual or personal character of criminal responsibility. It is held as a general rule that only human beings can commit offences. The primary objective of this research is to critically examine the human rights aspects of corporate criminal responsibility of companies in Cameroon. The conducts of business by various corporations in Cameroon are recognized as an impetus to economic, social, cultural and political advancement. With the rise in corporate crimes in the world today, the question has been whether a corporate body can be held liable for corporate crimes or not. The paper answers in the affirmative that a corporate body can be subject to criminal prosecution and liability for crimes occurring within the corporation especially in the domain of human rights. Considering that a corporate body cannot be imprisoned, or punished like an individual, there are ways to punish a corporation. A corporate body may be fined, ban, closed placed under judicial supervision for a specified period of time. With this in mind, the paper analyses the concept of corporate criminal liability with specific regards to corporate capacity, the basis upon which such liability attaches to a corporation and sanctions with the aim of illustrating the weaknesses of the different aspects trundled-out above.
Keywords: Cameroun; Cooperate; Criminal; Human rights; Sanctions

Congolese Land Rights Put to the Test by the Private Real Estate Investment Revolution - Milenge, Christian Mwenyemali (Open Journal of Social Sciences, 2023)
Private investors’ land rights vary from country to country, depending on the legal system in place. The degree of openness of land laws determines the degree to which both domestic and foreign investors are attracted, as the latter aims to invest in countries with legal systems offering the most secure and sustainable interests. How can Congolese land laws be made more attractive to private investors in the real estate sector? Using exegetical and comparative methods, we will test our hypothesis that reform to increase the rights of private national and foreign investors to access land would be an asset. By comparing Congolese land law with other legal systems, and with current social and economic realities, we have concluded that accommodating land rights is a prerequisite for increasing both domestic and foreign private investment in real estate and an essential step towards boosting and modernizing real estate investment in the DRC.
Number: 9
Keywords: Agricultural Investment; Congolese Land Ownership Law; Investments; Land Rights; Private Investment; Real Estate Law

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
https://rgu-repository.worktribe.com/output/2255845/transparency-in-international-arbitration-balancing-the-need-for-openness-with-the-need-for-confidentiality
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

Structural Change, Productivity Growth and Labour Market Turbulence in Sub-Saharan Africa - Mensah, Emmanuel; Owusu, Solomon; Foster-McGregor, Neil; Szirmai, Adam (Journal of African Economies, 2023)
This paper presents a shift-share decomposition of the role of structural change in driving labour productivity in sub-Saharan Africa (SSA). The paper further examines the effect that the observed structural change has had upon the dynamics of labour markets in SSA. The analysis is based on a newly constructed dataset, the Extended Africa Sector Database. This database updates and extends the Africa Sector Database of the Groningen Growth and Development Centre. It includes eighteen countries covering the period 1960–2015. Overall, the database shows that productivity growth has been slow, with large and persistent sectoral productivity gaps present. The extent of structural change has been higher than that observed in previous studies, however. But while the share of employment and value added in agriculture has declined, resources have been pulled into certain service sectors that have relatively low productivity, thus limiting aggregate productivity improvements. The general direction of structural change has not been towards the most productive sectors. Results of the labour market analysis complement this analysis, providing suggestive evidence of a role for labour market institutional arrangements in many SSA countries in affecting these outcomes.

Selection and Appointment in International Adjudication: Insights from Political Science - Larsson, Olof; Squatrito, Theresa; Stiansen, Øyvind; St John, Taylor (Journal of International Dispute Settlement, 2023)
This article summarizes insights from political science and empirical legal scholarship concerning selection and appointment of adjudicators to permanent international courts (ICs). This scholarship suggests that designers of ICs face challenging trade-offs in balancing judicial independence and accountability, as well as in promoting descriptive representation and necessary qualifications on the bench. The article considers different institutional design features related to appointment procedures: representation, reappointment, screening procedures and procedures for removing judges. Representation is discussed in a series of sections considering full or selective representation, voting rules and geographic and gender quotas and aspirational targets. Throughout, we draw on data on 24 ICs to illustrate the different appointment procedures and institutional features.

Corporate Social Responsibility and Green Marketing Adoption in Nigeria: A Panoramic View - Nkwede, Maria-Friday; Ogbulie, Angela (African Journal of Politics and Administrative Studies, 2023)
Corporate social responsibility (CSR) and green marketing adoption is a twin trend that is fast becoming a global tendency amongst world economies, irrespective of socio-economic outlook. This paper pedagogically links the two concepts in the Nigeria business climes and explores, through a panoramic view the rate of adoption of CSR and green marketing in Nigeria. This study adopted an exploratory research design vis-à-vis a qualitative research approach. Based on the findings, this paper posits that corporate social responsibility in the Nigerian context is highly “localized” to reflect realities in the Nigerian socio-cultural space. However, green marketing adoption is near impossible for the average Nigerian organization; this is due in part to the enormous funds necessary for implementation of green marketing strategies in their businesses. This study therefore recommends the setting up of trust fund for companies (especially, small scale business) by government; this would give the companies the opportunity to fully develop and adopt green marketing strategy
Keywords: CSR; Corporate Social Responsibility; Customers; Green marketing adoption; Nigeria; RSE

Artificial Intelligence: Challenges and Opportunities for the Accounting Profession in Nigeria - Nkwede, Maria; Aniuga, Chukwuma (African Journal of Politics and Administrative Studies, 2023)
Artificial intelligence with its fifth industrial revolution is fast griping the African continent. The emergence and adoption of artificial intelligence applications and systems is fast becoming a normal trend in emerging markets landscape across Africa. This paper is borne out of the need to identify challenges that professional grapple with in their quest to surmount the challenges posed by the realities of artificial intelligence applications in Africa. The study adopted the thematic style in presenting the challenges as well as the prospects of artificial intelligence applications for the accounting professional in emerging market. Some of the challenges of artificial intelligence application identified in this study include: complex algorithms, reduced investment, and software failure, lack of political will and limitations amongst others. On the other hand, opportunities of artificial intelligence in emerging market include transportation automation, technological cyborgs and robotic companions amongst others. From the findings, accounting professional are advised to strive harder in order to beat competition by delivering quality services to her clients through harnessing opportunities for rebranding, reengineering and radically improving the business and investment decisions which is the ultimate purpose of the profession. More so, they are encouraged to develop a novel set of proficiency revolving around data in the profession
Keywords: AI; Accounting Profession; Artificial Intelligence; Challenges; Fifth Industrial Revolution; Inteligência artificial; Intelligence Artificielle; Opportunities

The significance of a forum selection agreement as an indicator of the implied choice of law in international contracts: a global comparative perspective - Okoli, Chukwuma Samuel Adesina (Uniform Law Review, 2023)
Where the parties to an international contract fail to specify the choice of law, a forum selection agreement is one of the most, if not the most, significant factors to consider in implying the choice of law in many international, supranational, regional instruments, and national jurisdictions. However, it is an ill-defined, notoriously complex, and hotly debated issue as to the weight that should be attached to a forum selection agreement in implying the choice of law. Hence, this article is devoted to discussing this topic from a comparative perspective, in order to propose a guide to global uniform criteria. To achieve this, the article covers all relevant international, regional, and supranational instruments, and selected legal systems in Africa, Asia, Australasia, Europe, the Middle East, and North and South America. The legal systems compared include those from the global North and global South, including common law, civil law, and mixed legal systems. The article’s core proposal is that an exclusive forum selection agreement should be a key factor in implying the choice of law. However, except in such cases as where a forum is chosen on a neutral basis, there should be a general requirement of corroboration with at least one other factor of significance. The aim of the proposal is to contribute to greater uniformity, predictability, and certainty in the global community in this field of law.

Legal scope of the carrier's liability in the contract of carriage of goods by sea - Drici, Amina (Journal OF LEGAL STUDIES, 2023)
The area of responsibility of the sea freight carrier is to determine the scope of liability over time for damage to the goods and is reflected in the search for the beginning and end of its liability; as well as the determination of the damage which triggers the carrier's obligation to compensate for the losses, damage, delay and determine the persons responsible for the damages for which the recipient or beneficiary of the goods has the right to recourse.
Keywords: Liability; Material scope; Personal scope; Sea carrier; Time scope; Transportation of goods

Legal Framework on Protection of Environmental and Foreign Direct Investment Rights in Nigeria: A Reflection on the Oil and Gas Industry - Osaro, Ebiemere (African Journal of International Energy & Environmental Law, 2023)
It is trite that environmental challenges remain one of the major global concerns and no doubt of great impact on human existence and wellbeing. This impact is a result of human activities on the natural ecosystem. This article examines the legal framework by the Nigerian state in regulating the activities of the multinational investors in the oil and gas industry in the Niger Delta region of the country. It discusses the international, regional, and national legal framework in the protection of environment and environmental rights of the host community and foreign direct investment rights. The author demonstrates the imbalance in the protection of environmental and foreign direct investment rights from which suggestions are made towards correcting this injustice as caused by the existing legal framework.
Keywords: Community; Direct; Environment; Foreign investment; Niger Delta; Oil and Gas Industry; Protection; Rights

Saudi Banks Level of Compliance with Accounting Standards of Accounting and Auditing Organization for Islamic Financial Institutions - A. Al-Bogami, S. (Information Sciences Letters, 2023)

The Relation between Corporate Governance, Risk Management and Financial Performance: Theoretical and Analytics Framework - Ayoob Mohammed Hassan, Noora; Din, Badariah binti Haji; Senasi, Vally (Information Sciences Letters, 2023)
The paper aims to review the relation between Corporate Governance, Risk Management and Performance. We reviewed these variables and develop a Theoretical and Analytics framework. First introduction (study background, Problem Statement, Research Objectives and research questions). Second literature review (A) financial performance such as ROA, ROE, EPS and Tobin’s Q, (B) Corporate Governance as Board of Directors, Board Composition, CEO Duality and Board Size (C) Risk Management. Third, we discussed Underpinning Theories such as, Agency Theory and Institutional Theory. Fourth, we developed a Theoretical Framework where we illustrated (A) Corporate Governance and Financial Performance, (B) Risk Management and Financial Performance (C) Compliance with Accounting Standards and Financial Performance. Finally, we developed a comprehensive reviewing based on above variables.
Keywords: Corporate governance; Performance; Risk Management

Influence of Training, Experience, and Expertise on Quality of Financial Reporting in Dubai – Mediation of Adoption of International Public Sector Accounting Standards - IPSAS - El Haron, Esam O.; Haji Din, Badariah (Information Sciences Letters, 2023)

Accounting Choices During COVID 19 Pandemic: Does Corporate Strategy and Corporate Social Responsibility Matter? - T. Hassan, N. (Information Sciences Letters, 2023)
This study aims to understand the accounting effects of the Corona pandemic in more depth and clarity, where the study explores the accounting choices during the pandemic period and the impact of the firm's strategic orientation and its social responsibility performance on those choices. Using data from non-financial Saudi companies, the accounting choices divided into aggressive accounting strategy and conservative accounting strategy, and regression models used to examine the study hypotheses. The results of the study provide a clearer and in-depth vision about the nature of accounting practices during the pandemic and indicated that business strategy affects accounting choices, while corporate social responsibility does not affect. The results can imply useful information for the market regulators that help them in controlling and stabilizing the market, as well as for professional accounting organizations to help them issue guidelines for accounting work during crises.
Keywords: Accounting choices; CSR; Corporate Social Responsibility; Corporate strategy; Covid-19 pandemic; Saudi companies

Critical Reflection on the Rights of Creditors in Case of Insufficiency of Assets in OHADA Collective Procedures Law - Kontchop, Hilarion; Tsala, Edith Nadège Fopa (International Journal of Law and Society, 2023)
The procedure of liquidation of assets can be closed for the extinction of liabilities or for insufficient assets. The court may then, at the request of any interested person or ex officio, at any time during the proceedings and after a report by the official receiver, close the proceedings. In case of insufficiency of assets, the business disappears and, perhaps, the hope of any payment to creditors as well. For a long time, it was accepted that the closure for lack of assets allows creditors to resume individual proceedings against the debtor, especially if the latter returns to better circumstances. This traditional solution has been abandoned. According to OHADA Uniform Act on the organisation of collective procedures for the settlement of liabilities, revised on 10 December 2015, closure for insufficiency of assets no longer automatically gives creditors the right to take individual action. Thus, when a liquidation leads to a shortage of assets, the satisfaction of creditors remains uncertain. The objective of this study is to show that despite this reform, the protection of creditors’ rights has not changed significantly in the event of insufficient assets. Indeed, any possible recourse to the recovery of their claims remains paralysed by certain measures that infringe their rights. The infringements can be described as severe or moderate depending on the case.
OpenAlex: https://openalex.org/W4381057496
Keywords: Closure (psychology); Collective Proceedings; Creditors; Debtor; Insufficiency of Assets; Liquidation; Settlement (finance)

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

Exploring the Voice of Populist Movements in the Employment of Foreign Nationals: A Comparative Study of Botswana and South Africa - Utete, Reward; Zhou, Sheunesu; Ajani, Oluwatoyin Ayodele (International Journal of Social Science Research and Review, 2023)
Labour immigration has been on the rise and has had policy implications for public leaders of relatively stable Southern African Development Corporation (SADC) countries. In this paper, the status of populism and labour immigration in Botswana and South Africa was explored. The primary sources of labour immigration are Zimbabwe and Mozambique. Economic disparities and the disintegration of the socio-economic conditions of the neighbouring countries have been major antecedents for the labour movements of the masses. The study utilised a qualitative method and comparative case study design. The study found that populist movements have much influence on the termination of employment of foreign nationals in Botswana and South Africa as shown by their anti-immigrant attitudes, market protectionism, and close-the-borders protests. As these measures have become inefficient over the years, policies and proposals are recommended in response.
Keywords: Economy; Employment; Foreign Nationals; Immigrants; Policies; Populist Movements

Corporate human rights obligations of investors in recent investment agreements: The progressive hardening process of CSR clauses - Francis Maïnkade, Belengar (Heliyon, 2023)
Since the earlier indirect Corporate Social Responsibility (CSR) provisions failed to hold investors responsible for human rights abuses, the recent hardening process of direct CSR clauses has resulted in incorporating CSR clauses under sections or chapters entitled “investors obligations” and tying CSR obligations to binding human rights and environmental prohibitions, as well as to human rights obligations established by the host state's legislation. This paper provides a non-exhaustive analysis of recent developments in treaty practice based on research primarily sourced from investment agreements concluded between 2012 and 2021, doctrinal input, and normative analysis. As shown in this paper the hardening process has not yet been completed, and reformations are necessary. Specifically, new investment agreements should enshrine investor human rights obligations as legally binding obligations, consider violations of these CSR obligations as part of investment disputes and provide direct remedies to victims. This study contributes to the literature on the international responsibility of TNCs with regard to human rights by examining the process of hardening up the CSR obligations within investment agreements as an approach that could lead to effective human rights protection.
Keywords: Corporate Social Responsibility; Corporate human rights responsibility; Hardening of corporate social responsibility clauses; International responsibility of transnational companies; Investors' human rights obligations

Analysis of Intellectual Property Rights Disputes Between PS Glow and MS Glow in View of Law No. 20 of 2016 Concerning Marks and Geographical Indications (Analysis of Decision of Case Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby) - Gracia, Indiera Fortuna; Kurniawan, Kurniawan; Sili, Eduardus Bayo (International Journal of Social Science Research and Review, 2023)
This study analyzes intellectual property rights disputes between PSGlow and MSGlow in terms of Law no. 20 of 2016 concerning Trademarks and Geographical Indications (analysis of case decision number: 2/pdt.sus.HKI/Merek/2022/pn.niaga Sby) which aims to explain and analyze the basic considerations of Surabaya Commercial Court judges in accepting lawsuits, explaining and analyzing how is the legal protection of trademarks that have been registered based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications, explaining and analyzing whether there is an element of passing off between PS Glow and MS Glow based on Case Decision Number: 2/Pdt.Sus.HKI /Merek/2022/PN. Niaga Sby.The legal materials in this research are primary, secondary, and tertiary legal materials using normative research methods.The basis for consideration is that a lawsuit was filed from PS Glow for the use of the brand without rights against MS Glow. and legal protection for brands that have been registered under Law no. 20 of 2016 concerning Marks and Geographical Indications, namely that the penalties that will be imposed on these counterfeiters can be in the form of imprisonment, imprisonment and fines, as referred to in articles 100 to 102 of Law No. 20 of 2016 concerning Marks and Geographical Indications. and between PS Glow and MS Glow there is no element of passing off based on Case Decision Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby, because the MS Glow brand registers its brand in HAKI in class 32 with the classification of powdered drinks and PS Glow registered their brand on Intellectual Property Rights in class 3 with a cosmetic classification.
Keywords: Brand; IPR; Passing off

Challenges of CSR in Sub-Saharan Africa: clarifying the gaps between the regulations and human rights issues - Ndong Ntoutoume, Achille Gildas (International Journal of Corporate Social Responsibility, 2023)
This paper discusses the practice of Corporate Social Responsibility (CSR) and its challenges in Sub-Saharan Africa. The main purpose is to highlight and clarify the gaps between CSR regulations and human rights abuses caused by business organizations.
Keywords: Business and human rights; CSR; Stakeholders; Sub-Saharan Africa

Banking System Fragility in Nigeria: Hanging on the Precipice? - Kayode, Peter; Oluwole, Foluso (AAU Journal of Business and Law, 2023)
The health of a country’s banking system is a key determinant to the development of the country. A fragile banking system portends danger not only to the financial system but the entire economy. This study investigates the state of the Nigerian banking system in terms of stability or fragility from 1981 to 2020. We used the banking system fragility index (BSFI) proposed by Kibritçioğlu (2003) to analyze Nigerian banking industry aggregate data from three risk areas: credit, market and liquidity. We estimated that out of the 40 years examined, the banking system was fragile for 23 years given their BSFI less than 0 while it was not fragile for 17 years with BSFI = 0 or greater. We found that most of the years when the Nigerian banking system was fragile were periods of relaxed monetary policies, deregulation and credit expansion. Secondly, the years of banking system stability were when the county’s banking system was subjected to stiff regulation and consolidation. Given the number of years that the system was fragile, we observed that sustained economic growth and development requires that the banking system remain strong as long as possible, and that the Nigerian situation could not promote this important objective. We recommend that the financial regulatory authorities put in place more stringent policies as banks are more fragile during the deregulation of the banking industry.
AAU Journal of Business and Law مجلة جامعة العين للأعمال والقانون
Keywords: Banking system fragility; Precipice

Who Are the Best Law Firms? Rankings from IPO Performance - Bates, Thomas W.; Lv, Jin Roc; Neyland, Jordan (The Journal of Corporation Law, 2023)
Recent scandals have brought rankings to the forefront of the legal profession. Several of the most prestigious academic institutions have withdrawn from being ranked, citing the problematic nature of the rankings. However, rankings persist for both legal academics and practice, and there is substantial sentiment to improve the methodologies, with little detail as to how to improve. In this paper, we rank law firms on their clients’ IPO performance. We focus on the most relevant outcomes: litigation, first-day returns, disclosure, and legal fees. The focus on these measures provides benefits relative to other methodologies, which typically focus on inputs or size-related characteristics. Namely, this ranking is less manipulable and more accurately captures performance metrics that matter most to clients’ shareholders. Our rankings control for observable and unobservable deal characteristics, which helps ensure we capture law firm quality, not client traits. With the rankings based on legal fees, potential clients can compare the benefits of a particular law firm (e.g., lower litigation or higher selling prices) against the additional cost of hiring a higher-quality law firm. Hence, our rankings allow for a value-for-the-money comparison of law firms for clients selling shares in an IPO.
Keywords: Disclosure; IPO; Lawyers; Litigation; Rankings; Securities Regulation

Legal Protection of Trade Secret from the View of Civil and Criminal Law - Atika, Atika (International Journal of Social Science Research and Review, 2023)
Indonesia has ratified the WTO/TRIPs Agreement convention and is in full compliance and non-reservation, the insistence of developed countries’ owners of Intellectual Property Rights against Indonesia, and the need for national Intellectual Property Rights. By looking at the above, legal protection is needed for every product and service, especially licenses for trade secrets in the Intellectual Property Rights component. The state imposes criminal sanctions on violators of Trade Secret rights as stipulated in chapter 17 (1) constitution number 30/2000. However, it is also hoped that the act of imposing sanctions by the state will return to the interests of the protected party by making the crime a complaint offense chapter 17 (2) constitution number 30/2000. There are repressive legal actions that can be carried out as chapter 11 constitution number 30/2000 states that the holder of trade secret rights or the licensee may sue anyone who deliberately or without rights commits the actions referred to in the article in the form of (a). Compensations claim and/or; (b). Cessation of all actions referred to in chapter 4 constitution number 30/2000.
Keywords: Intellectual Property Rights; Legal Protection; Trade Secrets

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

African Economic Integration Initiatives and the Challenge of Responsible Business Conducts: Analysis of Corporate Social Responsibility Provisions in African Regional Trade and Investment Agreements - Azapmo, Jean Bertrand (Revue Interventions économiques, 2023)
Left alone, economic integration initiatives, which aim to promote growth through investment and trade liberalization, do not automatically generate win-win outcomes for all stakeholders, or lead to the inclusive economic growth and sustainable development of participating countries. This situation which is due among others to possible market failures and externalities of corporations’ activities, has increasingly become a matter of concern with the numerous corruption scandals; human rights violations and environmental degradation involving corporations observed in a recent past. How therefore to continue promoting economic integration while ensuring socially responsible conducts from businesses in societies where they operate? One approach that has recently gained traction is the institutionalization of corporate social responsibility (CSR) clauses in trade and investment agreements. This paper analyses 10 African regional trade and investment agreements concluded between 2000 and 2020 to determine the extent to which they converge with this trend and the approach adopted in regulating CSR. The research complements the literature on the nexus between international law and CSR in the African context. Laissées à elles-mêmes, les initiatives d'intégration économique, qui visent à promouvoir la croissance par la libéralisation commerciale et économique, ne génèrent pas automatiquement des résultats gagnant-gagnant pour toutes les parties prenantes, ou ne conduisent pas à la croissance économique inclusive et au développement durable des pays participants. Cette situation, qui est due entre autres à d’éventuelles défaillances du marché et à des externalités des activités des entreprises, est devenue de plus en plus préoccupante avec les nombreux scandales de corruption, de violation des droits de l’homme et de dégradation de l’environnement impliquant des entreprises. Comment donc continuer à promouvoir l'intégration économique tout en garantissant des comportements socialement responsables des entreprises dans les sociétés où elles opèrent ? Une approche qui a récemment gagné du terrain est l'institutionnalisation des clauses de responsabilité sociale des entreprises (RSE) dans les accords de commerce et d'investissement. Cet article analyse 10 accords régionaux africains de commerce et d'investissement conclus entre 2000 et 2020 pour déterminer dans quelle mesure ils convergent avec cette tendance à l’institutionnalisation des clauses sur la RSE, et l'approche adoptée dans la réglementation de la RSE. La recherche complète la littérature sur le lien entre le droit international et la RSE dans le contexte africain.
Keywords: Accords régionaux d'investissement; Accords régionaux de commerce; AfCFTA; CEDEAO; Corporate Social Responsibility; ECOWAS and SADC; Economic integration; Intégration économique; SADC; ZLECAf; regional trade and investment agreements; responsabilité sociale des entreprises

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Trade between China and 45 African countries: does the Gravity Model matter? - Ondja'A Abeng-Abe, Christian Johan; Ebissemitie Kisso, Eunice (Revue d’Études Sino-Africaines, 2023)
The population of Africa and that of China put together amounts to a little over one-third of the world's total. The theoretical justification of the gravity model is applied to analyze the factors influencing bilateral trade between China and African countries using the panel data regression technique, covering the period between 2002 and 2021 and with special consideration for the income level of the African countries. Empirical results and estimates reveal that the economic size as well as the population of trade partners positively affect China’s trade with 45 African countries. The positive impact that distance has on trade is inconsistent with previous research. We conclude from the analysis that the factors affecting trade between China and African countries are, namely, the size of the population, the economic size represented by the GDP, and the distance between the countries. The indication of effects on the trade sector is important, and the sensitivity of the potential product to distance and countries varies considerably, giving a revealed comparative advantage. African countries should diversify their exports and improve their trade diplomacy.
Keywords: Africa; China; Gravity Model; Panel data regression; Trade

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

Impact of the Commercial Law on E-Commerce Practices and Business Sustainability in Nigeria - Ufua, Daniel Ebakoleaneh; Olujobi, Olusola Joshua; Al-Faryan, Mamdouh Abdulaziz Saleh (International Journal of Management, Economics and Social Sciences, 2023)
With the advent of global market interdependence and interaction, coupled with the consistent spread of the internet facilities across geographical boundaries, businesses engage in e-commerce practices either to augment existing on-ground businesses or as independent outfits. This study focused on the law on e-commerce practice and business sustainability in Nigeria. The study applied a conceptual review focusing on the trends of development of ecommerce practice and the supportive effects of the legal system in facilitating business sustainability in Nigeria. The study relied on extant literature sourced from various outlets, relevant to the topic of this study. The key findings highlighted and discussed factors for improved e-commerce practices in Nigeria. These included access to legal services, effective government policy and institutional support, time and fair interpretation of the law governing e-commerce, continuous evaluation of the ecommerce processes in Nigeria, increased awareness and familiarity with e-commerce facilities, and the adoption of suitable technology. The study provides valuable insight into the support of the Nigerian commercial sector on e-commerce practices. The adoption of systems theory enhances the promotion of fairness across the entire ambience of e-commerce practice and the support of the law. This implied focusing on the continuous evaluation of legal support and a flexible process of developing the needed approaches to address emerging changes in e-commerce that can enhance business sustainability in Nigeria.
eprints.covenantuniversity.edu.ng
Keywords: Business sustainability; E-commerce; Flexible process; Government Policy; Legal system support; Nigerian economy

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on. There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

Situation of Earning Management After Revision of the Ohada Accounting Standards Adopted on January 26, 2017 - Georges, Wandji; Nebasi, Akoso Wilfred (Law and Economy, 2022)
Following the mandatory adoption of the revised OHADA Accounting Standards that have moved closer to the International Financial Reporting Standards (IFRS), this study examines whether the level of Earnings Management of Companies making public offers or listed firms, in the West African Stock Exchange Market Abidjan-Ivory Coast (BRVM) has reduced. The study avails of Financial Statement figures during pre-adoption (2014–2017) and post-adoption (2018–2021) periods, for 26 selected listed firms in the BRVM. Findings suggest that firms in the post-adoption period of the revised OHADA Accounting Standards (2018–2021) are less likely to smooth earnings compared to the pre-adoption period (2014–2017). This indicates that adopting accounting standards of higher quality can bring an improvement in Financial Reporting Quality, everything being equal.
Number: 4
Keywords: Earnings management; IFRS; International Financial Reporting Accounting Standards (IFRS); Revised OHADA Accounting Standards; SYSCOHADA

International Commercial Law Emerging in Africa - Neels, Jan L. (Potchefstroom Electronic Law Journal, 2022)
This article provides an overview of the history of international commercial law in Africa with reference to instruments of the three sister organisations of private international law (in a wide sense): UNCITRAL (the United Nations Commission on International Trade Law), UNIDROIT (the International Institute for the Unification of Private Law) and the HCCH (the Hague Conference on Private International Law). The adoption of UNIDROIT's Cape Town Convention on International Interests in Mobile Equipment of 2001 is identified as a possible watershed moment in respect of the future development of international commercial law in Africa. Following the creation of an African Continental Free Trade Area by member countries of the African Union, it is suggested that participating states reconsider joining the United Nations Convention on the International Sale of Goods (1980) (CISG) and incorporating the UNCITRAL Model Law on International Commercial Arbitration (1985/2006), which are in a certain sense the two founding documents of the modern lex mercatoria. Another priority, the author suggests, is that Africa needs a supporting instrument on the private international law of contract. The first draft of the African Principles on the Law Applicable to International Commercial Contracts is then discussed with an emphasis on the role of substantive law instruments, in particular the CISG
Keywords: African Principles of Commercial Private International Law; African Principles on the Law Applicable to International Commercial Contracts; International Commercial Law; International commercial contracts; Private international law

Impact of Lack of Self-efficiency and Assets Evaluation on Resistance of IPSAS Implementation - Alhuda Tawffek Al-otoom, Nour; Alrabba, Hussein Mohammed (Information Sciences Letters, 2022)
This study examines factors influencing the international public sector accounting standards (IPSAS) implementation and presenting of accounting information related to the Jordanian public sector, also the information of reports is based on “Accounting principles and practices (No.39/1962) among government accountants. This study identified several important factors influencing the IPSAS implementation which are; lack of self-efficiency and assets evaluation. In addition, a quantitative approach was employed by distributed the questionnaires to 100 respondents enrolled at Jordanian General Budget Department using simple random sampling. The data were analyzed using SPSS to verify the relationships between the variables. The results found significant positive relationships between lack of self-efficiency and assets evaluation and IPSAS implementation resistance among government accountant in the public sector of Jordan. To sum up, this study contributes in expanding the literature concerning IPSAS implementation in Jordanian context, it’s also provides meaningful guideline to the government of Jordan for IPSAS implementation resistance. Finally, providing insights on the critical success factors to ensure successful implementation process.
Keywords: Accrual Accounting; Assets Evaluation; IPSASs; Public Sector Accounting; Self-efficiency

Article 255 of the OHADA Uniform Act on General Commercial Law and Consumer Protection: The Need to Experiment - Djieufack, Roland (International Journal on Consumer Law and Practice, 2022)

Business Dispute Settlement Through Mediation in State Courts and Arbitration Institutions - Yuspin, Wardah; Aziz, Abdul (International Journal of Social Science Research and Review, 2022)
In social life, there are often differences in perceptions between humans, causing problems or disputes, whether minor or serious. Likewise in the relationship of economic activities or more commonly known as business relations. Not infrequently humans experience a clash and differences of opinion that lead to disputes. Various problems will always arise in business as long as humans run their business solely for profit, so there are often differences of opinion because the parties will not be harmed which will eventually lead to disputes. In the end, dispute resolution, especially business disputes, is often resolved through a trial in court through a lawsuit by one of the parties who feel aggrieved. However, what was expected from the settlement turned out to be unsatisfactory for the parties because the settlement through litigation sometimes took a long time to obtain legal certainty so that it actually harmed business people because of the loss of time, energy and materials. As an alternative to resolving business disputes, business actors have a tendency to avoid disputes in court and choose to use mediation or through arbitration institutions. This study will briefly describe the comparison of business dispute resolution through court mediation with settlement through arbitration institutions. The research was conducted through descriptive empirical legal research.
Keywords: Arbitration; Business; Dispute

The application of knowledge stylised facts in West Africa Economic and Monetary Union (WAEMU) - Amanzou, Nogbou Andetchi Aubin; Ballo, Zie; Troupa, Sery Guy Flavien (Journal of Innovation and Entrepreneurship, 2022)
Sub-Saharan Africa has one of the dynamic economies in the world. Unfortunately, the performance achieve has not led to a reduction of social issues. So, the government are making massive investment to overcome social issues. This massive public investment highlights the exogenous nature of the current economic growth. So, a change of the strategy in the economic management of sub-Saharan Africa is required. One solution remains the change of economic paradigm: the transition from exogenous economic with decreased return to endogenous economic with increased return. The theoretical explanation of such arguments are supported by New Growth Theory. However, the implementation of the new theory required compliance to a set of indicators known as stylized facts. In 2009, Romer and Jones have developed a list of stylized corresponding to the need of New Growth Theory. The stylized facts of the West African Economic and Monetary Union (WAEMU) have been compared to the standard facts of Romer and Jones in order to apply the recommendations of New Growth Theory in this area. To reach that aim, the stylized facts have been described and analysed with econometric panel model. As result, we find that the description of the stylized facts in WAEMU fitted perfectly with that of Romer and Jones for the same period. Unfortunately, when using data, institution don’t work as expected by Romer and Jones. This study strengthens the argument for the implementation of economic policy based on the valorisation of knowledge economic in WAEMU.
Keywords: Africa; D83; Economic development; Economic growth; Knowledge economic; Macroeconomic Analyses; N17; O11; O17; O40

Analysis of the Determinants of the Effectiveness of the Board of Directors in Family Businesses in Cameroon - Roukatou, Aboubakar; Dretti, Denise (Open Journal of Business and Management, 2022)
The composition of the Board of Directors is commonly presented as an understandable variable for its effectiveness. However, the work that examined the relationship between the composition and effectiveness of the Board is not characterized, as they require about whether or not certain categories of directors (internal, external, independent) are relevant and the related empirical results are mixed. This work examines the relationship between the characteristics of the board of directors and its effectiveness in a type of business that is very common in the world, respecting the family business. Thus, the problem that this study tries to solve is to identify the characteristics of the board of directors that can contribute to its effectiveness in Cameroonian family businesses. We found that the size of the Board, the presence of external directors, and the cumulative management and control functions appear to have an impact on the effectiveness of the Board.
Number: 5
Keywords: Board of directors; Family Business; Governance; Public Limited Company

Comparison of IAS/IFRS and OHADA standards in terms of taking inflation into account in financial accounting - Matofali, Victoire (Revue du Contrôle de la Comptabilité et de l’Audit, 2022)
Financial accounting is one of the indispensable management tools in an organization, its objective is to present financial statements that reflect a true and fair view of the assets, financial position and results of the entity. In times of high inflation, however, money loses its purchasing power at such a rate that comparing amounts resulting from transactions and other events that occurred at different times, even during the same accounting period, can be misleading. This can cause the figures in the financial statements to be misleading. It is therefore essential to adjust these figures to the actual economic conditions in order to preserve a true and fair view of the company's assets, financial position and results. International financial standards such as those of OHADA analyze this problem of inflation in accounting through different methods of restatement of the figures of the financial statements to make them faithful and consistent with the economic reality. In this work, we will identify the points of divergence as well as the points of convergence between OHADA and IAS/IFRS accounting standards in terms of inflation accounting.
CERN European Organization for Nuclear Research
Keywords: Accounting; IAS/IFRS; Inflation; Standardization

The Effects of Covid-19 Crisis on Good Governance at the Local Level, The Case of Tunisia - Braham, Fatma; Seguir, Sonia (Journal of the Association of Arab Universities for Research in Higher Education, 2022)
The COVID-19 crisis, in addition to its serious health impact, has negatively affected key socio-economic aggregates and has shocked the strategic planning of all economic and social actors, including local communities. In search of resilient, skillful and intelligent good territorial governance, the municipalities are working to adapt their governance systems to the new social and environmental priorities. This work proposes a new reading of the acquired approaches to good governance, a new paradigm related to the new conjuncture and an assessment of the performance system at the central and local levels

Influence of current and capital account liberalization on economic growth: Evidence from heavily indebted SSA economies - Leykun, Fentaw (African Journal of Economic and Business Research, 2022)
Capital and current account restrictions were widely used in the past but were largely released during the liberalization movement of the 1990s, as interventionist policies got widespread support that paves the way to the renewed conception of government as an impartial referee. Such a restriction has come back on the agenda with the surge in public debt in the rouse of the Global Financial Crisis. By distorting market signals and incentives, financial repression persuades losses from inefficiency and rent-seeking that cannot be easily quantified. This paper seeks to investigate the impact of current and capital account liberalization on growth, using recent de jure and de facto measures, covering 26 heavily indebted Sub-Saharan African countries over 2000-2020. The results suggest that capital account liberalization escalates growth, brought distributional efficiency in conformity with the neoclassical growth model.
Keywords: Capital account; Current account; Economic growth; Financial liberalization; Financial repression

Investment Law and its Others - Schneiderman, David (Temple International Law Journal, 2022)
Accepted: 2024-06-06T13:17:31Z

Determining the Liability for Carriage of Goods by Road in West Africa - Can OHADA Uniform Rules on Transport be a Foundation? - Osinuga, Damilola (Southern African Journal of Policy and Development, 2022)

Innovative Approaches for Tackling Tax Evasion in the South African Minibus Taxi Industry: Lessons from Ghana, Zambia, and Zimbabwe - Ndlovu, Jane; Mohale, Enhle (Journal of Law, Society and Development, 2022)
In South Africa, minibus taxis are a crucial mode of public transport for many commuters and a vital informal business sector with an estimated value of R90 billion. Concerns have been raised that the South African Revenue Service (SARS) is not collecting the optimal amount of tax revenue from this industry, with estimated tax collection at only R5 million in 2021. As a result of concerns that this industry might be involved in tax evasion or massive tax avoidance, this study investigates the taxation of minibus taxis in South Africa and explores alternative tax regimes that could be implemented to improve revenue collection. The study compares the current South African turnover tax system for minibus taxi operators to other African tax systems and evaluates a viable alternative tax regime or tax collection system. To improve tax collection from the industry, South Africa could consider a tax system tailored to the industry’s informal nature, utilising metrics such as vehicle seating capacity or distance travelled. A standardised tax system for small, medium, and micro enterprises may not be suitable. Consultation with industry stakeholders is essential for the proposed tax system to be acceptable. The study’s findings could inform South Africa’s National Treasury in creating a tax structure or collection scheme targeting the minibus taxi industry. This could increase tax revenue collection from the industry and support government expenditure, including income and wealth redistribution. This study distinguishes itself from prior publications on the South African minibus taxi industry by addressing tax compliance and collection challenges. It offers recommendations for alternative tax regimes to mitigate these challenges.
Keywords: Informal sector; Micro-enterprises; Minibus taxi; Presumptive tax; Tax relief; Turnover tax

Effectiveness of the Recognition and Enforcement of the OHADA's Arbitral Award - Rezara, Juvelin (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization which consists of arbitral tribunal within some regions in Africa in handling international investment and commercial disputes. Henceforth, the purpose of this study is to examine the effectivity of the enforcement of arbitral awards under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal binding to member countries, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards and the effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving arbitration rules relating to enforcement of the awards. It is found that the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law due to conflict of interest.
Keywords: Arbitral Awards; Enforcement; Exequatur; res judicata

Effectiveness of the Recognition and Enforcement of the OHADA`S Arbitral Award - Juvelin, Rezara (International Journal of Social Science and Human Research, 2022)
OHADA is amongst an international organization consists of arbitral tribunal within regions in Africa to deal with international disputes on investment and commercial related. Henceforth, the purpose of the study examines the effectivity of arbitral awards enforcement under the perspectives of OHADA arbitration rules. The study axed through qualitative approach by interpreting legal rules, analyzing cases and commenting the weakness of the charter in terms of enforcement and recognition of arbitral awards. The decision of OHADA arbitral tribunal shall contain intrinsically legal effect to country members, however it leads problematics as the enforcement and recognition rules may be different in every country involved. Hence, the study interpreted the legal rules concerning enforcement and recognition of arbitral awards, effectiveness of the rules. In addition it exerted also the challenges and significant recommendation for improving the arbitration rules on enforcement of arbitral awards. It is found the weakness of the arbitral awards locates on refusal of concerned State to enforce the awards under the domestic law for undefinable conflict of interest
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Enforcement; OHADA; res judicata and exequatur

Hyperlinking and copyright - Karjiker, Sadulla (The South African Law Journal, 2022)
This article critically considers the legality of hyperlinking to copyright-protected material on the Internet. It considers the position with respect to standard hyperlinks, and attempts to provide a possible approach in light of the proposed introduction of two new exclusive rights, namely (i) the right of communication to the public; and (ii) the making-available right. These new exclusive rights appear to be an attempt to amend the South African Copyright Act in order to give effect to the 1996 WIPO Copyright Treaty, which sought to ‘digitise’ copyright law in light of the digital technology that had developed. The WIPO Copyright Treaty supplements, in particular, the rights granted to copyright owners under the Berne Convention, extending the right of communication to the public to include the making-available right. Use will be made of the case law of the Court of Justice of the European Union, which has given effect to the right of communication to the public (including the making-available right), following its inclusion in the WIPO Copyright Treaty of 1996. Through a more focused analysis of these exclusive rights, it is intended that this article can provide some guidance to South African lawyers and our courts when considering the application and scope of these exclusive rights.
Keywords: Copyright; Hyperlinking; Intellectual property; Legality

Exporting the Luxembourg Rail Protocol to the Convention on International Interests in Mobile Equipment to Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2022)
This article recommends the Cape Town Convention on International Interests in Mobile Equipment and appeals to African countries to accede to the Luxembourg Protocol on Railway Rolling Stock (Rail Protocol). The discussion in this article focuses on the extent to which Article XXII of the Rail Protocol can be applied with respect to Africa. The article critically analyses the competence of the African Economic Community (AEC) and its sub-regional organizations to accede to the Cape Town Convention and Rail Protocol. The author provides a detailed argumentative analysis of the legal mandate of the AEC and the influence of African Union (AU) laws on the competence of the AEC’s sub-regional organizations to make declarations under the Cape Town Convention and Rail Protocol. The analysis confirms that competence to accede to the Convention and Rail Protocol resides with sovereign States in Africa and not with the AU, the AEC, the Organisation pour l’harmonisation en Afrique du Droit des Affaires, or any existing sub-regional organization in Africa.

Soil protection and legal aspects of international trade in agriculture in times of climate change: The WTO dimension - Ruppel, Oliver C. (Soil Security, 2022)
Soils are essential for food security and the right to food. But where is the connect between soil, trade in agriculture and the rules of the World Trade Organization (WTO)? While the WTO is not an environmental protection agency (as per its initial design at least), existing WTO rules fail to make agricultural trade patterns sustainable when it comes to the medium of soil. Notwithstanding, trade policy is of growing importance to soil protection, biodiversity preservation, deforestation, land degradation and desertification. Soil is key in this regard not only because it is the world's second-largest carbon sink after the oceans. Unsustainable trade in agricultural commodities should increasingly be seen in light of an industrial transition to increased climate neutrality and decarbonisation. This in turn should be guided by the leitmotiv – in times of climate change - to place soil protection for sustainable food security at the centre of any economic policy, also in terms of the rules on international trade in agriculture under the WTO.
Keywords: Climate change; Decarbonisation; Food security; Soil protection; Trade in agriculture; World trade law

Does the implementation of IFRS improve transparency regarding the company's financial conditions?: evidence from an emerging market - Ebaid, Ibrahim El-Sayed (PSU Research Review, 2022)
Purpose This study aims to examine whether there are differences between financial statements prepared in accordance with International Financial Reporting Standards (IFRS) and financial statements prepared in accordance with local accounting standards in terms of its ability to present the financial conditions of companies listed on the Saudi Stock Exchange as one of the emerging markets. Design/methodology/approach Data on study variables were obtained from the published financial statements of 67 of listed companies in the Saudi Stock Exchange during the period 2014–2019. The study addressed the research hypotheses by using Altman Z-score model. Both the T-test and Wilcoxon rank test were used to investigate the significance of differences between the values of Z-score and the individual variables included in the model in the pre- and post-IFRS mandatory adoption periods. Findings The results revealed a decrease in the values of Z-score as well as the values of the individual variables included in the model in the period following the adoption of IFRS than it was before the adoption of IFRS, which indicates the ability of IFRS to show the financial conditions of companies more transparently than local accounting standards. However, the results of the T-test and Wilcoxon test showed that these decreases were not statistically significant. Research limitations/implications This study has some limitations, including the small sample size as a result of the small size of the Saudi Stock Exchange, As well as the reliance of this study only on the Altman model with its five variables in assessing financial conditions without examining the impact of other factors that may affect the financial conditions of companies. Practical implications Financial conditions of the companies have important implications for multiple parties such as management, government, investors and others as an early warning sign that enables them to take the necessary measures early before the actual bankruptcy occurs and what results in costs. Originality/value Although assessing financial conditions of the companies is one of the basic uses of accounting information, this topic has not received sufficient attention as a means to test the benefits of adopting IFRS, especially in emerging markets such as Saudi Stock Exchange. This is the first study to examine the impact of adopting IFRS on the transparency of financial reporting in assessing financial conditions in Saudi Arabia.
Keywords: Financial conditions; IFRS; Saudi Arabia; Z-score

Factors affecting the probability of formalizing informal sector activities in Sub Saharan Africa: evidence from World Bank enterprise surveys - Moyo, Busani (African Journal of Economic and Management Studies, 2022)
Purpose This study aims to investigate the factors that affect the likelihood of formalizing informal sector activities in 13 Sub-Saharan African countries, using World Bank enterprise survey data collected between the periods 2009 and 2018. Notwithstanding the great contribution of the informal economy in Africa, developing countries may stand to gain more if they make inroads in formalizing the informal sector. Design/methodology/approach Since the dependent variable is binary taking the value of one if the firm is willing to formalize and zero otherwise, the study will employ a discrete choice probit model. Findings Results inter alia show that firms that are more likely to formalize are young, owned by individuals with high levels of education and, have registered before. Governments should therefore target firms that are young and provide them with information about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood for them to register would be high. Research limitations/implications The study uses cross sectional data and therefore cannot capture time variant factors affecting the probability to register and also cannot correct effectively for endogeneity. Practical implications Governments should therefore target firms that are young and provide them with as much information as possible about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood to convince them to register would be high. They should also reduce the cost of registration so as to improve net benefits in line with the rational exit view. Social implications Formalizing informal activities will help improve the performance of these firms, reduce vulnerable employment as well as crime, poverty and inequality. Providing decent operating and working conditions to informal players will reduce social and political unrest. Originality/value The African continent is home to many informal firms accounting for roughly 55% of economic activity with 90% of workers eking out a living in a sector that does not respect worker rights, provide decent working conditions and where changes in growth have done little to reduce its size. Regulatory reforms have also been implemented resulting in the number of start-up registration procedures falling from 11 in 2003 to seven in 2019. The uniqueness of Sub Saharan Africa in terms of entrepreneurial culture, political, institutional and economic conditions as well as lack of consensus in the extant empirical literature make this study pertinent.
Keywords: Formalization; Informal; World Bank and Africa

The impact of the pandemic on the legal regulation of entrepreneurial activity of transport companies - Rubtsova, Natalya (Transportation Research Procedia, 2022)
The purpose of this paper is to analyze the trends of legal regulation in the business activity under the conditions of new coronavirus infection. The dialectical method of research in conjunction with a retrospective and comparative analysis made it possible to identify three main trends in the legal regulation of entrepreneurial activity in the framework of new socio-economic realities. The increasing role of state regulation of entrepreneurial activity, based on the use of public and legal means, due to the need to increase state intervention in the activities of entrepreneurs is shown. The state support of business for the subsequent development of the economy and compliance with the social balance is also increasing. Accordingly, the social importance of entrepreneurial activity is growing. The pandemic has also intensified the digitalization of entrepreneurial activity, of transport companies, since many traditional forms of doing business are limited by the forced isolation of society. Individual means of digitalization, including the industrial Internet of Things, e-commerce, and smart contracts, have become most prevalent. Consequently, the pandemic cannot be viewed only as a negative factor, its impact on entrepreneurial activity also has a positive effect.
Keywords: Business; axiology; digitalization; means of legal regulation; pandemic; transport companies

Does the impact of IFRS on audit fees differ between early and late adopters? - Tawiah, Vincent Konadu (International Journal of Accounting & Information Management, 2022)
Purpose This study aims to examine whether the impact of international financial reporting standards (IFRS) on audit fees differs between early and late adopters. Design/methodology/approach The authors use robust econometric estimation on a sample of 314 firms from both early and late IFRS adopting countries. Findings The authors find that IFRS is positively and significantly associated with an increase in audit fees for early adopters, but the impact is very weak for late adopters and insignificant in some cases. The results on auditing time suggest that increase in audit fees around IFRS adoption is due to an increase in audit reporting lags. After accounting for pre- and post-years, the authors find that the relationship between IFRS and audit fees, as well as audit time for late adopters, is significant only in the adoption year. However, early adopters experience a significant increase in audit fees and audit time in the transition year to one-year post-adoption. Practical implications The findings imply that countries that are yet to adopt IFRS are less likely to experience a significant increase in audit fees audit time. Hence, is probable that the benefit of IFRS will outweigh the cost. Originality/value The results, therefore, suggest that early adopters paid a premium for been the first users of IFRS, which is consistent with any innovation. The study provides new insights by demonstrating that the consequences of IFRS differ between early and late adopters.
Keywords: Africa; Audit fees; Audit reporting lags; Early adopters; IFRS; Late adopters

Accountability during the Incorporation of Public and Private Limited Companies under Ohada Law - Sama, Merinda Afanui (International Journal of Research and Innovation in Social Science, 2022)
This work sets out to evaluate the OHADA Uniform Act’s laws on accountability in Private and Public Limited Companies. Normally, laws which provide for effective accountability, guarantee the smooth functioning and stability of companies since its rules work at averting all forms of mismanagements. The inspiration of this work stems from the realization that, levels of accountability in these companies are still wanting. Hitherto, companies are plagued with vices of obscured activities, fake transactions, non-transparent reporting and acute dishonesty by its organs. It is therefore baffling that, these are still prevalent despite the existence of the Uniform Act’s laws which contains accountability mechanism aimed at dispelling all these forms of corporate transgressions. From this arose lingering doubts as to how these laws are.

La jurisprudence de la Cour commune de justice et d'arbitrage (CCJA) sur l'immunité d'exécution au profit des entreprises publiques - Quo vadis? - Ayikaba, Jules Masuku (Recht in Afrika, 2022)
This study traces the evolution of the CCJA case law on the principle of exemption from enforcement for public companies. It aims in particular to highlight the direction in which this case law is moving. It appears that the CCJA has so far not succeeded in elaborating its own definition of the concept of 'public companies'; yet it is there that, in our view, the mystery of the immunity from execution that it has long recognized to these companies hides; even when they were incorporated in the form of a corporation. However, over time, the Court has rightly reversed its previous decisions by moving from an extensive to a restrictive interpretation of exemption from enforcement. In any case, the involvement of the lawmaker is more than welcome in order to put an end to the situation of inequality, which has existed for a long time in terms of enforcement under OHADA law, between corporations having the State or its branches (public companies) as shareholders and those whose shareholders have no State participation.

Dissenting opinions in international arbitration : More than an opinion? - Baltag, Crina (Principia, 2022)
Dissenting opinions have increasingly gained acceptance in international arbitration, with arbitration rules and laws allowing them, by either providing directly for such a possibility, or indirectly, by referring to ‘arbitral awards taken with majority of votes.’ Alan Redfern’s seminal 2003 Freshfields Lecture on dissenting opinions has highlighted the benefits, as well as the concerns with dissenting opinions, in particular, with those directed to alleged irregularities in the arbitral procedure. More recently, in the motion to set aside the arbitral award in Vantage Deep Water Co. v. Petrobras Am., Inc., the US District Court for the Southern District of Texas has rejected Petrobras’ argument that ‘the arbitral process was [so] “fundamentally flawed” … that “produced the extraordinary Dissent filed” by Mr Gaitis.’ While it is accepted that dissenting opinions have no legal effects, and in particular no legal effects similar to arbitral awards, they can have significant impact on the set aside and recognition and enforcement of arbitral awards. Las opiniones disidentes han ganado aceptación en el arbitraje internacional mediante reglas de arbitraje y leyes permitiéndolos, ya sea aceptando directamente la posibilidad de emitirlos, o indirectamente refiriéndose a ‘laudos arbitrales decididos por mayoría de votos’. El seminario del 2003 de Freshfields dictado por Alan Redfern sobre opiniones disidentes llamó la atención sobre los beneficios y las preocupaciones, en particular, aquellas opiniones disidentes dirigidas a señalar irregularidades en el procedimiento arbitral. Más recientemente, durante el procedimiento para anular el laudo arbitral de Vantage Deep Water Co. v. Petrobas Am., Inc., la Corte del Distrito Sur de Texas rechazó el argumento de Petrobras de que ‘el procedimiento arbitral había sido [tan] “fudamentalmente viciado…” que “produjo la extraordinaria opinión disidente consignada” por el Sr., Gaitis’. Mientras que es aceptado que las opiniones disidentes no tienen efectos legales, y en particular ningún efecto legal parecido a los laudos arbitrales, pueden lograr impactar significativamente a lograr la nulidad y el reconocimiento y ejecución de los laudos arbitrales.
Keywords: Anulación; Arbitral Awards; Dissenting opinions; Laudo arbitral; Recognition and enforcement; Reconocimiento y ejecución; Set aside; Voto salvado

Digitalization, institutions and new venture internationalization - Brieger, Steven A.; Chowdhury, Farzana; Hechavarría, Diana M.; Muralidharan, Etayankara; Pathak, Saurav; Lam, Yan Tong (Journal of International Management, 2022)
This study examines the effect of digitalization on the internationalization of new ventures and further investigates the influence of a home country’s presence of institutional voids and digital infrastructure on the extent of internationalization by new ventures, with the prediction that a home country’s institutional voids and a weak digital infrastructure strengthen the positive relationship between new ventures’ digitalization and internationalization. Applying multilevel modeling on a sample of more than 6000 entrepreneurs from 62 countries the study offers empirical support for these predictions. The findings are robust to alternative specifications. Entrepreneurs using the internet to sell their products and services are more likely to focus on customers in foreign markets when they face institutional voids and a lack of digital infrastructure in their home countries. The study contributes as follows: From a theoretical view, it provides a better understanding of the boundary conditions of the digitalization-new venture internationalization linkage. From a practical perspective, the findings of the study suggest the complementary roles of institutional voids and digital infrastructure at home to help entrepreneurs grow domestically and facilitate their internationalization.

The Limits of Public Contract Law - Casey, Anthony J.; Niblett, Anthony (Law and Contemporary Problems, 2022)
This work received SSHRC funding
Accepted: 2023-06-19T20:16:27Z

Privacy Between Regulation and Technology: GDPR and the Blockchain - Jusić, Asim (IUS LAW Journal, 2022)
Compliance with the GDPR while using blockchain technology for data processing results in compliance issues, due to the fact that the blockchain and the GDPR employ different methods to ensure privacy-by-design and privacy-by-default. The blockchain is built on disintermediation and relative decentralization, whereas the GDPR aims for re-intermediation and relative centralization of the data protection process. This paper provides an overview of and suggestions on how to secure compliance with the GDPR while processing data using the blockchain. A focus is placed on the data protection impact assessment on the blockchain network, issues in identifying and determining the role(s) of sole and joint data controllers and data processors, obstacles to exercising the right to rectification and right to be forgotten when the data is recorded on the blockchain, GDPR data transfer requirements as applied to the blockchain, and the protection of privacy in the process of creating blockchain-based smart contracts.
Keywords: Blockchain; Compliance; GDPR; Privacy

Relationship between International and Domestic Law in the Constitutions of the States of the Economic and Monetary Community of Central Africa - Mairema, Jacqueline (Journal of Law and Criminal Justice, 2022)
The purpose of this paper is to analyze the constitutional provisions relating to the relationship between international law and domestic law of the States of the Economic and Monetary Community of Central Africa reveals an ambivalent conception of the system relationships. This is all the more true since the choice of monism with primacy of international law is affirmed both formally and materially. Even if this variant of monism seems to be tempered by certain constitutional provisions, the treaties have considerable effects in the domestic legal order. Once integrated into the legal order through the modalities of insertion, treaties have a supra-legislative and infra-constitutional rank. However, some constitutions of the States of the Economic and Monetary Community of Central Africa, such as Gabon and Equatorial Guinea, have not enshrined constitutional provisions on the place of treaties in the legal order. The concern to safeguard the supremacy of the constitution and consequently of national sovereignty may justify such a constitutional practice.
Keywords: Droit d’origine externe; Dualism; Insertion; International law; Monism; Monisme; National law; System relationship; Sécurité juridique

Rising from its ruins? The Southern African Development Community (SADC) Tribunal - Shumba, Tapiwa (Law, Democracy and Development, 2022)
The Tribunal of the Southern African Development Community (SADC) was established to ensure adherence to and the proper interpretation of the provisions of the SADC Treaty and its subsidiary instruments, and to adjudicate upon such disputes as might be referred to it. However, since its establishment, it has had a troubled history. After the rulings it made against the Government of Zimbabwe in the landmark Campbell land seizures case, the Tribunal's operations were unceremoniously suspended. This was followed by a process to revise its mandate, one that ultimately condemned it to paralysis and ruin. The new 2014 Protocol on the Tribunal, meant to revise the mandate of the Tribunal to confine it to hearing disputes involving states only, has been criticised as an attempt to undermine the rule of law and human rights in the region. Since the adoption of this 2014 Protocol by the SADC Summit, stakeholders have mobilised regionally to resist its ratification by member states. In particular, lawyers in SADC countries are embarking on legal petitions to reverse the Protocol and promote the revival of the Tribunal in terms of its old mandate. So far, there have been victories in these cases in two influential SADC member states, South Africa and Tanzania. However, it remains important to assess the significance of these developments. As such, the article raises the question: Is the Tribunal rising from its ruins?
Keywords: Regional integration; Rule of law; SADC Tribunal

Reassessing State Consent to Jurisdiction: The Indispensable Third Party Principle before the ICJ - Sparks, Tom (Nordic Journal of International Law, 2022)
Keywords: Adjudication; Advisory opinion; Certain Phosphate Lands; Chagos Archipelago; Consent; East Timor; Indispensable third party principle; International Court of Justice (icj); Jurisdiction; Monetary Gold

A Closer Look at the Doctrine of Separability in Arbitration - Todorović, Ilijana (IUS LAW Journal, 2022)
In the ever-growing business world impacted by globalization, many commercial contracts nowadays contain an arbitration clause. This article focuses on the history behind arbitration as an alternative method of dispute resolution and its penetration to the forefront of mechanisms for resolving commercial disputes -with focus on England, France, and the United States. The article also delves into some of the key questions related to the relationship between an arbitration clause and the underlying contract in which it is contained. And those are the infamous separability and competence-competence doctrines. The author’s conclusion is that the efficiency of an arbitration clause is feasible only if its autonomy is entrenched and safeguarded from preventative and baseless court intervention. In that regard, the author addresses the consequences, current challenges, judicial and academic discourse, and the need for improvement when it comes to these two arbitral principles -all with the goal to provide contracting parties with forethought as to what to consider when drafting their contracts as to avoid unwelcome consequences.
Keywords: Arbitrage; Arbitragem; Arbitration; Competence-Competence; Doctrine; International Arbitration; Issues of Jurisdiction

Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

The Impact of Covid-19 Pandemic on Women In Nigeria - Iheanacho-Shahid, Jennifer (African Journal of Politics and Administrative Studies, 2021)
The paper examines the impact of corona-virus pandemic on women in Nigeria. Emergencies and times of unrest have been linked with increasing reports of Gender Based Violence. Pandemics and Epidemics on the other hand are no exception. The COVID-19 pandemic has been associated with an increase in Gender Based Violence termed the Shadow Pandemic due to the control measures adopted in containing the spread of the virus. The paper adopted the Social Ecological Model to explain and understand the factors that contribute to the increase of Gender Based Violence against women during emergencies or natural disasters and how interaction of individual and environmental factors influence behavior and attitudes that create an atmosphere that encourages violence. The paper was based on secondary sources of data.  The findings of the paper revealed that the lockdown isolated women and attenuated opportunities for them to divulge the abuse or receive necessary support services or resources.  The paper also discovered that there has been an increased rate of reported cases of Gender Based Violence during the months of lockdown in Nigeria. The paper concluded that the corona-virus outbreak has exposed the shadow pandemic of violence and inequality and the exclusion of the Minister of Women Affairs and Social Development is a step in the wrong direction . The paper recommended that it is pertinent to integrate gender lens into disease response and protection mechanism and Gender Based Violence services should be termed as essential duties during crisis and emergencies.

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

Soft Law in International Investment Law and Arbitration - Adinolfi, Giovanna (The Italian Review of International and Comparative Law, 2021)
In the more recent decades, international investment law (“iil”) and arbitration have been going through a process of recalibration prompted by both the intensification of cross-border capital flows and the States’ growing concerns over the potential restraints iil may impose upon the pursuit of public interests. The present contribution will pay attention to a specific feature that can be observed within these developments, i.e. the role played by soft law in investment arbitration and, more generally, under iil, also with a view to assessing the impact on the formation of binding international law of instruments formally devoid of normative force within the international legal order. After an introduction (Section 1), the contribution is articulated into four sections. Section 2 will first define the field of investigation. The case law of investment tribunals and the treaty practice under the more recent iia s will be then explored as to the reliance on soft law instruments for the purposes of settling procedural (Section 3) and substantive issues (Section 4). Some final remarks will close (Section 5).

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Reasonable awareness in compensation for infringement of IP rights - Vanbrabant, Bernard; Glorieux, Dietger (Revue de Droit Intellectuel. L'Ingenieur-Conseil, 2021)

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Combating insolvency and business recovery problems in the oil industry: proposal for improvement in Nigeria's insolvency and bankruptcy legal framework - Olujobi, Olusola Joshua (Heliyon, 2021)
Insolvency and business recovery laws in Nigeria have not evolved to incorporate reorganisation, reforming insolvent oil firms' operations to boost commercial oil firms' steadiness and economic suitability like other moderately developed countries. In Nigeria, liquidation is understood by many as the panacea to indebtedness. The research evaluates the Nigerian insolvency and business recovery legal regime to sustain indebted oil firms from economic shocks due to the global decline in the oil price to avert imminent business failures due to insufficient cash flows. The aim is to fill the gaps in Nigeria's insolvency and business recovery laws by recommending a model for the sustenance of oil firms and to suggest the reform of the gaps identified in the existing laws and the extant literature on the subject. The paper opted for conceptual legal review, comparative legal and policies analyses of solvency and business recovery legislations in Nigeria, Malaysia, India, South Africa, the United Kingdom and the United States. These nations were designated for this study because their insolvency and business recovery legal regime are business rescued driven, not winding up centred. The study is library research-based to address some of the flaws in Nigeria's insolvency and business recovery laws. The study finds that Nigerian legislation on insolvency is flawed in oil firms' salvage, improvement and rearrangement. It ends that, statutory bodies in the designated case study nations are efficient than those in Nigeria due to the strong political will of their governments in supporting insolvent oil firms for successful financial recovery, to safeguard jobs, to protect creditors and to enhance the wealth of their nations through sound business recovery policies and laws. The study, advocates, remodel of Nigeria's insolvency and business recovery legislations and policies in compliance with the international standards on insolvent oil firms salvaged and creditors focused policies for a robust economy. The study concludes with the recommendation for further study to consider quantitative analysis research methodology to project further scholarship on the subject.
Keywords: Creditor; Insolvency and business recovery laws; Nigeria; Oil firms

The Impact of Trade Openness and Foreign Direct Investment on Economic Welfare in sub-Saharan Africa - Adegboye, Folasade Bosede; Adesina, Olumide Sunday; Olokoyo, Felicia Omowunmi; Ojeka, Stephen Aanu; Akinjare, Victoria Abosede (International Journal of Financial Research, 2021)
The sub-Saharan African region is characterized by a high relative degree of openness to trade. The region is also identified with increased inflows of foreign investments with no significant welfare improvement. Economic development emphasizes that the lack of domestic investment in the developing economies could be boosted by trade openness and inflow of Foreign Direct Investment (FDI) for impactful enhancement of capital formation. In this article, the impact of trade openness and foreign capital inflow on economic welfare was examined on a sub-regional analysis for sub-Saharan Africa. The study also appraised the effect of openness to trade and FDI inflow on the region's economic welfare. The data for 30 countries from 2000 to 2018 were collected and analyzed, with the Generalized Least Square (GLS) technique to fit the model developed. The study showed that openness to trade has a significant impact on economic welfare for all sub-Saharan Africa regions, while FDI is only significant for the Western sub-region. Hence, the study recommends that the government of the countries in the sub-Saharan Africa region should boost trade openness to enhance efficiency in productivity, and improve industrial development.
Number: 2
Keywords: Economic Welfare; Foreign direct investment; Sub-Saharan Africa; generalized least square; sub-regional analysis; trade openness

Legal Translaboration for Effective Intercultural Communication - Bell Mandeng, Adrien (Scientific Annals of Alexandru Ioan Cuza University, 2021)
The European-inspired bilingualism and bi-legal system in Cameroon lead to an irregular profile and may be interesting for the European Union (EU) in its quest for preservation of intercultural processes through translation. The Organization for the Harmonization of Business Law in Africa (OHADA) of which Cameroon is part is only affiliated to Civil Law. However, the two legal systems employed in Cameroon (where both Civil Law and Common Law are used) are based on a balance in what concerns the conceptual, epistemic and stylistic representation. Intercultural dysfunction is the consequence of the lack of methodology in legal translation. Collaboration between legal translators and practitioners is key to adopt an agreed-upon model in multilingualism.
Keywords: Culture; History; Intercultural communication; Legal translaboration; OHADA

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

The Contents of the Articles of Association as a Document used in the Creation of Companies in Cameroon under the OHADA Law - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2021)
This study unveils that the creation of companies in Cameroon is been regulated by the OHADA[1], law under the Uniform Act on Commercial Companies and Economic Interest Groups (UACCEIG) which says, every company must have its own Articles of Association [2]. The Articles of Association is a document that contains the internal regulation for the management of the company’s affairs. [3] The articles of association are the contracts between the shareholders and the company and among the shareholders themselves. [4] The questions raised are what are the requirements common in the Articles of Association of all companies under OHADA Law? What effect do the AOA has? The study adopted an analytical approach which has led to the finding that the AOA under OHADA, is similar to the MOA [5] in most English speaking countries, but a major difference in that UACCEIG has limited the life span of the company to 99years while under English company law, a company goes on for an indefinite period. [6] The life span of the company should not be limited due to the principle of perpetual succession. The UACC seem to have concurred with some aspects of the Common Law, making the UACC an applaudable law reform.
Keywords: Articles of association; Cameroon; Commercial companies; Notarised deed; OHADA Law

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.
Copyright © Pamela K. Bookman, Matthew S. Erie 2021. This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence, which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited.

Corporate social responsibility and management of oil related conflict in Host Communities of Niger Delta Region, Nigeria - Gbali, Kenneth Chisom; Weli, Vincent Ezikornwor; Mmom, Prince Chinedu (World Journal of Advanced Research and Reviews, 2021)
The study sought to examine the Corporate Social (CSR) and management of oil related conflicts in Host Communities of the Southern States. Corporate Social Responsibility is the commitment of businesses to contribute to sustainable economic development by working with employees, the local community and the society at large to improve their lives in ways that are good for business and for development. The study was guided by three research objectives, three research questions and three hypotheses. The design adopted for this study is exploratory and descriptive research design and was conducted in Bayelsa, Delta and Rivers State in Nigeria. The population of this study comprised of 15,245,247 residents in Bayelsa, Delta and Rivers State in Nigeria. The instrument for data collection was a set of structured questionnaire. Data derived from the field were analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. And statistical tools such as mean and standard deviation were used to respond to the research questions, while inferential statistical tool of independent sample T-test was used to test the hypotheses at 0.05 level of significance. Findings from the study showed that there is a significant difference in the mean ratings of male and female respondents on the level of relationship between IOC’s and hosts Communities in Niger Delta Region, Nigeria ((P=0.738>0.05), df (400) =. -0.49273, p=0.738); there is a significant difference in the mean ratings of male and female respondents on the on CSR programs carried out by IOCs in hosts Communities in Southern Nigeria (P=.117>0.05), df (400) = -401.618, p=.117); further findings showed that there is a significant difference in the mean ratings of male and female respondents on the Factors causing conflict between oil companies and host communities in Southern, Nigeria (P=0.775>0.05), df (400) =382.256 p=0.775). Based on the findings of the study, it was recommended that host communities should be integrated into the planning process, a paradigm shift from planning for to planning with the host Communities, amongst others.
Keywords: CSR; Corporate Social Responsibility; Host communities; Oil Related Conflict; Oil companies; Southern Nigeria

COVID-19 and Comparative Corporate Governance - Gelter, Martin; Puaschunder, Julia M. (The Journal of Corporation Law, 2021)
With the pandemic caused by the novel coronavirus SARS-CoV-2 raging around the world, many countries’ economies are at a crucial juncture. The COVID-19 external shock to the economy has the potential to affect corporate governance profoundly. This Article explores its possible impact on comparative corporate governance. For an economy to operate successfully, a society must first find a politically sustainable social equilibrium. In many countries, historical crises—such as the Great Depression and World War II—have resulted in a reconfiguration of corporate governance institutions that set the course for generations. While it is not yet clear whether COVID-19 will have a similar effect, it is possible that it will change patterns of what kind of firms are -from an evolutionary perspective- likely to survive, and which ones are not. We argue that to some extent, it will accelerate ongoing trends, whereas in other areas it put corporations on an entirely new course. We observe three trends, namely the need for resilience, a growth of nationalist policies in corporate law, and an increasing orientation toward “stakeholder” interests. First, firms will have to become resilient to the crisis and consequently long-term oriented. Corporations that are not operating merely on an arm’s length capital market basis but are integrated into a network, generated by core shareholders, state ownership, or bank lending may be more likely to survive. In addition, firms are beginning to interact with their workforce differently in their attempts to maintain what could be called “healthy human capital.” Second, we are likely to see a resurgence of nationalism in corporate governance to ensure that foreign ownership and interconnected supply chains do not put national security at risk. Third, the existing critiques of inequality but also climate change awareness will accelerate the trend toward a broadening of corporate purpose toward “stakeholderism” and public policy issues. As in the past years, institutional investors acting as “universal owners” will play a role in shaping this trend.
Keywords: Behavioral; COVID-19; Climate change; Corporate governance; Corporate law; Economic protectionism; Evolutionary theory; Free cash flow; Green New Deal; Human capital; Inequality; Nationalism; Ownership structure; Relational finance; Shareholder primacy; Stakeholder theory; Varieties of capitalism

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

Global Civil Procedure - King, Alyssa S. (SSRN Electronic Journal, 2021)
A “global” civil procedure has emerged and found its way into debates over procedural reform in both international and domestic arenas. Global civil procedure includes the procedural rules, practices, and social understandings that govern transnational litigation and arbitration. A global civil procedure norm is a norm adopted across courts or arbitration providers with the purpose of making that jurisdiction or provider more competitive in attracting transnational litigation or arbitration. Global civil procedure norms are at stake in multiple present trends and debates, including model laws in commercial arbitration, the procedure of international tribunals, the debate over investment dispute resolution, the rise of courts oriented towards international litigation, and sprawling litigation spanning multiple jurisdictions and fora. On a surface level, the values reflected in global civil procedure seem to be roughly the same across jurisdictions. A common language has emerged around competition for litigation business and procedure values such as efficiency, certainty, and impartiality. Yet different legal systems do not necessarily agree on the purpose of various shared elements of global civil procedure. For democracies, for instance, the purpose of procedural reforms might be to facilitate access to justice. Other countries may favor the same reforms because they facilitate top-down administrative control of judges. Surface agreement can submerge divergent logics that may ultimately lead to very different applications of harmonized rules. This Article begins by introducing the concept of global civil procedure, who uses it, and how. Next, it considers several examples of the phenomenon including conflicts of interest rules for adjudicators, aggrega tion, and discovery or disclosure rules. Finally, it considers the limits of global civil procedure. Although the rhetoric of procedural competition can be heard across systems, procedural values do not necessarily translate both in terms of enduring divisions between legal traditions and in terms of applications by current political regimes.

The job security of employees of financially distressed companies - Loubser, Mieka E.; Garbers, Christoph (South African Mercantile Law Journal, 2021)
This contribution considers the legislative regulation of the job security (which boils down to preservation of employment) of employees in case of financial distress of a company. It juxtaposes the legislative regulation of four interrelated processes a company may engage in where it finds itself in financial distress, namely a voluntary internal restructuring (especially retrenchment), the transfer of the business or part of the business, business rescue and winding up. The legislative endeavour to preserve the job security of employees in all these processes is described and analysed. The discussion shows that room exists for companies to circumvent this protection and, to the extent that the protection does apply, that it remains difficult for employees to ultimately challenge the substance of decisions negatively affecting their job security. The main protection for employees in all these processes is procedural in nature and to be found in their rights to be informed of and consulted prior to decisions negatively affecting them. In this regard, business rescue is the most employee-friendly process. Participation in this process by employees, however, requires a fine balance as it may be self-defeating and lead to winding up and the permanent loss of jobs.
Keywords: Business rescue; Dismissal; Insolvency; Job security; Labor laws and legislation; Liquidation; Merger; Operational requirements; Retrenchments; Transfer of a business

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

Double taxation treaty interpretation : lessons from a case down under - Du Plessis, Izelle (Potchefstroom Electronic Law Journal, 2020)
In the Australian case of Bywater Investments Ltd v Commissioner of Taxation; Hua Wang Bank Berhad v Commissioner of Taxation (the Bywater case) the Australian High Court dealt with the question of whether certain companies were resident in Australia for income tax purposes. The majority answered this question by applying Australian domestic law. In a separate but concurring judgement, Gordon J also discussed the interpretation and application of the relevant double taxation treaty. This contribution analyses Gordon J's judgment to extract guidance from it for the South African courts on their interpretation of double taxation treaties. It is submitted that South African courts should also follow the "first step" proposed by Gordon J when interpreting double taxation treaties. South African courts may find Gordon J's judgment "instructive" when dealing with the interpretation of the "place of effective management" concept in both domestic law and double taxation treaties. In his judgment Gordon J favours the goal of common interpretation and it is argued that South African courts should follow this example and explicitly support this notion in applicable cases. From Gordon J's judgment and the judgement in Krok v Commissioner, South African Revenue Service, it is deduced that the positions in South Africa and Australia are similar in that the courts in both countries will be bound by the principles of Articles 31 and 32 of the Vienna Convention on the Law of Treaties when interpreting double taxation treaties. Moreover, Gordon J's judgment indicates that the domestic principles of interpretation should not be used in the interpretation of double taxation treaties. Recent South African cases have suggested that there are no differences between the South African domestic principles of interpretation and those contained in Articles 31 and 32 of the Vienna Convention on the Law of Treaties. This contribution submits that there are many similarities between the two, but that the rules are not exactly the same. South African courts should be aware of these differences and rather apply the rules of public international law, including those contained in the Vienna Convention on the Law of Treaties, when they interpret double taxation treaties. Gordon J specifically identifies the category of the Vienna Convention on the Law of Treaties in which he places the Commentary on the OECD Model Tax Convention, to rely on it for his interpretation of the relevant double taxation treaty. South African courts may well learn from this approach, to create more certainty in the process of interpreting a double taxation treaty.
http://hdl.handle.net/10019.1/124068

Economic Community of West African States at forty-five: a fool at forty-five a fool forever? - Nwosumba, Victor (African Journal of Politics and Administrative Studies, 2020)
Amid COVID-19 pandemic lockdown in the year 2020, Economic Community of West African States hereafter called ECOWAS quietly celebrated its forty-five years of establishment. Widely, much was not heard of or written about the community probably due to the challenges of the pandemic. However, the address of the President of ECOWAS Commission to the staff of ECOWAS institutions on the occasion of the commemoration of the community’s forty-fifth anniversary serves as a reminder that attention should also be given to this regional giant against all odds. Thus, the purpose of this paper is to celebrate ECOWAS at forty-five and then examine whether it is a fool at forty that is proverbially referred to as a fool forever. The paper, through thorough examination of the data collected from secondary sources finds that ECOWAS is still far from achieving its main mandate, its achievements as orchestrated by His Excellency, the President notwithstanding. The paper argues that the postponement of the establishment of ECO, a common currency for the region for the sixth time from 2020 to yet to be announced date, lack of realistic free movement of persons and goods among members and selfish interests of its leaders in the guise of national interest are enough reasons to conceive ECOWAS as a fool at forty-five. With the aid of constructivist theory,it concludes that even if ECOWAS at forty-five is still fooling around it has the chances of not being a fool forever if the leaders should turn a new leaf and pursue the attainment of the community’s mandate before its fiftieth anniversary.

Tax Competition: Global but Virgin under Rwandan Law - Habimana, Pie (Recht in Afrika, 2020)
This paper’s foundation is the global character of (harmful) tax competition. While this phenomenon’s global existence is widely recognised alongside the…

International Commercial Arbitration - Kizi, Boratova Ziyoda Sobir (International Journal of Trend in Scientific Research and Development, 2020)
This article is devoted to the complex analysis of the English legislation of the international commercial arbitration. The author analyzed the commercial disputes and the bodies that proceed these disputes in England as well as main statutes regulating the international commercial arbitrations of England. The international commercial practices of the London International Court of Arbitration are described. Moreover, the author represents the main conclusions formed on the basis of the provisions of the national legislation on commercial arbitration and the regulations of the most well-known international arbitrations in England.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Act 1996; Arbitration institution; Commercial disputes; International commercial arbitration; The LCIA Rules; The London International Court of Arbitration (LCIA)

The intersection of Public Procurement Law and Policy, and International Investment Law - Dagbanja, Dominic Npoanlari (Transnational Corporations Journal, 2020)
There is substantial scholarship on the limitations that international investment agreements (IIAs) place on States’ authority to regulate in the public interest. An area of fundamental importance that has not received scholarly attention in connection with IIAs is public procurement regulation. Given that public procurement is about the needs of States and their citizens, States would want to retain their authority within municipal public procurement laws to decide with whom to contract to meet those needs, and to pursue socioeconomic and industrial policies through procurement. However, most States are parties to IIAs, which impose obligations on them with respect to the protection of foreign investment. This article explores this seminal issue of whether IIAs stand to limit the authority of States in the implementation of procurement legislation and policies. Based on textual analysis and arbitral case study, it argues that treaty-based standards of investment protection can limit States’ authority on the implementation of methods of procurement (such as national competitive tendering or restricted tendering) and socioeconomic policies in procurement. A question that needs fuller engagement is the extent of conflict between specific IIAs and public procurement laws and policies, either regionally or globally, and how to reconcile conflicting obligations to promote foreign investment and sustainable development. This article provides the foundation for such future research.
http://hdl.handle.net/10019.1/124422
Keywords: Foreign (International law); Investments; Methods of procurement; Socioeconomic policies; Sustainable development

Relationship between corporate social responsibility practice and its effects on the botton-line - Tandoh, Isaac; Aovare, Ayishetu (International Journal of Innovation and Scientific Research, 2020)
The study comparatively evaluates the relationship between Corporate Social Responsibility and Profitability in the fuel and gas sectors in Ghana. The descriptive survey design and quantitative methods was adopted to find a relationship between innovations in strategic stakeholder engagement with corporate profitability or bottom-line, with the mediating role of strategic stakeholder engagement leading to a firm’s bottom-line. An analysis of strategic stakeholder engagement and bottom-line of selected fuel and gas companies in the Kumasi Metropolitan, Asokore Mampong, Oforikrom and Ejisu Municipalities was provided.A five point closed ended Likert Scale self-administrable structured questionnaire and researcher guide to aid participants answer relevant questions was used to confirm that innovations in strategic stakeholder engagement fueled increases in corporate bottom-line of selected companies. The four major steps of analysing data collected from Atkinson’s (2002) categories of quantitative data analysis was used, following which the primary data/information gathered and coded was analysed using the Statistical Package for Social Sciences to guarantee validity and reliability of the various investigations conducted. The hierarchical multiple regression of the Baron and Kenny’s (1986) procedure was also adopted to analyse for study the mediating effect of innovation on the relationship between strategic stakeholder engagement and corporate bottom-line.The study opines the involvement of key stakeholder participation in the siting and general operations of fuel and gas companies given the divergent viewpoints of operators and stakeholders (O’Riordan, 2017). A discovery of a statistically significant positive influence of perceptions of CSR towards customers on an organization’s image in general intensifies the suggestion that mangers of fuel and gas sectors take special interest in innovative ways of engaging strategic stakeholders due to its influence and ripple mediating effect on corporate bottom-line to improve the performance of the business or induces increases in profit.
Keywords: Brand; Corporate Social Responsibility; Employees; Image; Perception; Strategic Stakeholder

Transition to the Revised OHADA Law on Accounting and Financial Reporting: Corporate Perceptions of Costs and Benefits - Fossung, Micheal Forzeh; Ntoung, Lious Agbor Tabot; Santos de Oliveira, Helena Maria; Pereira, Cláudia Maria Ferreira; Bastos, Susana Adelina Moreira Carvalho; Pimentel, Liliana Marques (Journal of Risk and Financial Management, 2020)
This paper examines the ongoing transition to the revised Organisation for the Harmonisation of Business Law in Africa Act on Accounting and Financial Reporting for companies in general and to the International Financial Reporting Standards for listed and group companies with a particular focus on recent institutional developments and corporate concerns. The study used 80 professional accountants, most of whom were members of the Institute of Chartered Accountants of Cameroon and academics. Using the descriptive statistics, the study shows that the transition to the revised OHADA brings about a high level of comparability and transparency of the financial statements, that the International Financial Reporting Standards can be implemented in Cameroon (but not fully), and that the benefit of the transition exceeds the cost.
Number: 8
Keywords: Comparability; IFRS; OHADA accounting; perception; transition

The Changing Paradigm of International Tax Dispute Settlement: What Are the Promises and Challenges of Mandatory Arbitration for China? - Ji, Xueliang (Oregon Review of International Law, 2020)
Through comparing dispute resolution methods under bilateral investment treaties (BITs) and bilateral tax treaties, this Article critically discusses the advantages of incorporating mandatory arbitration in bilateral tax treaties and demonstrates that national sovereignty will not be decreased by it. As a result, the Article argues that it would, in fact, be beneficial for China to adopt the mandatory arbitration method, which would further strengthen the global reform initiated by the OECD.
Keywords: China; Dispute resolution; International tax law

An economic and legal analysis of trade measures against illegal, unreported and unregulated fishing - Ma, Xuechan (Marine Policy, 2020)
Illegal, unreported and unregulated (IUU) fishing threatens the ability of the aquatic systems to continue providing vital ecosystem services and essential food resources. Most of the existing economic analysis on IUU fishing is conducted from the perspective of IUU fishing vessels rather than that of States. This paper seeks to fill this gap and concludes that trade measures against IUU fishing are cost-effective for the international community, as the IUU fishing has reached such a substantial scale that the total harm or loss caused is estimated to be greater than the total abatement costs required. Meanwhile, from a legal point of view, trade measures against IUU fishing might have more tensions with international trade law than with the international law of the sea. This paper draws on relevant GATT and WTO jurisprudence for guidance to eliminate such tensions. Two other comprehensive solutions to ensure legal compliance of trade measures against IUU fishing include taking such measures on a cooperative basis and making use of the standard-setting process through competent international organizations or conferences such as the FAO.
Keywords: Economic analysis; IUU fishing; International trade law; The law of the sea; Trade measures

Reimagining the Framework for Resolving Intra-African Commercial Disputes in the Context of the African Continental Free Trade Area Agreement - Onyema, Emilia (World Trade Review, 2020)
This article examines the effectiveness of the framework for the resolution of intra-African cross-border commercial disputes, arising from the projected increase in intra-African trade in goods, services, and investments under the African Continental Free Trade Area. It examines the peculiar nature of intra-African trade and of the participating entities to provide the context to discuss the three major processes adopted in commercial dispute resolution (litigation, mediation, and arbitration) in Africa. It then argues for the promotion of arbitration as the dispute resolution process of choice for such disputes. It reimagined the framework for arbitration at the continental level and made two proposals targeted at the greater efficiency of the process: the designation of Regional Arbitration Centres across the African Union's eight recognized Regional Economic Communities, to administer such references; and the establishment of an African Commercial Court as a one-stop court for the enforcement or annulment of the final award.
Number: 3
Keywords: AfCFTA; Arbitrage; Arbitragem; Arbitration; Commercial dispute; Dispute Resolution; Litigation

The Applicability of Mediation as an Alternative Dispute Resolution Mechanism under OHADA Law - Leinyuy, Kifemmabuh Antonia (Scholars International Journal of Law Crime and Justice, 2020)
Almost 20 years after it adopted the Uniform Act on Arbitration, OHADA revised its Uniform Act on Arbitration and adopted a new Uniform Act on Mediation along with the fresh set of arbitration rules of the Common Court of Justice and Arbitration in Abidjan. These three texts were revised with the assistance of consultants. Among other changes, with the 2018 Uniform Act on Mediation, a solid platform for the use of mediation in the region is now in place. The ability of mediators to carry out their adjudication function with judicial intervention remains a major challenge by parties under the OHADA zones. In this light, the worry which this article seeks to uncover is how the new mediation law is applicable and facilitates the amicable settlement of investment disputes. The article also highlights the legal basis regulating the mediation process as a whole. In attaining these objectives, we employ doctrinal research methodology. The article conclude with vigorous recommendations which if effectively implemented will go a long way to enhance business (investment) security.
OpenAlex: https://openalex.org/W3035045968
Keywords: ADR; Alternative dispute resolution; Applicability; Dispute resolution mechanism; MARD; Mediación; Mediation; Mediação; Médiation; OHADA Uniform Act

The African Continental Free Trade Area: Toward a New Legal Model for Trade and Development - Kuhlmann, Katrin; Agutu, Akinyi Lisa (Georgetown Journal of International Law, 2020)
International trade law is at a turning point, and the rules as we know them are being broken, rewritten, and reshaped at all levels. At the same time that institutions like the World Trade Organization (WTO) face significant change and a global pandemic challenges the rules of the market, Africa’s new mega-regional trade agreement, the African Continental Free Trade Area (AfCFTA), is emerging as a promising framework for redesigning international economic law. As this Article will argue, the AfCFTA presents a new normative approach to trade and development that is positioned to rewrite the rules in a more inclusive and equitable way and, over time, possibly affect global trade well beyond the African continent.Historically, trade and development have been linked through the framework of Special and Differential Treatment (S&D), which has been a central feature of the WTO and is increasingly shaping regional trade agreements (RTAs) as well. Although the connection between trade and development is more important than ever before, traditional S&D is not positioned to deliver on broader priorities of social and economic development in the current international climate. Fortunately, as this Article will argue, Africa’s approach under the new AfCFTA sets the stage for a needed refresh of S&D. While the AfCFTA incorporates traditional aspects of S&D, it also includes elements of a forward-looking, rules-based approach to further economic and social development, advancing the Sustainable Development Goals (SDGs). This new dimension of S&D holds great potential for promoting integration through trade, representing the needs of a diverse group of countries in the rulemaking process, and reshaping international economic law more broadly to generate positive development outcomes. This Article begins with an assessment of the AfCFTA as an alternative model for trade and development law, evaluating the agreement in the historical and evolving context of S&D and examining its role in shaping a new normative approach to S&D. The AfCFTA, we argue, represents a shift from using S&D as a largely defensive trade approach to one that positions S&D as an affirmative tool for achieving sustainable development through the design and implementation of the rules of trade themselves, while still maintaining flexibility for countries that need it. This new approach may finally replace the old trade paradigm of the ”haves and have nots” with a system in which trade rules can be designed to benefit all. Although the AfCFTA is still at an early stage and will have to overcome formidable challenges, this Article provides an initial assessment of the AfCFTA’s proactive new model in the context of the substantive areas of law identified as next-stage (Phase II) negotiating priorities: intellectual property rights (IPR), investment, and competition law. The Article’s comparative assessment draws upon the laws of African nations, African and international RTAs, and other proposals for international legal reform. Finally, the Article looks to the future, positing that the AfCFTA could be the best legal instrument available to break the stalemate in international rulemaking, design new trade law approaches to pressing issues like global health and food security, and close the loop between trade rules and development goals, including the seventeen SDGs. As the AfCFTA is rolled out and implemented, it could have a profound impact on trade and development law, reshaping the rules for Africa and perhaps the world as well.
Keywords: AfCFTA; African Continental Free Trade Area; International Economic Law; International Trade

Trade in Services in the African Continental Free Trade Area: Prospects, Challenges and WTO Compatibility - Simo, Regis Yann (Journal of International Economic Law, 2020)
This article engages with the recently adopted agreement for the African Continental Free Trade Area (AfCFTA) in the area of services. While services trade had heretofore stood at the queue of African trade pacts, the AfCFTA breaks new grounds by negotiating goods and services concurrently, signalling a paradigm shift and a commitment to a deeper integration of the continent. Upon Members’ implementation of the Protocol on Trade in Services, whose aim is to establish a single market in services, the region will be the largest economic integration agreement ever concluded since the birth of the World Trade Organization (WTO). This paper sets out to analyse the provisions of the Protocol and how they contribute to achieving the objective of attaining a single market where services (alongside goods, people and capital) move unrestricted.

The Opportunity for Convergence of SYSCOHADA towards IFRS Standards: An Effect of Coercitive and Mimetic Isomorphism - Souleymanou, Kadouamaï; Mouafo, Cédrick Nzokouo (Journal of Modern Accounting and Auditing, 2020)
The last few years have been marked by the increase in power of IFRS international accounting standards. From the full or partial adoption to the gradual convergence, many countries have displayed a strong preference for these standards. Meanwhile, the implementation of International Financial Reporting Standards (IFRS standard) in the context of developing countries is not trivial. We are witnessing an unprecedented clash between the authors who support the interest of these standards for developing countries, and those who conversely demonstrate that these norms are not well adapted to the context of those countries. Falling within this problematic, this thesis analyses the issues and determinants of the convergence of the Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) accounting system towards IFRS international accounting standards in view of the reforms introduced by the last revision. From a sample of 10 companies, among which two local firms, two international firms, three publicly traded companies, and three not listed other companies, we show that the current convergence towards international accounting standards follows an effect of coercitive and mimetic isomorphism. In so doing, the timely implementation of these standards in the context of Cameroon is contingent with a number of structural and environmental factors that call their pertinence into question.
Keywords: Convergence; Developing countries; IFRS; SYSCOHADA; Système Comptable OHADA

The Standards for Proving Damages and Its Amount: A Comparative Study under Transnational Instruments and International Arbitration Awards - Shoarian, Ebrahim; Sahebjam, Sara (Public Law Researsh, 2020)
Defining the applicable standards for proving and measurement of damages constitute one of the most significant issues under the law of damages. In principle, an aggrieved party, who claims compensation for damages based on contractual liability is responsible for showing the existence and the amount of losses suffered or to be suffered. Due to great importance of the issue, transnational instruments of contract law, such as UNIDROIT Principles of International Commercial Contracts (UPICC), Principles of European Contract Law (PECL) and Draft Common Frame of Reference (DCFR) have set out, explicitly or implicitly, special standards such as reasonable certainty, reasonably likely to occur and so on for proving damages; By contrast, the Iranian laws and regulations including the Civil Code do not set out such standards. The legal scholarship and jurisprudence have also failed to address the issue. Therefore, a comparative study of the issue with particular look at international instruments and arbitral awards could provide a reliable source of guidance. This paper analyzes the general and specific standards for proving damages and those situations that fall outside of ambit of the standards such as late payment damages. By doing so, the paper tries to open the debate in Iranian law. یکی از موضوعات قابل توجه در حوزه حقوق خسارت، تعیین استانداردهای قابل اعمال برای اثبات خسارات و میزان آنها است. علی القاعده، زیان‌دیدهای که به استناد مسئولیت قراردادی برای مطالبه خسارت اقامه دعوی میکند، بایستی اصل و میزان خسارتی را که متحمل شده یا خواهد شد، به اثبات برساند. نظر به اهمیت موضوع، اسناد فراملی مربوط به حقوق قراردادها از جمله اصول قراردادهای تجاری بینالمللی، اصول حقوق قراردادهای اروپا و پیشنویس طرح مشترک مرجع، به صورت صریح یا ضمنی، استانداردهای مشخصی مانند قطعیت متعارف، وقوع محتمل متعارف و غیره را برای اثبات خسارت پیشبینی کردهاند. در مقابل، مقررات موضوعه ایران از جمله قانون مدنی؛ چنین استانداردهایی را تنظیم ننموده و موضوع نیز مورد بررسی حقوقدانان و رویه قضایی قرار نگرفته است. بنابراین، مطالعه تطبیقی موضوع با نگاهی ویژه بر اسناد بینالمللی و آرای داوری می‌تواند منبع قابل اتکایی برای طرح بحث باشد. این مقاله، استانداردهای عام و خاص اثبات اصل خسارت و میزان آن و نیز مواردی مثل خسارت تأخیر تأدیه را که خارج از قلمرو شمول این استانداردها هستند، مورد تحلیل قرار میدهد و در نهایت تلاش دارد تا باب بحث را در حقوق ایران بگشاید.
Keywords: Arbitral Awards; Reasonable Certainty; Reasonably Likely to Occur; Standard for Proving Damages; Transnational Instruments; آرای داوری; استاندارد اثبات خسارت; اسناد فراملی; قطعیت متعارف; وقوع محتمل متعارف

Fall of Last Safeguard in Global Dejudicialization: The Problem of Protecting Public Policy in Private Business Disputes - Ghodoosi, Farshad (Oregon Review of International Law, 2020)
The importance of courts is shrinking. This is largely due to global dejudicialization: the process of outsourcing disputes to private dispute resolution. In the last several decades, along with the triumph of neoliberalism, privatization of the resolution of disputes has become the gospel of modern judiciaries. Courts have been pushed to the tail end of the private adjudication process and are used only as the last resort. The courts’ warm embrace of this structure along with practitioners’ push has led to a staggering expansion of private dispute resolution. The world therefore has witnessed an unprecedented growth of arbitration—the primary mode of private dispute resolution.
Keywords: Business law; Dejudicialization; Dispute resolution; Déjudiciarisation; Privatization; Public policy

The OHADA Structure as a Possible Model for the Development of a Commercial Law Structure in the Southern African Development Community (SADC) - Leno, Ngaundje Doris (International Journal of Social Sciences and Management Review, 2020)
The Southern African Development Community's (SADC) colonial legacy which introduced foreign legal traditions and the consequences of the diversity heighten the urgency for unified commercial legislation to deal with cross-border disputes.Thus, the issue is whether the Organisation for the Harmonisation of Business Law in Africa (OHADA) structure can serve as a possible model for the development of a uniform commercial law structure in the SADC .Despite the success of the OHADA, the author submits that the OHADA can only serve as a source of inspiration, or roadmap, providing guidance to the SADC drafters.The paper aims at demonstrating that the OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC.The significance of this paper lies in the contributions it makes to the development of a commercial law structure in the SADC.
OpenAlex: https://openalex.org/W3124748692
Keywords: Development; Integration; Model; OHADA; SADC

Chinese Investment in Ethiopia: Contribution, Challenges, Opportunities and Policy Recommendations - Gebrehiwot, Berihu Assefa; Gebreeyesus, Mulu; Weldesilassie, Alebel Bayrau (PSI Research Report, 2020)
Recognizing the immense potential for greater Chinese investment promotion and its contribution to Ethiopia’s industrialization and acknowledging the gaps, this paper aims to conduct a rigorous research through analysis of secondary sources and qualitative survey of Chinese enterprise doing business in Ethiopia in various sectors. In this regard, the key policy questions that this study tries to answer are ‘the involvement in and the contribution to Ethiopia’s industrialization and the challenges and opportunities they face. Hence, the overall objective of this research will be to (i) assess the trends in Chinese enterprises involvement in Ethiopia’s industrialization for the last decade, (ii) inform both the Chinese government and Ethiopian government on key business barriers and market failures that are constraining Chinese business entry and growth in Ethiopia; (iii) investigate the immense untapped investment potential from China that can be attracted and opportunities that Ethiopia could offer to Chinese investors; and (iv) propose policy options on how to address the challenges and thereby maximize the opportunities to enhance Chinese investment towards Ethiopia’s industrialization.

Political business cycles, bank pricing behaviour and financial inclusion in Africa - Iddrisu, Abdul Ganiyu; Turkson, Festus Ebo (Cogent Economics & Finance, 2020)
This paper analyses financial inclusion in Africa focusing on the role of political business cycles and pricing behaviour of banks. We employ a sample of 330 banks operating in 29 African countries to test for two related hypotheses. Panel fixed and random effects were estimated for the period 2002 to 2013. The regression results that ensued suggests first that loan price increases in pre-election and election years. Building on this result and employing various specifications of financial inclusion, the second results suggest that, high bank loan prices in election years tend to increase financial access more, compared to non-election years, and that, high deposit price reduces financial usage but increases financial access in election years, compared to non-election years. By extension, these results have important policy implications for policymakers.
Publisher: Abingdon: Taylor & Francis https://www.econstor.eu/handle/10419/245317
Keywords: Africa; Banks' pricing behaviour; Election; Financial inclusion; Political business cycles

Protection of Intellectual Property Rights in International Trade - Indradewi, Anak Agung Sagung Ngurah (International Journal of Social Sciences, 2020)
That intellectual property is the creation of ideas in the form of new discoveries, literary works, and works of art, symbols, names and images used in trade. Of course, intellectual property is closely related to the world of commerce because its emergence is triggered by the desires of the members of the World Intellectual Property Organization who want to protect their economies in the era of free trade. In this case how the form of protection of intellectual property rights in the perspective of international trade, it can be seen that basically the laws and or regulations in every country in the world are different and each country has the right to implement its own legal rules in the jurisdiction of their country.
Keywords: Intellectual property; Intellectual property rights; International Trade; Legal rules

IFRS compliance, corporate governance and financial reporting quality of GSE-listed nonfinancial firms - Mbir, Deborah Esi Gyanba; Agyemang, Otuo Serebour; Tackie, George; Abeka, Mac Junior (Cogent Business & Management, 2020)
The adoption of International financial reporting standards (IFRS) has been presented in several empirical literature as a factor that could improve the quality of financial reports. However, Ghana has not attained the desired levels of financial reporting quality after the adoption of IFRS. Literature reveals that lack of proper enforcement of these high-quality standards may result in limited compliance and will undermine the effectiveness of these standards in terms of attaining high-quality financial reports. This study therefore argues that the relationship between IFRS compliance and reporting quality revolves around some enforcement mechanisms like corporate governance structures. In view of that, by using random effect estimation technique, this study examined the role of corporate governance in the relationship between IFRS compliance and the reporting quality of firms listed on the Ghana Stock Exchange (GSE). The study found that the right corporate governance mechanisms will enhance the positive effect of IFRS compliance on reporting quality. This study further recommends that to gain an appreciable level of public confidence in the annual reports of firms listed on the GSE, the audit committee’s independence and the board’s independence should be strengthened to ensure that management does not only adopt IFRS, but that the standards are actually complied with.
Keywords: Compliance; Corporate governance; IFRS; Reporting quality

The Effect of IFRS Adoption on Foreign Direct Investment in Africa - Musah, Alhassan; Adjei, Eunice; Ahmed, Ibrahim Anyass (Journal of Applied Accounting and Taxation, 2020)
Adoption of International Financial Reporting Standards (IFRS) is supposed to help enhance comparability of financial statement, improve the quality of financial reporting and accounting information of businesses in a country. This is expected to help improve Foreign Direct Investment (FDI) in the adopting countries. This study examined the effect of IFRS adoption on FDI inflows in Africa. Unlike previous studies that sample both adopting and non-adopting countries, this study sampled only Africa countries that have adopted IFRS to determine whether the adoption has improved FDI inflows. To achieve this objective, 20 African countries that have adopted IFRS were sampled covering a period 1980 to 2015. Data was sourced from The World Bank financial and Economic Data. Control variables such as GDP growth, openness of the economy, government debt and population growth were included in the model. The correlation and regression analysis showed that IFRS adoption has a positive and significant influence on FDI inflows in Africa. On the other hand, open economy, government debt and population growth had a positive and significant association with FDI. Overall, the results show that African countries that want to improve FDI inflows must improve the quality of their reporting environment by adopting IFRS.
Keywords: Africa; FDI; Foreign direct investment; IFRS; IFRS adoption; Investments; Macroeconomic variables

Arbitration related lessons: Insights from the supreme courts around the world - Nigmatullina, Dilyara; Vanlerberghe, Beatrix (b-Arbitra : Belgisch tijdschrift voor arbitrage, 2020)
In international arbitration, arbitrators have procedural powers that allow them to manage and conduct the arbitration proceedings in a fair and efficient manner. These powers are typically set out in the arbitration rules that the parties have agreed to, such as the International Chamber of Commerce (ICC) rules or the United Nations Commission on International Trade Law (UNCITRAL) rules. Arbitrators have the authority to determine the procedure to be followed in the arbitration, including the admissibility, relevance, materiality, and weight of the evidence presented. They can also decide on the language to be used in the arbitration and the location of the hearings. In addition, arbitrators can issue orders and directions as needed to ensure the fair and efficient conduct of the proceedings. This may include ordering the production of documents or witness testimony, or setting time limits for the submission of evidence. The present paper critically examines the lex arbitri, the law that governs the arbitral proceedings, and makes out a case that lex arbitri cannot be challenged in court, as the parties to the arbitration have agreed to resolve their disputes through arbitration rather than through the courts. However, if the tribunal exceeds its powers or acts in a manner that is inconsistent with the lex arbitri, the parties may have grounds to challenge the tribunal's decision on the grounds of lack of jurisdiction or due process. The paper summarises some key judgments in which Courts have upheld or quashed the Tribunals procedural orders. It will be concluded that the procedural powers of arbitrators in international arbitration are real and not perfunctory, though bounded within powers extended by Parties to the arbitral tribunal.
Place: Brussel
Keywords: Arbitrage; Arbitragem; Arbitration

The Trajectory of Illicit Waste Trade in Africa: Implications for Human Rights and Sustainable Development - Umenze, Nnamdi Stanislaus (Journal of Law, Society and Development, 2020)
As globalisation intensifies, the environmental burden of economic development is being shifted to poor countries. This development manifests in waste trade involving the transboundary shipment of toxic waste from developed to developing countries. This article evaluates the strategies with which waste trade is being perpetuated to the detriment of sustainable development and human rights values in Sub-Sahara Africa. It argues that capitalism has influenced massive generation and commodification of waste, especially in industrialised countries. It has also established that globalisation has made the transboundary shipment of waste easy. Moreover, foreign investments in the waste industry in developing countries appear to be a means by developed countries to perpetuate waste shipment to developing countries, which helps waste traders to avoid stringent regulations and high costs of waste management in developed countries. Therefore, such investments in developing countries should not always be viewed as a breakthrough in attracting foreign investments. The findings made include that despite the existence of the Basel and Bamako Conventions at global and regional levels, respectively, waste trade has continued in different forms in Africa, where waste merchants exploit the low-cost facilities, cheap labour and weak regulatory frameworks. The trend includes the reckless dumping of hazardous industrial waste, electronic waste as well as ostensible investment in “dirty industries” in some African countries. It concludes by urging the states to individually establish robust mechanisms that protect the environment and enforce environmental rights. These measures will help complement the collective efforts they have made in multilateral and regional agreements.
Keywords: Africa; electronic waste; globalisation; human rights; sustainable development; toxic waste trade

The Recovery of Debts Inherent in Cheques without Cover in Cameroon via the OHADA Simplified Recovery Procedure and Enforcement Measures - Penda, Akama Samuel; Ndikum, Nji Keneth (International Journal of Trend in Scientific Research and Development, 2019)
The vast number of commercial transactions that take place daily in the modern business world will be inconceivable without negotiable instruments like cheques. This is the reason why the recovery of debts inherent in cheques without cover has been given the attention it deserves within the CEMAC Region under the OHADA Uniform Act on Business Law. The OHADA Uniform Act on Simplified Recovery Procedure and Enforcement Measures has instituted a procedure in the member states of the OHADA zone to recover debts of a company when it eventually goes bankrupt or when it winds up. It should however be understood that all the member states of CEMAC are OHADA signatories. This ipso facto means that Cameroon being a member of CEMAC, with its bi jural nature, where the Common Law and Civil law legal systems operates in the Former West Cameroon and Former East Cameroon respectively, both parts of the country are bound to implement the OHADA Uniform Act in their various jurisdictions. The Uniform Act on Simplified Recovery Procedures and Enforcement Measures was issued on the 10th of April 1998. Like the Uniform Act on Securities, this Act overlaps the bound of pure business law in that it effects a general reform of civil procedure in relation to recovery and enforcement. The reform was indispensable of the OHADA Member States, only Mali had, in 1994, put in place a modern system that was suited to present day economic and social conditions. Otherwise, the relevant legislation dated, at best from the 1970s and in several cases from colonial times. The OHADA Uniform Act governs commercial companies and Economic Interest groups. Since banks are commercial companies governed under Public Limited Companies S. As , they are equally governed by the OHADA Uniform Act. Thus, this paper questions the potentials of the OHADA Simplified Recovery Procedure and Enforcement Measures in relation to the special mechanisms for the Recovery of Debts inherent in cheques without cover in Cameroon.
Keywords: Chèques; Procédure simplifiée; Recouvrement de créances; Recovery of Debts; Voies d'exécution

Personal Property Security Law: International Ambitions and Local Realities - Castellano, Giuliano; Tosato, Andrea (International Business Law, 2019)
Personal property security law is a key element of “access to credit” and “financial inclusion”. The prevailing view is that a legal framework enabling the effective use of personal property as collateral markedly benefits both lenders and borrowers. Lenders can offer financing at a lower cost thanks to reduced credit risk; borrowers can access funding by leveraging the otherwise unavailable value of the assets integral to their operations. Over the past century, the priorities of personal property security law have evolved fundamentally. As small and medium-sized enterprises (SMEs) and individual entrepreneurs have become the growth engine of both developed and developing economies, legislators have grown sensitive to the financing needs of these entities. In parallel, the advent of the information society has demanded that lawmakers address squarely the rules governing the use as collateral of intangibles such as “receivables”, “intermediated securities”, “non-intermediated securities”, and “intellectual property rights”, rather than confine their gaze to tangibles such as industrial machinery, mobile equipment and inventory. Concurrently, the increasingly transnational nature of both economic development policies and commercial activity have engendered the need for global principles and standards for asset-based lending. To address these novel priorities and promote a healthy and vibrant credit ecosystem, international and regional organizations have undertaken projects aimed at modernizing and harmonizing personal property security law. Over time, these efforts have yielded a panoply of legal instruments. Binding conventions have been adopted to unify the rules of discrete facets of personal property security law, while soft-law texts, such as model laws and legislative guides, have been formulated to supply comprehensive legal templates to lawmakers keen to revise their domestic legal regimes. Nevertheless, states have struggled to assimilate these international efforts into their domestic legal systems. Common law jurisdictions have been loath to abandon the familiarity and safety of the path paved by centuries of case law; in similar vein, civil law jurisdictions have resisted inducements to renovate the normative infrastructure erected by the codifications of the 19th century. This Chapter explores the tension between international ambitions and local realities, with a special focus on the issues encountered in civil law jurisdictions. To this end, the case of Italy is examined as a living experiment in comparative personal property security law. In this jurisdiction, the recent enactment of a non-possessory security device, absent a comprehensive reform of the country’s civil code affords important lessons for any civil law system which might be pondering personal property security law reforms. More profoundly, it epitomizes the gap that separates the aspirations of international legal instruments from their effective implementation in domestic contexts. This analysis is divided into two parts. The first reviews international and regional legal initiatives that have shaped the personal property law landscape and then identifies a set of core tenets shared among them. In the second part, attention shifts to Italy, scrutinizing both the personal property security legal edifice originally constructed in this jurisdiction and the attempts to overhaul it that have taken place over the past three decades. This is followed by a critical appraisal of the current state of the law, by reference to the aforementioned core tenets of personal property law reform.
Keywords: Commercial Law; Law Reform; Non-possessory Pledge; Personal Property Security Law; Secured transactions

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
OpenAlex: https://openalex.org/W2998516176
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Multidimensionality of Sustainable Public Procurement (SPP) - exploring concepts and effects in Sub-Saharan Africa and Europe - Stoffel, Tim; Cravero, Carol; La Chimia, Annamaria; Quinot, Geo (Sustainability, 2019)
Strategic objectives in public procurement, such as environmental or social considerations, are being increasingly referred to under the umbrella term of sustainable public procurement (SPP). The concept of sustainability is intrinsically multidimensional, encompassing environmental, social, and economic aspects. However, the existing literature on SPP highlights the generalization that the regulation and practices of public procurement are biased toward the environmental dimension. There is conflicting evidence from countries in Sub-Saharan Africa (SSA) that calls for further investigation. Analyzing how SPP is actually constituted in SSA and contrasting it with the situation in the European Union (EU), as a spotlight on the Global South and North, contributes to a better understanding of sustainability in public procurement. The comparative analysis will help with understanding processes related to the integration or disintegration of sustainability dimensions in SPP. Our results indicate a contrary orientation on the environmental and the social dimensions in the EU and SSA. Although there is no sign of a comprehensive integration of all dimensions in SPP, there are developments toward the integration of the ‘missing’ dimension in the respective regional setting. Thus, at the moment, achieving a multidimensional implementation of SPP appears to be more a matter of expanding SPP practices of the ‘missing’ dimension than of pushing for integrated concepts.
http://hdl.handle.net/10019.1/124395
Keywords: GPP; Government purchasing; Green public procurement; Multidimensional sustainability; SRPP; Socially responsible public procurement; Socioecological transformation; Sustainable development; Sustainable supply chains

The Influence of IAS/IFRS on the New OHADA General Chart of Accounts - Tchokoté, Ivan Djossa (Journal of Modern Accounting and Auditing, 2019)
Accounting standardization in black African French-speaking countries is presented through two streams of research. The first stream presents the general chart of accounts common to all these countries as an accounting model which reconciles the divergences between the Anglo-Saxon and continental approaches to accounting, and thereby satisfies the requirements of users of accounting information. The second stream considers that the convergence towards IAS/IFRS is a vital way of attracting international investors and increasing development. This article stands by the second perspective and analyzes the changes introduced in the PCG-OHADA (2017) compared to the PCG-OHADA (2000). It shows that the new provisions of the PCG-OHADA are mainly inspired by IAS 1, IAS 16, IAS 19, IAS 36, IAS 38, IAS 40, and IFRS 6.
Keywords: Accounting harmonization; Accounting standards; IFRS; PCG

Problems of Enforcement of ICSID Awards: An Analysis of Micula Case - Hasankhani, Ali (Public Law Researsh, 2019)
In the case Micula A.O. v. Romania, the arbitration tribunal established under the auspices of the International Center for Settlement of Investment Disputes (ICSID) sentenced Romania to pay a compensation for the revocation of investment incentives and for the breach of fair and equitable treatment principle that had been laid down in a bilateral investment treaty between Sweden and Romania. Considering investment incentives as a breach of the EU regulations regarding state aids, the European Commission then rendered a directive, prohibiting the enforcement of the arbitration award by the member states. As articles 53 and 54 of ICSID emphasize that the awards are binding, the EU Commission’s act of rendering the aforementioned directive, and the member states refusal to comply with the award equals to giving the EU law primacy over international law, which should be considered as a breach of their international obligations. Using a descriptive-analytical method, this article seeks to explain the viewpoints of the parties and the courts which were asked to enforce the award, as well as to determine the nature of their acts.

Block Chain Accounting: The Face of Accounting and Auditing in Industry 4.0 - Antoney, Laly; Augusthy, Theresa Josephine (International Multilingual Journal of Science and Technology, 2019)
Keywords: Accounting Education; Block Chain Accounting; DLT; Future Audit; Tripple Entry Book Keeping

Causes of Delay in the Resolution of Commercial Disputes via Litigation Arbitration as a Way out within OHADA Laws - Sigala, Buma Roland (International Journal of Trend in Scientific Research and Development, 2019)
An essential requirement of justice is that it should be dispensed as quickly as possible. It is a well-known adage that, « justice delayed is justice denied». Delay in litigation is caused by a number of factors. For example in litigation the parties have the right to make a counterclaim, right to make appeal etc. Arbitration has been able to overcome the factors which cause delay in litigation because in arbitration, parties are given the right to exclude the possibility to make a counterclaim, the right to make appeal has expressly been prohibited by the Organization for the Harmonization of Business Laws in Africa (OHADA)1 legislator etc. But since the OHADA legislator has not expressly prohibited counter claim in arbitration, it is recommended that counterclaim should be expressly prohibited in arbitration as it is the case with appeal. This article aims at identifying the causes of delay in the disposal of commercial disputes via litigation and how these causes of delay have been combated in arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; Delay commercial; Disputes Litigation; Law and management

Electronic Tax System As A Panacea For Tax Revenue Leakages In Nigeria - Nwamgbebu, Obinna; Oketa, Chiamake; Odom, Amarachi; Nwambe, Cynthia; Nweke–Charles, Uchenna (African Journal of Politics and Administrative Studies, 2019)
The broad objective of the study is to assess the problems of the traditional tax system in Nigeria and establish electronic taxation as a solution to these problems. The study adopted content analysis in analyzing text books, journals, newspapers and other essential materials that were used to obtain the needed information for the study. Extensive review of the literature showed that electronic tax system solves the problem of low tax collection, unavailability of tax statistics and poor record keeping, complex of payment and high cost of tax compliance. The implication of these findings is that an adoption of electronic tax system is an intelligent means of achieving a system of tax administration that allows for the collection and accountability of required taxes at a minimum cost. The study concluded that there are some challenges with the manual system of administering taxes and that modern technology could simplify these challenges and alienate them in the form e-tax. The study therefore recommended that government should support with everything on their disposal the establishment of e-tax administration so as to start ripping the benefit of high rate of compliance among taxpayers at all levels of government in Nigeria.

What the African Continental Free Trade Agreement Protocol on Dispute Settlement says about the culture of African States to Dispute Resolution - Akinkugbe, Olabisi (Articles, Book Chapters, & Popular Press, 2019)
An effective Dispute Settlement Mechanisms (DSM) upholds a rules-based trade regime; enunciates, clarifies and develops the jurisprudence of its constituent trade agreement; and also ensures predictability in the trading regime. Article 20 of the African Continental Free Trade Agreement (AfCFTA) establishes the DSM. The AfCFTA Protocol on Dispute Settlement (“Dispute Protocol”) provides for the rules and procedures for the settlement of disputes. Unlike the majority of the African regional economic community courts that are modelled after the Court of Justice of the European Union, the AfCFTA-DSM follows a handful of other regional judicial bodies – such as the Southern African Community Development Community (SADC) and the Tripartite Free Trade Area Agreement (TFTA) – that are modelled after the World Trade Organization (WTO) dispute settlement mechanism.
Keywords: AfCFTA; Dispute Settlement Mechanisms; Free Trade; Trade Agreement

The Development of Mortgage Finance in Nigeria and its Impact on the Economy - Siyan, Peter; Adegoriola, Adewale E; Erivwode, Ovosa Mercy (International Multilingual Journal of Science and Technology, 2019)
This study examines the development of mortgage finance in Nigeria and its impact on economic growth. Aggregate housing finance data for by both banks and non-financial institutions was used to measure housing finance. Other variables considered include financial debt proxy by M2Per capita, financial instability proxy Interest rate and the level of development of the capital market measured by market capitalization. Time series data covering the period 1990-2016 was obtained from Central Bank statistical bulletin, National Bureau of Statistic and World Bank. The methodology adopted in the study is Vector Autoregressive Model (VAR) was estimated using linear regression method. The results of the analysis indicated that there is a one-way causal link runs from mortgage finance to economic growth. In addition, mortgage finance was found to be a significant determinant of increasing pattern of economic growth over a long period of time. Due to the level of the country’s financial depth, it was recommended that Nigerian government should intensify effort aimed at consolidating the level of financial re-structuring in the non-financial sector which mortgage financing belong. The central bank should make a policy stipulating commercial banks to set aside certain proportion of their total assets to finance housing demands.
Keywords: Economic growth; Hypothèque; Mortgage Finance; Vector Autoregressive

May an employer dismiss an employee if the disciplinary chair imposed a lesser sanction? South African Revenue Service v Commission for Conciliation Mediation and Arbitration 2017 38 ILJ 97 (CC) - Calitz, Karin Beatrix (Stellenbosch Law Review, 2019)
In South African Revenue Services v Commission for Conciliation, Mediation & Arbitration, Kruger, the employee, called his superior a “kaffir” on more than one occasion. The employer unilaterally dismissed the employee after the chairperson of the disciplinary hearing had imposed a lesser sanction. In doing so, the employer disregarded the collective agreement which did not make provision for the sanction of the disciplinary chair to be substituted. The employee claimed that his dismissal was invalid and therefore unfair. The Commission for Conciliation Mediation and Arbitration (“CCMA”), Labour Court and Labour Appeal Court (“LAC”) agreed. However, in the Constitutional Court (“CC”) the employer no longer argued that it was entitled to substitute the sanction in the light of the breach in the trust relationship, but only alleged that reinstatement was a remedy that no reasonable decision-maker would order. The CC agreed and held that the dismissal was substantively fair but procedurally unfair. The CC did not answer questions of lawfulness, fairness and invalidity, but in Steenkamp v Edcon the CC held that employees claiming remedies for unfair dismissal in terms of the Labour Relations Act 66 of 1995 (“LRA”) should not rely on invalidity. However, employees still have the right to common-law remedies based on their employment contract. Considering the importance of collective agreements, negotiated disciplinary codes, certainty and consistency, and to avoid employers exercising unfettered power over employees, state organs should apply for a review of an unsatisfactory sanction by the disciplinary chairperson in terms of section 158(1)(h) of the LRA. Private employers could negotiate a disciplinary code which allows both the employer and employee to appeal against the decision of the disciplinary chair which should make provision that a more severe sanction can be imposed on appeal.
http://hdl.handle.net/10019.1/124100
Keywords: Arbitrage; Arbitragem; Arbitration; Commission for Conciliation; Dismissal of employees; Labor discipline; MARD; Mediación; Mediation; Mediação; Médiation; South Africa; South African Revenue Services

A Critical Look at the Mechanism for Challenge of Arbitrators Under ICSID Convention and Arbitration Rules - Gautama, Ivan (Juris Gentium Law Review, 2019)
Administered arbitrations under ICSID are amongst the most-utilized means to resolve investor-state disputes. Part of why it is so is because the ICSID as an institution is heavily affiliated with the World Bank. This affiliation serves as a double-edged sword in ICSID’s hands: while on one side such affiliation lends ICSID the credibility any successful arbitral institutions need, on the other side ties between the two institutions are proving to become too close for comfort. This paper explores what could go and has gone wrong in the past within the current ICSID arbitration system with regards to the mechanism for challenging arbitrator(s), and whether such mechanism allows ICSID to effectively deliver what it is expected to provide.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Conflict of interest; ICSID; Investor-State; World Bank

Voluntary membership: up to which point do cooperatives support liberalism? - Hiez, David (International Journal of Cooperative Law, 2019)

Online Dispute Resolution: Methods and Effects - Kumari, Poonam; Sood, Geetika (International Journal of Science and Research, 2019)
The concept of online dispute resolution came with the development of e-commerce. It is a branch which resolves the dispute between parties without interference of court. It includes arbitration mediation and negotiation. It also includes consumer to consumer disputes. With the emerging to globalisation the concept of online dispute resolution emerging day by day. The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. Thearticle is a study of ODR, online mediation and electronic arbitration. It includes their uses and their relationships with e-commerce. The paper is regarding primary aspects of online dispute resolution, its definition and its growth and development. It also includes the relationship between ODR and technology. Research paper isdiscussing the two forms of ODR: online mediation and electronic arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Online Dispute Resolution

Role of Alternative Dispute Resolution as a Mechanism for Administration of Justice - Renu, Shailja Chauhan (International Journal of Science and Research (IJSR), 2019)
Desire for quick and affordable justice is universal. Right to speedy trial is a right to life and personal liberty of every citizen guaranteed under Article 21 of the Constitution, which ensures just, fair and reasonable procedure. Alternative Dispute Resolution mechanisms have become more crucial for businesses operating in India as well as those doing businesses with Indian firms. There are various reasons for which ADR is preferred over the conventional way of resolving the disputes. India being a developing country, going through major economic reforms within the framework of the rule of law, for expeditious resolution of disputes and lessening the burden on the courts, alternative mechanisms for resolution (ADR) are the only alternative through arbitration, conciliation, mediation and negotiation.

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

Emerging Issues in Arbitration, Mediation and Conciliation - Sunil, Bhawna Bhelly (International Journal of Science and Research, 2019)
The resolution of disputes through alternative dispute resolution mechanisms has gained momentum over recent decades. It has increasingly occupied space in the academic literature as the “new” method to achieve “justice” for disputing parties. It is important to note that a variety of definitions of “justice” can be relied upon. However, in many cases, justice will mean the parties being able to resolve their dispute fairly, justly and amicably by applying law or legal principles. Traditional legal mechanisms for resolving disputes have been increasingly questioned as to whether they are actually capable of achieving justice in individual cases. Resolution in the courts is not only the method of resolving disputes . If the parties can resolve their own disputes then there will arise no need for court system in world. All though court system is good and fair way of dealing with civil disputes yet it might not be the best method to resolve the disputes. Basically there are four ways to of alternate dispute resolution. They are Negotiation, Mediation, Conciliation and Arbitration . The of ADR is to resolve the matters in a cost effective manner and foster long term relationship.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Conciliation; MARD; Mediación; Mediation; Mediação; Médiation; Méthodes alternatives de règlement de conflit

The Implementation of Provisions of IFRS Framework and Financial Perfomance of Banks - Anichebe, Alphonsus Sunday; Okpala, Ngozi Eugenia (International Journal of Trend in Scientific Research and Development, 2018)
The need for global financial language gave birth to International Financial Reporting Standards (IFRS). The adoption of IFRS has been argues to have changed the manner in which the financial statements are prepared, presented and reported. IFRS represents a single set of high quality, globally accepted accounting standards that can enhance comparability of financial reporting across the globe. The significant disparities between the Nigerian Statement of Accounting Standards and International Financial Reporting Standards have resulted in the Statement of Accounting Standards being regarded as outdated and incomplete as an authoritative and internationally accepted guide to the preparation of financial statements. The study however examined the extent to which Nigerian banks have implemented the provisions of IFRS frameworks. The sample comprises of fourteen quoted deposit money banks in Nigeria. Specifically, financial statement figures of 2007 – 2011 (pre-adoption period) and 2012 – 2016 (post-adoption period) were utilized. The study adopted the ex-post facto research design. Annual panel data were collected from the financial statements and accounts of 14 deposit money banks quoted on the Nigerian Stock Exchange as well from the Securities and Exchange Commission statistical bulletin from 2007 to 2016. The findings revealed that the return on shareholders’ funds has improved since implementation of International Financial Reporting Standards (IFRS) on Nigerian banks. IFRS implementation has significant effect on the profitability of quoted banks in Nigeria. The implementation of International Financial Reporting Standards (IFRS) has significantly influenced banks’ earnings and it was concluded that IFRS has positive impact on equity and earnings of banks. It was recommended that government and regulatory authorities should organize more quality training to get bankers informed.
Keywords: Banks; Financial performance; IFRS

Contractual capacity and the conflict of laws in common-law jurisdictions (part 1) : the United Kingdom - Fredericks, Eesa A. (Obiter, 2018)
This series of two articles provides a comparative overview of the position in the common-law conflict of laws in respect of the contractual capacity of natural persons. The comparative study is undertaken in order to provide guidelines for the future development of South African private international law. Reference is primarily made to case law and the opinions of academic authors. The legal position in the law of the United Kingdom, as the mother jurisdiction in Europe, is investigated in part I. Although Scotland is a mixed civil/common-law jurisdiction, the situation in that part of the United Kingdom is also discussed. Part II will deal with the rules and principles of private international law in respect of contractual capacity in Australasia (Australia and New Zealand), North America (the common-law provinces of Canada and the United States of America), Asia (India, Malaysia and Singapore) and Africa (Ghana and Nigeria). Part II also contains a comprehensive summary of the legal position in the common-law countries, followed by ideas for the reform of South African private international law in this regard.

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.
Number: 3 https://irep.ntu.ac.uk/id/eprint/41477/

Effect of IFRS on Value Relevance of Accounting Information: Evidence from Quoted Manufacturing Firms in Nigeria - Ezejiofor, Raymond Asika (International Journal of Trend in Scientific Research and Development, 2018)
This study evaluated the extent to which value relevance of financial information in Nigerian manufacturing firms has improved after the implementation of International Financial Reporting Standards (IFRS). Specifically, the study intended to: Ascertain the extent the adoption of IFRS has significantly improved the book value per share of manufacturing companies in Nigeria; Determine the extent the adoption of IFRS has significantly improved the Earnings Per Share of manufacturing companies in Nigeria and Examine the extent the adoption of IFRS has significantly improved the cash flow of manufacturing companies in Nigeria. Ex-post facto research design was adopted for the study. A sample of 54 manufacturing companies was randomly selected from manufacturing companies quoted on the Nigerian Stock Exchange for the periods of 2008-2015. Data for the study were obtained from the annual reports and accounts of the sampled companies. Specifically, a modified price model for detecting value relevance of accounting data for two different periods was employed. Regression Analysis and Chow test statistical tools were used to analyze and validate the data with aid of SPSS version 20.0. The study found that the adoption of IFRS has improved the book value per share, market share price, Earnings Per Share and cash flow of manufacturing companies in Nigeria. The implication of findings is that the value relevance of accounting information of manufacturing companies is more sensitive during Post-IFRS era than the Pre-IFRS era. The findings also imply that the book value per share, market price, earnings and cash flow have become informative to equity investors in determining the value of firms following IFRS adoption. The study recommends among other things that the accounting information for book value per share should be communicated to the investing public; and such information should be of high quality to avoid negative consequences on the part of investors.
Keywords: Accounting information; Manufacturing company; Value relevance

Impact of Contractual Capacity of Minor - Godha, Atisha (International Journal of Trend in Scientific Research and Development, 2018)
A contract involves s a promise between two persons for the exchange of either good or services. A contract signifies the free consent of the parties to the contract to be bound by law. For a contract to be valid, it must have these basic elements: mutual assent, consideration, capacity, and legality. Mutual assent is characterized by offer and acceptance through mutual accent; "consideration," on the other hand denotes any form of compensation with something of value for the goods or services traded. A contract between persons, either natural persons or legal persons, who have no capacity to contract can either be voidable or void depending on the case. Legality gives the condition that should be satisfied for a contract to be excised by the law. Illegal contracts are for example those involving illegal activities. For example one can't bring a plea of damages to a court of law for breach of a contract entered into to kill another person.The possible remedies for breach of contract are; general damages, consequential damages, reliance damages, and specific performance. This paper will examine the capacity to contract as pertains to contracts entered by minors minor's.
Keywords: Capacity; Consideration; Contract; Legality; Minor; Mutual accent void/voidable

Aspects of the regulation of cross-border insolvency in South Africa - Chitimira, Howard (Obiter, 2018)
This article analyses the regulation of cross-border insolvency under the Cross-Border Insolvency Act 42 of 20001 in order to examine the adequacy of such regulation as regards to the enforcement of insolvency proceedings in South Africa and other relevant jurisdictions. To this end, the paper provides an overview analysis of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act. Moreover, where possible, the paper also provides a comparative analysis of selected aspects of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act and those that are provided under the Insolvency Act 24 of 1936 and other related international instruments. This is done to expose the challenges and future prospects of the regulatory and enforcement framework under the Cross-Border Insolvency Act in South Africa.
Keywords: Insolvency; Regulation; South Africa

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
http://www.journalijar.com/
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

International Arbitration Practices in Nigeria: A Construction Industry Appraisal - Ewa, O. O.; Haytham, B.; Okon, E. E.; Enang, O. P.; Emiri, D. A. (World Journal of Innovative Research, 2018)
This paper aims to investigate Corporate Alternative Conflict Management and Dispute Resolution compliance through an appraisal of International Arbitration practices in Project-based Organizations in the Nigerian Construction Industry. In this study, simple percentages and frequencies of occurrence were used to analyse data derived through subject matter interviews and a questionnaire survey. Using the Survey Monkey tool, 85 questionnaires were distributed to key players in the AEC (Architecture-Engineering-Construction) Industry including Engineers, Project Managers, Architects and Quantity Surveyors and 53 were returned complete. The survey indicated that 66% preferred a more private Construction Arbitration to a public Litigation as a preferred method of dispute resolution, with 65% agreeing that a lack of proper project funding hinders the arbitration process in the Nigerian Construction Industry. 66% agree that Arbitration Time contributes more to project delays while 32% believe that Cost of the arbitration process is the greater source of project delays. We recommend that issues of confidentiality be carefully managed in dealing with outside counsels, while Project-based Organisations in Nigeria should ensure to develop master plans compatible with long-term strategies, including setting aside adequate funding for the timely resolution of project disputes through the implementation of only Arbitration-friendly contracts. This paper contributes to knowledge by bringing to bear the current compliance levels of project-based organisations in the practice of Arbitration in the Nigerian Construction Industry.
https://www.neliti.com/publications/262476/

Who is in? Who is out? How the Uncitral Transparency Rules Can Influence the Upcoming Amendments of the ICSID Arbitration Rules - Yu, Hong-Lin (Contemporary Asia Arbitration Journal, 2018)
The International Center for Settlement of Investment Disputes (hereinafter "ICSID") has started its fourth amendment of its Arbitration Rules since 2016. The issue of transparency has been highlighted as a delicate issue in ICSID ongoing current amendment. It is also listed in the topics that have been identified for potential amendment. This article analyses how the issues of access to hearings and confidentiality over information arising from arbitration is treated under the current framework. A comparison is made against the Transparency Rules. The analysis is also made against the comments received from the public whose views are analysed as a possible direction the amendment may take.

L’arbitrage international dans l'OHADA : évolution vers l’arbitrage des investissements en Afrique - Dalil, Mustapha (Journal of Strategic Affairs, 2018)
En vertu des dispositions de l’article 53 Al. 1 du Traité de création de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires) : « Le présent traité est, dès son entrée en vigueur, ouvert à l’adhésion de tout Etat membre de l’Union Africaine et non signataire du traité. Il est également ouvert à l’adhésion de tout autre Etat non membre de l’Union Africaine invité à y adhérer du commun accord de tous les Etats Parties ». Cette action d’harmonisation du droit des affaires, tout en s’inspirant d’autres législations telles que le droit français et la common law, les Etats-membres de l’OHADA ont à leur disposition un arsenal législatif efficace et approprié à leur développement économique communautaire. Ce droit revêt un intérêt particulier pour les entreprises marocaines actives dans l’espace OHADA. Le Maroc, par le renouvellement de son adhésion à l’Union Africaine (UA) et en procédant à une demande d’adhésion à la Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) dont le but est de « promouvoir la coopération et l’intégration dans la perspective d’une Union économique de l’Afrique de l’Ouest », (le Maroc) a réaffirmé sa détermination d’intégrer les espaces économiques africains de référence
Keywords: Arbitrage international; Droit des affaires; Développement économique; Relations internationales; Union africaine; الاتحاد الإفريقي; التحكيم الدولي; التنمية الاقتصادية; العلاقات الدولية; قانون الأعمال

OHADA and the Making of Transnational Commercial Law in Africa - Bashi Rudahindwa, Jonathan (Law and Development Review, 2018)
The Organisation for Harmonisation of Business Law in Africa (OHADA) was established in October 1993 with the ambitious aim of inciting economic development in its Member States. Through the adoption of Uniform Commercial Laws, the organisation is expected to create an enabling environment for business development, thereby providing for a path to economic growth and subsequent development. In light of this professed aim, both the transnational methodological approach and comparative law theories are used in this paper to critically analyse the various processes conducted under the OHADA banner and to engage in discussions on the highly debated role of law as a vehicle for development in sub-Saharan Africa. This exercise, which proves crucial in order to trace its origin within the global governance and law and development theories, allows us to present OHADA as a transnational legal system, while also highlighting both its strengths and limitations.
Keywords: Law and development; Law reform; Legislative unification; OHADA; Transnational law

Application of the OHADA Accounting System by Companies in DRC, Current Status and Prospects: Case of the City of Bukavu - Kulondwa, Safari; Nshobole Bahirwe, Nathalie (Journal of Accounting, Finance and Auditing Studies, 2018)
The objective of this research was to determine the current status of the application of the OHADA accounting system in DRC, five years after its adoption. A survey was conducted on thirty small and medium-sized enterprises in Bukavu to determine the level of compliance with the SYSCOHADA principles, the degree of harmonization of accounting practices and the difficulties related to the application of this system. The results shown consistently that compliance with Syscohada principles is not absolute, the level of Harmonization is still low and finally companies in DRC still need time to fit into the OHADA accounting system.
Keywords: Accounting Practices; Accounting Principles; Harmonization

Does the 1980 Vienna Sales Convention Reflect Universal Values? The Use of the CISG as a Model for Law Reform and Regional Specificities - Schroeter, Ulrich (Loyola of Los Angeles International and Comparative Law Review, 2018)

African Trade Growth or Trade Deficit: GATT/WTO Rules as Trojan Horse on African Trade Development - Obida, Idibia Daniel (World Journal of Research and Review, 2018)
The principle of Most Favored Nation (MFN) as a GATT rule as annexed to World Trade Organisation (WTO) is viewed as very crucial in the operations of the WTO amongst member countries. Another rule of striking importance is the standard of non-discrimination inserted in the MFN rules. As against the background, this study addresses the routine conviction with respect to the viability of GATT laws and WTO rules in the light of non-discrimination principle and Multifibre Agreement (MFA) and, The National Treatment Principle. The study explores the standards of these rules which are whittled down with concrete exemption clauses. These clauses make the adequacy of unhindered commerce guideline perplexed amongst member nations especially, the Sub-Saharan Africa. The study finds that rules of GATT having been made since 1947 at the time when Africa‟s economic development was annexed to their colonial masters and therefore, not in contemplation by the progenitors. The realization that Africa ought to be given chance to develop come too late within the GATT rules. The study finds that the current GATT structure cannot advance the promotion of African trade. The study addresses the grouping of African nations with other nations like Asia, India and South America as a misnomer and erroneous as Africa is the least developed in terms of international trade bargaining power among other developing countries. The study after analyzing MFN, MFA, National Treatment principle and Transparency rules of GATT, concludes they are development deficit as against trade promotion. The study further concludes that the difficulties in finding an acceptable definition of the „like product‟ by several Dispute Resolution Panels as laid down by GATT makes nonsense of the rule and a lacuna in the definition of Article III (2) and III (4) as they are components of paralysis of non-clarifications.
Keywords: GATT; General Agreement on Tariffs and Trade; Most Favoured Nations; Multifibre Agreement; WTO; World Trade Organization

Analysis of the rights and duties of insurers in Nigeria - Anifalaje, K. (University of Ibadan Law Journal, 2018)
The paper analyses the rights and duties of Nigerian insurers at common law emanating from the contractual relationship between the insurer and the insured as amplified or abridged under the statute. It argues that the statutory incursion into the common law rules of uberrimae fidei, insurable interest, conditions and warranties and assignment of policies, circumscribing some of the rights exercisable by the insurer against the insured to defeat just claims as well as expanding the scope of the insurer’s duties in order to improve on service delivery is salutary. The paper, however, concludes that further reform measures, aimed at addressing some other salient issues, are still essential in the overall interest of the insuring public.
Accepted: 2023-03-20T09:15:48Z
Keywords: Assurances; Assureur; Common law; Duties; Insurers; Nigeria; Rights; Statute

Gaps in the IFRS Conceptual Framework - Barker, Richard; Teixeira, Alan (Accounting in Europe, 2018)
The stated purpose of the IFRS Conceptual Framework is to assist the IASB to develop Standards that are based on consistent concepts, and also to assist preparers to develop consistent accounting policies when Standards either do not apply or allow a choice of accounting policy. Yet, the Framework actually does surprisingly little to help the IASB (or preparers) determine which assets, liabilities, income and expenses should be recognised, and how they should be measured. The Framework’s focus on assets and liabilities implies that the accounting can, and should, be determined from the balance sheet. Yet, many current financial reporting requirements focus initially on the income statement, and so they are not so much derived from the Framework as instead in need of being reconciled back to it. At its heart, the problem here is that, while the Framework states that accrual accounting provides a better basis for assessing past and future performance than cash-based information, it does not explain why. To do so would require a conceptualisation of how entities’ business models are employed to create value, and of the strengths and limitations of accounting data in enhancing investors’ understanding of that value-creation. The lack of explanation of the purpose and informational objectives of accruals, how they relate to business models and how they cause the income statement and the balance sheet to interact are gaps in the Framework. Filling those gaps would provide a more robust, and natural, way for the IASB to develop recognition and measurement requirements in its Standards.
Keywords: Accruals; Conceptual framework; IFRS; Measurement; Unit of Account

An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

Arbitration cost : a short comparative view of the schedule of fees of arbitration centers within the OHADA zone - Dogué, Karel Osiris Coffi (Revue de l'ERSUMA, 2018)
Amongst the seventeen OHADA member states there are over fourteen arbitration centers or institutions that handle disputes arising from contractual agreement without going through the courts of the state. The arbitration cost within the various arbitral centers differs from one arbitration center to another. The schedule or method for calculating fees are regulated by the rules of the various arbitration centers or by the OHADA Uniform Act Arbitration Rules pertaining to arbitration fees annexed to the rules of arbitration for the Common Court of Justice and Arbitration and for arbitration centers without arbitration rules. This contribution describes and contrast the various schedule of fees applicable with the arbitration centers under the OHADA zone in particular and also makes a comparative view of the arbitration fees out of the OHADA zone.
Keywords: Arbitragem; Arbitraje; Arbitration; Arbitration cost; Arbitration fee; Arbitration proceedings; Coût de l’arbitrage; Frais d’arbitrage; OHADA Arbitration's Center; Procédure arbitrale

Factors Influencing Indian Firms Decision Making In Foreign Direct Investment In Africa - Kukreja, Mukta; Joshi, Mahesh Chandra (International Journal of Applied Business and International Management, 2018)
India's economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the International typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.
Keywords: African nations; Developing countries; FDI; India; Indo-Afro relations; Investments; Multinational companies; OLI eclectic paradigm

The Organisation for the Harmonisation of Business Law in Africa (OHADA) System: Overview of some Benefits and Problem Areas - Leno, Ngaundje Doris (International Journal of Advanced Research and Publications, 2018)
As much as the Organisation for the Harmonisation of Business Law in Africa (OHADA) aims to improve the legal environment for business, the harmonisation process should be seen as a tool of economic integration with several advantages. Despite the achievements and benefits, OHADA, like other regional integration efforts in Africa, has some temporary drawbacks that may become permanent if no effort is made to overcome them. The primary focus of the paper is to present OHADA‟s background; offer an overview of some of the salient benefits of OHADA‟s institutional and regulatory framework; consider OHADA‟s problem areas; and propose possible solutions to the problems. The value of the paper, therefore, lies in the insight it offers into OHADA, the benefits and problems of its institutional and regulatory framework. It is also important because it is laying the foundation in making the OHADA structure available for all Africans.
Keywords: Business law; Harmonisation; OHADA

Accounting Translation of Corporate Social and Environmental Expenditures in Small and Medium Industry: What Evaluation Approach and what Accounting Scheme? - Missomba, Jean Christian Ewane; Hanko, Osée (Research Journal of Finance and Accounting, 2018)
The question remains whether societal reporting integrates the field of financial reporting. This old debate is repeated to scrutinize the case of African companies with strong cultural roots, which do not publish alternative societal documents to traditional financial reports. Through stakeholder theory (Jones and Wicks, 1999), this study aims to analyze the phenomenon, by describing the process of accounting recordings for social and environmental information (SEI) identified by the ISO 26 000 standard in an oil Company operating within OHADA Jurisdiction. The results indicate the presence of mandatory SEIs in the financial statements, which visibility depends on the pressure exerted by the State and the accounting regulations in force. Voluntary SEIs are not visible.
Keywords: Financial reporting; ISO 26000; Social and Environmental Information (SEI); Stakeholder Theory

Some considerations on the flexibility of carrier's liability in OHBLA Law - Monkam, Cyrille (Revue de l'ERSUMA, 2018)
This article argues that the liability of the carrier is more flexible in OHBLA Transportation Law. It appears from the analysis that the carrier who is under strict or presumed liability may enjoy a large number of exemptions that may be classifiedunder classic and modern defenses on condition to act fairly and honnestly in performing the contract of carriage. The fairness and honnestly are expressed under the good faith principle. The contrary attitude -the performance in bad faith- will be sanctioned by the exclusion from the benefit of the various exemptions. The assessment of this unscrupulous behaviour of the carrier is vested on judges who have to determine in case of claims whether the behaviour constitutes a willful misconduct or a gross negligence. As examiners of the carrier's attitude, judges play a major role in establishing security and justice in contract of carriage. By setting up a flexible liability regime, the OHBLA Uniform Act is seen as a balanced instrument that sets up a compromise between carrier's interests and cargo's interests.
Keywords: Acte uniforme; Contrat de transport; Droit OHADA; Droit des transports; Transport de marchandises par route; Transportation Law

The protection of workers' claims in the event of the insolvency of their employer : OHADA's approach - Ngaundje, Leno Doris (Revue de l'ERSUMA, 2018)
An employer's insolvency has far-reaching consequences on workers. The consequence of business failures have complelled policy makers to provide for workers protection in the event of their employer's financial demise. The policy makers of the Organisation for the Harmonization of Busniess Law in Africa approach (OHADA) are not left out. This article seeks to examine OHADA's super-priority approach (article 95 of OHADA's Revised Insolvency Act - RIA) on the protection of workers claims with the aim of showing that approach is limited. Article 95 does not prescribe the limit on the amount protected, the time period and the category of workers concerned. This article ecognizes the need to reform article 95 of OHADA's RIA.In so doing, the article describe the position of two international bodies (International Labor Organisation -ILO) and the European Union -EU) on employee entitlements in insolvency as the bases needed to reform article 95 of OHADA's RIA. The value of this article lies in the nisights it offers into the current framework on insolvency and the opportuniy given to address the limitations that invariably arise from article 95 of OHADA's RIA.
Keywords: Droit OHADA; Faillite; Insolvabilité; Insolvency; Procédures collectives; Protection des créanciers

Lex mercatoria in OHADA arbitration : A legal basis for unauthorized amiable composition? - Nshokano Kashironge, Dan (Bulletin ERSUMA de Pratique Professionnelle, 2018)
Keywords: Amiable composition; Arbitrage; Arbitration; Lex mercatoria; Lex mercatória

(Non) Compliance with multi-tiered dispute resolution clauses under OHADA's new ADR law : a question of juridiction or admissibility ? - Nshokano Kashironge, Dan (Bulletin ERSUMA de Pratique Professionnelle, 2018)

Corporate governance and resource management in Nigeria: a paradigm shift - Oyewunmi, Olabode Adeleke; Oyewunmi, Adebukola Esther (Business Perspectives, 2018)
The underlying significance of instituting measures for effective corporate governance and rewarding resource management outcomes cannot be relegated. The countries and organizations that deemphasize this practice have mortgaged their potential for long-term growth and corporate sustainability. This paper adopts a critical narrative method to deconstruct the essence of corporate governance and economic resource management ideals. The paper furthers the ongoing conversations on two interrelated business concepts, and provides an apt perspective towards unlocking the essence of corporate governance relative to the Nigeria’s corporate environment. It depicts a corporate paradigm shift that accommodates the dynamics of global best practices taking into account some peculiarities of Nigeria’s corporate climate. The paper also captures relevant theoretical dimensions and pragmatic policy propositions, especially for underperforming socio-economic contexts. In the light of the central theme, specific issues are discussed under the sub-headings of conceptual and theoretical clarifications, corporate governance and resource management in Nigeria, shifting the paradigms, conclusion and recommendations.
Number: 1 http://www.businessperspectives.org
Keywords: Corporate governance; Nigeria; Resource management

What Do Trade Agreements Really Do? - Rodrik, Dani (The Journal of Economic Perspectives, 2018)

Without Silence, There Is No Golden Rule; Without Dissent, There Is No Progress - Uluc, Inan; Sutton, Kristi R. (Oregon Review of International Law, 2018)
The frequency of dissenting opinions accompanying arbitration awards in international arbitration has multiplied, particularly in international investment arbitration. Accordingly, dissenting opinions are now inevitable companions to majority awards. Notwithstanding the fact that dissenting opinions neither form part of an arbitral award nor constitute a separate award, the escalation of dissenting opinions spawns anxiety in scholars and practitioners. This trepidation ignited a crusade whereby those opposed to the practice of rendering dissent challenge the role and usefulness of these opinions. In this respect, this Article initially considers and critiques specific arguments raised by those opposed to dissenting opinions in international arbitration. Following analysis of the criticisms, this Article explores the beneficial and constructive aspects of dissenting opinions. Evident from this discussion is that dissenting opinions are not only integral to supplement an arbitrator’s quasi-judicial capacity, but also encourage issuance of well-reasoned awards. Clear from the benefits of dissenting opinions in international arbitration, any departure from the present clemency espoused toward the practice will eventuate in the field’s regression.
Keywords: Civil law; Common law; International arbitration

The Impartiality and Independence of Arbitrators and Its Implication on the Validity of Arbitral Awards - Yoga, I. Ketut Dharma Putra (Juris Gentium Law Review, 2018)
Arbitration is a way to resolve disputes outside the courts as a form of an alternative dispute resolution. The submitted dispute will be decided by one or more arbitrators, who will then render an arbitral award. One of the most fundamental principles of arbitration that must be adhered to by all arbitrators worldwide is the impartiality and independence of arbitrators, which have been regulated in various International laws. Arbitrators are not allowed to communicate with any party related to the case they are hearing. Further, arbitrators should not be influenced by others in making their decision and drafting the arbitral award to ensure objectivity and prevent any bias. An arbitrator's failure to act impartial and independent can lead to the invalidity or annulment of an arbitral award.
https://www.neliti.com/publications/441283/

O.E.C.D. promotion for arbitration as an additional tool of settling disputes in the field of international taxation - Zeyen, Gaëtan (Revue de l'ERSUMA, 2018)
In a globalized world, arbitration plays an increasing role in settling international disputes. Almost all areas of Law are or might be concerned. Until very recently, [international] taxation was - as a rule - seen as a not ‘arbitrable-friendly’ matter. As the ‘classical’ method of settling international tax disputes - i.e., based on the so-called ‘Mutual Agreement Procedure’ (shortly, ‘M.A.P.’) - has shown its limits (mainly: lack of efficiency and involvement from the taxpayers themselves), arbitration became a subject of study for well-known and established academics and even an appropriate method of settling such international tax issues. As a result, both on international (O.E.C.D.) and European levels, legal initiatives have been taken, in order to promote arbitration as an additional tool of settling disputes in the field of international taxation. The purpose of the present article is, therefore, to describe and scrutinize these [very] recent legal initiatives and raise some potential issues that, at least in the author’s view, need to be addressed. One of these issues concerns the enforcement of such arbitral decisions.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration proceedings; Dispute settlement; International taxation; O.E.C.D; OCDE

Reflections on Legal Uncertainties for e-Commerce Transactions in Cameroon - Nwabueze, Caroline Joelle (The African Journal of Information and Communication, 2017)
This thematic report appraises legal provisions currently governing e-commerce transactions in Cameroon, in particular the matter of online contracts for sales of goods and services. There are uncertainties for Cameroonian consumers in the legal provisions at both regional level – via the Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA, the Organisation for the Harmonisation of Business Law in Africa) – and at Cameroonian national level. The report recommends steps to be taken to remedy the uncertainties.
Keywords: Consumer protection; E-commerce; Online contracts; Online transactions

Legal framework of Directors' Duties in OHADA Law (Senegal) - Niang, Oumar (International Journal of Business, Economics and Management Works, 2017)
This article is aimed to study the legal framework of directors’ duties in Ohada law. The Organization for the Harmonization of Business Laws (OHADA),is a supranational system of business laws that, as implemented in Senegal is trying to regulate all the core businesses.Ohada displays two level of mixing.Firstly,Ohada Law is supranational, it becomes part of the internal law of each state member but still remains supranational characteristics.Secondly,Ohada being at least partially French-inspired, we can understand that the most of the countries which adopted Ohada Laws are French-speaking. The duties of Directors in Senegal are regulated mainly by the uniform companies’ act which is part of the Ohada law. It should be noted that before the adoption of Ohada, company law was governed by the code of civil obligations and in its fourth part. For companies listed on the RSE, they must comply both with the general regulations of the BRVM and with the provisions of the Uniform Companies Act concerning publicly traded companies. This article aims to illuminate the lanterns on the question of the duties of directors in Ohada law, during my research I have observed that subjects such as corporate governance in general and the duties of directors in Ohada are left stranded by most researchers. This is why this topic has an interest in reabsorbing this gap insofar as the legal framework of the duties of directors often mentions many questions because of the lack of loyalty and diligence of certain directors.
Copyright © 2017 KWP Journals. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. International Journal of Business, Economics and Management Works Kambohwell Publisher Enterprises www.kwpublisher.com
Keywords: Company law; Corporate; Directors Duties; Governance; Senegal

Dispute resolution in the oil and gas industry: an appraisal of mediation and litigation procedures. - Mohammed, Jamilu Ibn (Journal of private and business law, 2017)
The Oil and Gas Industry Resolution originally recognised negotiation and concede to the alternative dispute resolution rather, their litigation. The paper analysed appraised the different alternative dispute resolution, formulae including mediation the doctrinal method of research which analyses all legal in others as applied. All methods relating to the dispute resolution were analysed from the library and it has formed that mediation which involves the process of resolution dispute weather the involvement of litigating is prefer for being use costly and time consuming. Litigation been so expensive and time wasting is not recommence for oil and Gas Industry.
Keywords: Dispute Resolution; Gas; Industry; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Oil

A Pluralist Approach to the Law of International Sales - Coetzee, Juana (Potchefstroom Electronic Law Journal, 2017)
International trade can support economic development and social upliftment. However, people are often discouraged from contracting internationally due to differences in legal systems which act as a non-tariff barrier to trade. This article focuses on the private law framework regulating international contracts of sale. During the twentieth century, the problem of diverse laws was primarily addressed by global uniform law such as the United Nations Convention on Contracts for the International Sale of Goods (CISG). However, uniform law is rarely complete and has to be supplemented by national law, trade usage or party agreement. Because of gaps that exist in the CISG the Swiss government made a proposal for a new global contract law. But is this a feasible solution to the fragmentary state of international trade law? In Europe, signs of reluctance are setting in towards further harmonisation efforts. The Proposal for a Common European Sales Law (CESL) was recently withdrawn, and now Britain has voted to leave the European Union; rumour having it that more countries might follow. The current private law framework for international sales contracts consists of a hybrid system where international, national, state and non-state law function side by side. This article submits that universalism is not per se the most efficient approach to the regulation of international sales law and that economic forces require a more varied approach for business-to-business transactions. The biggest challenge, however, would be to manage global legal pluralism. It is concluded that contractual parties, the courts and arbitral tribunals can effectively manage pluralism on a case-by-case basis.
Keywords: Global legal pluralism; Legal harmonisation; international contracts; international sales; unified law

Foreign Direct Investment and Economic Development in Africa - Adegboye, F. B.; Ojo, Joshua A. T.; Olokoyo, F. O. (Journal of Internet Banking and Commerce, 2017)
Africa unlike other developing regions of the world has experienced declining flows of foreign direct investment (FDI).The flow of FDI is expected to result into gradual reduction in reliance on external borrowed capital and acceleration of economic development. The study examined the declining flow of FDI to the African regions as well as the impact that it has had on economic development of the region, using the proxies of Income per capita, Life expectancy and Education indices. The study made use of pooled data from thirty nine African countries within the period 1993 and 2012.The method of analysis utilized for the study was the fixed effect least-square dummy variable model, employed to estimate the impact of foreign direct investment on economic development for the selected host African countries. The study finds that foreign direct investment is statistically significant in relation to economic development for host African countries. It is therefore recommended that the governments of host countries should consider closely the sectors that FDI flows into, encourage investment domestically in such sectors such that dependence on external financial flows could be reduced, resulting in sustained increases in income, literacy level and hence improved life expectancy which are expected to result into sustained economic development.
Number: 1 http://www.icommercecentral.com
Keywords: Economic Development; Foreign direct investment; Host African Countries; Income Per Capital; Investments; Life Expectancy

United States' bankruptcy jurisdiction over foreign entities: exorbitant or congruent - Walters, Adrian J. (The Journal of Corporate Law Studies, 2017)
Alarmed at the ease with which global bankruptcy jurisdiction can be engineered in the US through a combination of the Bankruptcy Code’s low bar to entry and the worldwide effects of a bankruptcy case, critics argue that the US promotes abusive bankruptcy forum shopping and harmful imposition of US norms on overseas stakeholders. This article advances a revised account of US bankruptcy jurisdiction over non-US debtors from a distinctively Anglo-American standpoint. The article’s central thesis is that critics overemphasise formal jurisdictional rules and pay insufficient attention to how US courts actually exercise jurisdiction in practice. It compares the formal law ‘on the books’ in the US and UK for determining whether or not a domestic insolvency or restructuring proceeding relating to a foreign debtor can be maintained in each jurisdiction and provides a functional account of how US bankruptcy jurisdiction over foreign entities is exercised in practice using the concept of jurisdictional congruence as a benchmark.

Alternative Dispute Resolution (ADR) and access to justice: An introduction - Betancourt, J. (Arbitration, 2017)
Text of a talk given by the author at the University of West London on 8 March 2016 on the topic of Alternative Dispute Resolution, its relation to the concept of access to justice and the idea of practising law in the interest of justice.
https://ora.ox.ac.uk/objects/uuid:fdf8485f-c538-4312-8241-9419561af728

International Accounting Standards in Africa: Selective Recursivity for the 'Happy Few'? - Botzem, Sebastian; Quack, S; Zori, Solomon George (Global Policy, 2017)
This study explores recursivity in international accounting standard-setting, focusing on participation of actors from African countries. While the International Financial Reporting Standards (IFRS) Foundation bases its legitimacy claims as a global standard-setter on a combination of expertise and a formally transparent set of recursive procedures for consultation of stakeholders, empirical results show that participation in the latter is geographically very uneven. The article argues that conceptual mismatch between the standard-setter's objectives on the one hand and the socio-economic, cultural and political conditions in many African countries on the other leads to selective recursivity that is problematic for the former's legitimacy and effectiveness. These findings are of wider relevance for debates on global standard-setting and development.
Keywords: Accounting Standard; Africa; Economics of Culture; IFRS; International Accounting

Oiling the machine: overriding mandatory provisions and public policy in the Hague Principles on Choice of Law in International Commercial Contracts - Dickinson, Andrew (Uniform Law Review, 2017)
Art. 11 of the Principles on Choice of Law in International Commercial Contracts, adopted by the Council of the Hague Conference in March 2015 contains provisions governing the relationship between the system of law1 chosen by the parties under Art. 2(1) (the “chosen law”) and the laws and policies of other systems. It provides as follows: 1. These Principles shall not prevent a court from applying overriding mandatory provisions of the law of the forum which apply irrespective of the law chosen by the parties. 2. The law of the forum determines when a court may or must apply or take into account overriding mandatory provisions of another law. 3. A court may exclude application of a provision of the law chosen by the parties only if and to the extent that the result of such application would be manifestly incompatible with fundamental notions of public policy (ordre public) of the forum. 4. The law of the forum determines when a court may or must apply or take into account the public policy (ordre public) of a State the law of which would be applicable in the absence of a choice of law. 5. These Principles shall not prevent an arbitral tribunal from applying or taking into account public policy (ordre public), or from applying or taking into account overriding mandatory provisions of a law other than the law chosen by the parties, if the arbitral tribunal is required or entitled to do so. In brief summary, therefore, the first and third paragraphs address the relationship between the chosen law and certain laws and policies of the forum, the second paragraph addresses the relationship between the chosen law and certain laws of legal systems other than the forum, the fourth paragraph addresses the relationship between the chosen law and the certain policies of the legal system whose laws would have applied but for the parties’ choice under Art. 2(1) and the fifth paragraph addresses the limits of the application of the chosen law in arbitration proceedings.

International Arbitration - Liatowitsch, Manuel; Rosenthal, Jeffrey; Forneret, Martine; Scherker, Emily; Ashford, Peter; Janzik, Sabrina; Weldon, Matthew; Houston, Robert; Boog, Christopher; Gottlieb, Benjamin; Meijer, Gerard; Verberne, Valerie; et al. (The Year in Review, 2017)
Keywords: Arbitration; Dispute resolution; International Law

Document Production and Disclosure in Investor-State Arbitration - Oepangat, Dioputra Ilham; Janet, Janet (Juris Gentium Law Review, 2017)
It is not uncommon for states to engage in arbitration proceedings with their investors (“Investor-State Arbitration” or “International Investment Arbitration”) administered under the International Centre for the Settlement of Investment Disputes. When these parties engage in document production during evidentiary proceedings, there arises an issue with regards to documents requested by the investor, which is considered as a “state secret” by the state. Based on the IBA Rules on the Taking of Evidence in International Arbitration (“IBA Rules”), states may have particular interest to refuse the production of a document. This is based on the argument that a document may be exempted from production if the document qualifies as a state secret by virtue of Article 9 of the IBA Rules. This paper will discuss appropriate measures to be taken by tribunals in order to allow for material and relevant evidence to be produced during proceedings, which may be crucial in being able to prove the case of the investor in the case of a conflict pertaining to the production of documents containing state secrets.
Keywords: Arbitrage; Arbitragem; Arbitration; Disclose; Document; IBA; ICSID; International; Investments; Prove; Secrets; Sensitive

Can third party funding deliver justice in international commercial arbitration? - Yu, Hong-Lin (International Arbitration Law Review, 2017)
Third party funding arrives at international commercial arbitration without clear guidelines. The recognition and acceptance of its legality is hampered by the omissions of all stakeholders' rights involved in international commercial arbitration. In balancing the funder’s contractual rights to gather information under the third party funding agreement and stakeholders' rights to know, the current research examined how non-disclosure of the third party funding agreement would prevent the arbitrators from fulfilling procedural justice required for the integrity of arbitration on their part and impede the opposing party’s right to know during the proceedings. The research highlights the issues from the delivery of procedural and substantive justice as well as suggesting legal and jurisprudential grounds in third party funding governance. It also points out that all issues examined will ultimately contribute to the failure in delivering justice in international commercial arbitration if third party funding is left to self-governance.
Keywords: Arbitration; International commercial arbitration; Third Party Funding

The stakeholder theory of corporate control and the place of ethics in OHADA: The case of Cameroon - Sama-Lang, Irene; Zesung, Njonguo Abel (African Journal of Business Ethics, 2016)
The rapid increase in globalization in the last two and a half decades has caused businesses to easily transcend national boundaries. States respond to such flexibility by harmonising their laws to easily adapt to such changes in order to attract investments. This is the case with the OHADA jurisdiction where its architects foresaw an economic spur through integration of business laws. Though expected to stay within the bounds of the law, the law cannot absolutely determine how businesses should prioritise their stakes. As such, ethics comes in to complement the law. This article uses the stakeholder theory of corporate control to investigate the place of ethics in OHADA, as applied in Cameroon. It concludes that an altruistic social conscience is still highly wanting.
Keywords: Business; Corporate control; Corporate law; Ethics; OHADA; stakeholder

Tax Mobilization in Sub-Saharan Africa: The Impact of Tax and Business Law Reforms - Bertinelli, Luisito; Bourgain, Arnaud (Economics Bulletin, 2016)
This paper contributes to measuring the influence of business (and tax) law reforms on sub-Saharan African countries tax mobilization ability. Relying on a new business law reform indicator, our results validate the significant impact of corporate law modernization on governmental revenue, and unearth a complementary effect between business and tax law reforms.

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

Force Majeure, Change of Circumstances and Termination of Contract - Han, Shiyuan (Journal of Law, Society and Development, 2016)
It is impossible to draw a distinct line between force majeure and change of circumstances, because the two overlap. In order to regulate both force majeure and change of circumstances, the United Nations Convention on Contracts for the International Sale of Goods (CISG) has adopted a unified model in article 79, whereas Chinese law adopts a dual model by treating them as different things and regulating them in different articles. Where the purpose of a contract becomes impossible to achieve because of a force majeure and both the CISG and Chinese Contract Law (the CCL) adopt the same model of termination of the contract, the contract should be terminated by one party with a notice to the other party instead of ipso facto avoidance. In a case of a change of circumstances, in order to terminate the contract, both the CISG and the CCL actually follow the path of raising an action by a notice of avoidance or termination to theother party. Both approaches have their merits and demerits but the differences between them in practice are not as large as presumed. Where force majeure and change of circumstances overlap each other, possible ways for termination of the contract are for a party either to choose their preferred solution or to follow the lex specialis derogat generali. The latter way is preferred in this article; and while in an action for termination the judge may balance the interests of both parties in making a final decision, the uniform application of the law, the safety of the transaction and the fairness of the judgment may be ensured in so doing.
Keywords: CISG; Change of circumstances; Chinese Contract Law; Force majeure; Gestaltungsklagerecht; Termination

Oil in the Gulf of Guinea States and South Africa in the Matrix of Overlapping Membership of African Regional Communities: An Impediment to Regional Integration? - Jobodwana, Zingisile Ntozintle (Journal of Law, Society and Development, 2016)
The Gulf of Guinea states (GOGs) discussed in this article comprise a diverse group of more than 20 African states bordering on the oil-rich Gulf of Guinea. They are former colonies of Belgium, France, Great Britain and Germany. These states are of strategic importance to the United States, the European Union, India and China because of their tremendous natural resources that include biodiversity, oil, gas and other strategic minerals. But to what extent are they also of strategic importance not only to South Africa but to SADC member states? After all, the GOGs boast of their sea routes being safer and more convenient for sea transport. Post-colonial independence finds these states still adopting a mixture of foreign legal systems side by side with indigenous laws and customs. The region is still underdeveloped, with poor physical infrastructure, weak government structures, an inefficient legal system, and internecine strife and other inter-state disputes exerting a debilitating influence. The NEPAD Plan of Action of 2001 looks to the regional economic communities (RECs) to become the leaders in regional economic co-operation and integration. Although the GOGs are characterised at present by overlapping membership of various communities, they have enjoyed some successes based on the newly found petroleum commodity which, wisely managed, can help to increase intra-African trade and produce a viable extensive African market buttressed by South Africa's economic advances into the rest of Africa. In some of the regions in Africa RECs such as ECOWAS and SADC have been able to transform their economic and monetary co-operation efforts into a powerful driving force for economic policy co-ordination and integration, but a strong, credible, effective and efficient legal framework with sustainable supporting institutions is now needed. South Africa is well poised to assist with deepening the political and economic integration in the GOGs by intensifying foreign direct investment (FDI), capacity-building and training projects, and the transfer of skills and technology. But the RECs overlapping membership needs to be rationalised, the negative influences of the superpowers need to be resisted, and support is required to maintain peace and stability and ensure the security of the maritime regimes. A strong, independent supra-national body that is also able to supervise and monitor revenues from oil for the benefit of the region as a whole should be established.
Keywords: African Union; COMESA; EAC; ECCAS; ECOWAS; Gulf of Guinea Commission; Gulf of Guinea states; OHADA; Overlapping membership; Regional economic communities (RECs); Regional integration; SACU; SADC; South Africa; Supra-national independent regiona; Treaties

The Attitude of OHADA Law Countries Towards the CISG - Kahindo, Nguru Aristide (Journal of Law, Society and Development, 2016)
Disparities in national laws are likely to result in uncertainty which, in turn, creates obstacles to international commerce. It is acknowledged that strong investment flows cannot be achieved without a secure legal and commercial environment. Mindful of such a need, states decided to harmonise sales law internationally. To this end, in 1980 they adopted the United Nations Convention on Contracts for the International Sale of Goods known as the Vienna Sales Convention or the CISG. The CISG has led a number of countries, including the Organisation for the Harmonisation of Business Law in Africa (OHADA) law states, to modernise their local sales law. However, only three of 17 countries that constitute the OHADA community have ratified the CISG. OHADA law countries give the impression of favouring a more regional approach to the unification of sales law rather than the CISG™s global approach by implementing a local Commercial Uniform Act. Their indifference towards the CISG is not without consequences for commerce in the OHADA region. This article seeks to demonstrate that the lack of ratification of a universal convention, as for example the CISG, poses a danger to commercial dealings. It also intends to show that the CISG is not hostile to regional uniform sales laws of the OHADA Commercial Uniform Act type. It concludes that OHADA countries do not need to be afraid of their acceptance of the CISG and recommends that it be ratified.
Keywords: Business law; CISG; Commercial Uniform Act; Harmonisation; OHADA law; Uniform sales law

The UNCITRAL Model Law on International Commercial Arbitration: Interpretation, General Principles and Arbitrability - Viscasillas, Pilar Perales (Journal of Law, Society and Development, 2016)
This article explores the possible modification of the UNCITRAL Model Law on International Commercial Arbitration (MAL) to include the topic of arbitrability. This is an area in which the domestic legal systems differ, particularly in relation to the arbitrability of intra-corporate disputes. The article also deals with new art 2A, introduced into the Model Law in 2006, which deals with the interpretation and gap-filling system under the Model Law. The interpretation of MAL in accordance with its international character is a very important step towards uniformity and therefore the different tools required for a uniform interpretation are analysed. These include case law and scholarly writings; the meaning and importance of achieving both a uniform and an international interpretation of MAL are also considered. The article also analyses the whole text of MAL in order to arrive at the general principles on which the Model Law is based; when problems have to be solved, these principles should guide issues of interpretation that arise under this law.
Keywords: Arbitrability; Arbitration; General principles; Interpretation; UNCITRAL

Regional Harmonisation of Contract Law - Is It Feasible? - Zeller, Bruno (Journal of Law, Society and Development, 2016)
This article investigates whether regional harmonisation is merely an academic exercise or a serious attempt to create a uniform contract law in a defined region. It builds on the recently conducted Symposium at Villanova University in 2013 and addresses comparatively the efforts by well-defined regions, namely OHADA, the EU and ASEAN. OHADA has introduced regional uniform laws; the EU is still working on formulating them. Furthermore, UNCITRAL has considered a proposal by the Swiss government to work urgently on a new initiative to further harmonise contract law. Against this backdrop, this article argues that regional proposals to harmonise contract law are akin to saying that ‘ein Gespenst geht um’ (a ghost is going around) (Reich 2006: 425). This is justified, because a proposal to create a harmonised contract law in East Asia has currently also been discussed, but the discussions have stalled. Is there a solution or do we simply admit that regional harmonisation is not possible? The starting point is the CISG, as has been adopted by 80 countries and needs to be considered by any region as a possible, albeit not perfect, solution. If the CISG has already been ratified, the issue, then, is how any regional developments can coexist with it. Or does a ratification of the CISG preclude any regional harmonisation? Secondly, the question must be asked whether regional harmonisation will reduce transaction costs, which is beyond what the CISG was able to achieve. This article argues that as far as the drafting of international instruments isconcerned, a shift in thinking has occurred. Instruments such as the Cape Town Convention are considered to be reforming the law in a particular narrow area rather than attempting to draft codes. Furthermore, the process is driven by industry groups. Regional harmonisation must take note of the ongoing shift and a more fruitful approach is to develop uniform laws through a better understanding and coordination of existing instruments.
Keywords: CISG; Contract law; Regional harmonisation; Uniform law

Arbitrability and public policy: an African perspective. - Mante, Joseph (Arbitration international, 2016)
Growth in international trade has led to considerable expansion of the scope of matters capable of settlement by arbitration. In spite of sustained scholarly activity on arbitrability, the question of what is arbitrable remains controversial but relevant in many regions of the world, including Africa. Arbitrability has the potential to affect the validity of an arbitration agreement, strip an arbitrator of jurisdiction, or derail enforcement of an award. Given the significance of the concept, it is vital that entities involved in international transactions do not speciously extrapolate knowledge of what pertains in Europe and America across all jurisdictions and regions of the world. This study draws a comparison between arbitrability and its relationship with public policy in Europe and America on one hand, and the trend in Africa in an attempt to critically investigate the extent to which African states are willing to extend the scope of arbitrable subject matters. A number of trends on arbitrability are discernible. Most commercial disputes are arbitrable and this observation generally aligns with practice in Europe and America. Beyond this, there are three significant differences in the areas of scope of subject matter, approaches to arbitrability regulation and the role of public policy.
https://rgu-repository.worktribe.com/output/246435/arbitrability-and-public-policy-an-african-perspective
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Policy

Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.
Number: 3

An Introduction and an Evaluation of Arbitration in Ivory Coast - Kalle, Aurélie (Recht in Afrika, 2016)
The paper deals with arbitration law in Ivory Coast and is mainly based on interviews with the most important authorities in this field. After a short introduction into the OHADA legal system the two main arbitration centres of Ivory Coast are presented. First, the paper treats the internationally known OHADA arbitration centre of the Common Court of Justice and Arbitration, hereinafter known as CCJA. It explains the bodies and the organisation of the CCJA, the arbitration procedure in detail, the enforcement of the arbitral award, the interim measures and the legal remedies against decisions of the CCJA. Second, the functioning of the Court of Arbitration of Côte d'Ivoire, hereinafter known as CACI, is explained. It is the second arbitration centre of Ivory Coast and it was created by the Ivorian Chamber of Industry and Commerce and settles mainly disputes between nationals. The analysis treats the same topics as mentioned for the CCJA centre, but is restricted to point out the differences or peculiarities of the CACI procedure, in order to prevent repetitions. Third, the paper analyses the advantages and disadvantages of the two arbitration centres and compares them to the proceedings of the Commercial Court of Abidjan. It avoids the comparison of yet well-known arguments such as confidentiality of arbitration proceedings or the parties' free choice in regard to the place of arbitration and the language, etc. The work rather limits itself to concretely address the problems or the advantages of each dispute solution considering the latest developments in the judicial system. The purpose of the report is to give a practical introduction into the Ivorian arbitration law, in particular to foreign lawyers. It should provide them with solid theoretical knowledge of the different dispute solutions. With the help of concrete comparisons and explanations of the actual situation regarding the civil and commercial judicial system it should enable them to find the most suitable dispute solution for their clients.
Keywords: Arbitrage; Arbitragem; Arbitration; Côte d'Ivoire; Ivory Coast

Integration through comparative private law: Four lessons from Cappelletti - Infantino, Marta (International Journal of Constitutional Law, 2016)
The aim of this article is to explore Cappelletti’s most enduring teachings relevant to those who promote global or regional integration of private laws. The article will review Cappelletti’s insights into the dynamic history of law, the need to respect diversity and take into account society’s imbalances, and the duty of comparative lawyers to engage in “applied” interdisciplinary legal research.

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

The OHADA Common Court of Justice and Arbitration: Exogenous Forces Contributing to Its Influence - Dickerson, Claire Moore (Law and Contemporary Problems, 2016)

Reflections on the Nexus Between Public Procurement Reforms and Economic Development in Nigeria - Okolie, Aloysius-Michaels; Nnamani, Kelechi (African Journal of Politics and Administrative Studies, 2016)
Corruption has widely been recognized as one of the impediments to the socio-economic cum political development of Nigeria. By 2000, it was observed that the conduct of government business in Nigeria had become difficult and expensive due to pervasive corruption, particularly procurement fraud. Although procurement fraud is one of the most common avenues of corruption in most countries, its incidence in Nigeria by 2000 was particularly widespread. To reverse this ugly trend, the Nigerian government initiated the public procurement reforms with a view that a corrupt-free procurement process will among other things, promote economic development in the country. Consequent upon the reform, the Public Procurement Act was enacted while the Bureau of Public Procurement was established to ensure due process, accountability and transparency in the award of government contract. In this light, this study evaluated the impact of the public procurement reforms on the economic development of Nigeria. We relied on documentary method of data collection and content analysis of data. Meanwhile, employing the basic propositions emanating from the Marxist theory of the Post-Colonial State, this study noted that the nature and character of Nigerian state undermined the procurement reform from achieving its expected goals. We however, recommended for the removal of the immunity in the constitution and strengthening of the anti-graft agencies in Nigeria.
Keywords: Corruption; Economic Development; Public Procurement; Reforms; Transparency

The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

LLCs and the Private Ordering of Dispute Resolution - Molk, Peter; Winship, Verity (The Journal of Corporation Law, 2016)
An emerging question in U.S. business law is how the organizational documents of a business entity set the rules for resolving internal disputes. This practice is routine in commercial contracts, which may specify where or how disputes must be resolved. Recent use of litigation provisions in corporation charters and bylaws have sparked controversy, ultimately leading to legislative action to preserve shareholder suits from contractual waiver. Yet despite accounting for the majority of business organizations and sharing features with corporations, non-corporate business entities and their internal dispute resolution process have been largely ignored. How do these non-corporate entities set ex ante rules for resolving disputes among their constituents? This paper begins to map this uncharted area with an empirical study of the practice of limited liability companies (LLCs). We find widespread use of contract to alter the default dispute resolution practices. This study helps not only to inform the evolving statutory and judicial framework for LLC regulation, but also to predict how corporations may respond in the future to recent judicial and legislative changes.
Keywords: Arbitration; Dispute resolution; Fee shifting; Forum; LLCs; Litigation; Operating agreements

Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

The CISG as a Model Law: A Comparative Law Approach - Chianale, Angelo (Singapore Journal of Legal Studies, 2016)
In this article I adopt a comparative law approach to illustrate the coexistence of various models governing the sale of goods, and their classification on the basis of two main characteristics: the transfer of property and the opposition certainty/flexibility. I use this approach to analyse the United Nations Convention on Contracts for the International Sale of Goods. 1 Then I examine how theCISG influenced several national systems and can influence future attempts at regional harmonisation. I conclude with the reasons that in my opinion make the CISG a good model for the sale of goods (prestige, equilibrium and derogability), and with the desirable future developments.

Teaching Transnational Commercial Law in the African Context - Eiselen, Sieg (University of Western Australia Law Review, 2016)

Private Ordering of Exit in Limited Liability Companies: Theory and Evidence from Business Organization Contracts - Gomtsian, Suren (American Business Law Journal, 2016)
https://onlinelibrary.wiley.com/doi/10.1111/ablj.12087

The Admission and Enrolment of Foreign Legal Practitioners in South Africa under the Legal Practice Act: International Trade Law and Constitutional Perspectives - Hagenmeier, Cornelius; Shumba, Tapiwa; Mireku, Obeng (Potchefstroom Electronic Law Journal, 2016)
Globalisation requires ever closer co-operation between legal professionals hailing from different national jurisdictions. This interactive global environment has fostered growing international training and mobility among legal practitioners and the internationalisation of legal education. Increasing numbers of law students get trained in other countries as part of their undergraduate degrees or even come to foreign shores to obtain law degrees. Many students hailing from other African countries study towardsLLBdegrees at South African universities. Major commercial law firms ensure that they can offer in-house expertise on major foreign legal systems and co-operate with partner firms in other parts of the globe. The General Agreement on Trade in Services (GATS), to which South Africa is a party, is a multilateral agreement focusing on the liberalisation of trade in services amongst member countries. Services under the GATS system include legal services. The commitments made by South Africa under this agreement require that South Africa allows foreign legal practitioners to establish a commercial presence or be transferred to South Africa. The Bill of Rights entrenched in Chapter 2 of the South African Constitution guarantees fundamental rights including the right to equality and freedom of trade, occupation and profession. With the coming into force of the new Legal Practice Act 28 of 2014, which provides a legislative framework for regulating the affairs of legal practitioners, including their admission and enrolment, it is necessary to assess the extent to which the Act complies with the GATS rules and the South African Constitution. This paper examines the new Legal Practice Act 28 of 2014, and examines whether the Act addresses the conflicts that have always existed between the regulation of the legal profession and the admission of legal practitioners in South Africa with South Africa's commitments under the GATS system. Using the doctrinal legal method, it analyses and evaluates the rules governing the admission of foreign attorneys in South Africa from two perspectives. First, it considers them in the light of the international law obligations of the country and second it evaluates whether or not they comply with the South African Constitution, and more specifically with the Bill of Rights entrenched in the South African Constitution. While the new legislation may assist in ensuring the compliance of South Africa with the relevant GATS rules, it will depend on the regulations which still have to be promulgated to what extent the new legal framework will achieve the full compliance of South Africa with all relevant GATS rules. The paper concludes with recommendations for the reform of the Legal Practice Act. It argues that while the requirement to be a South African permanent resident in order to qualify for admission as an attorney may be justifiable in terms of GATS and in terms of South African constitutional law, it is not in South Africa's best interest to retain it. Consequently, the paper calls for the repeal of the permanent residence requirement for admission as an attorney in the county.
Keywords: Affirmative action; Designated groups; Employment equity; Equality; Minority group; Multi layered disadvantage; Situation sensitive

Arbitration and Justice Denial on Foreign Direct Investment - Hendrawan, Daniel (Indonesian Journal of International Law, 2016)
The economic growth in Indonesia is thrive. The Economic growth can not be separate of the role of investment in Indonesia. The population in Indonesia very much and also the location of the Indonesian state strategic pretty much made Indonesia enjoyed by citizens of Indonesia itself and also foreign nationals who wish to also invest in Indonesia. In Indonesia there is a domestic investment and foreign investment. In this paper will be devoted to foreign investment. Foreign investment that currently exist in Indonesia has a sizeable amount and spread from Sabang to Merauke, and also has sometimes caused the dispute. Dispute occurs either the foreign investment by government or also foreign investment with other parties outside the government well with other foreign investment, and also in the company itself. Foreign investment dispute settlement is not only done through the court owned by the government, but there are also ways of alternative dispute resolution outside the court . One of the alternative dispute resolution outside the court is Arbitration. Arbitration carried out as part of efforts to achieve settlement of the problem in terms of investment activity . Arbitration itself is set in the legislation applicable investment in Indonesia . The parties in capital investment may create a separate section in the agreement governing the settlement of disputes in the case of investments completed by Arbitration. In the event that the parties have arranged to settle the case with Arbitration, then the court is not allowed to try again or to interfere in the decision Arbitration. Arbitration is one of the solutions if justice denial occur in the settlement of foreign direct investment issue.
Keywords: Alternative; Arbitrage; Arbitragem; Arbitration; FDI; Foreign direct investment

Regional Powers and Leadership in Regional Institutions: Nigeria in ECOWAS and South Africa in SADC - Hulse, Merran (KFG The Transformative Power of Europe, 2016)
Regional powers are not always benevolent leaders when it comes to the building of regional institutions. While powerful states – particularly the “new” rising powers – may have a vested interest in regionalism as a means of projecting influence, regional powers may behave as coercive or benevolent leaders, or alternatively display an absence of leadership altogether. The drivers of varying regional power behavior can be attributed to their competing concerns regarding (economic) power, functional efficiency, international legitimacy, and neopatrimonial networks. This paper explores the varying behavior of Nigeria and South Africa in relation to the institutionalization of free trade areas and regional courts within their respective regions. Nigeria has displayed little leadership in ECOWAS trade integration due to domestic opposition; however, a newly-democratic Nigeria’s search for international legitimacy drove the establishment of the ECOWAS Court of Justice. Likewise, South Africa’s search for legitimacy drove its support for the SADC Tribunal, but the competing demands of different audiences led it to abandon this support. South Africa has also displayed leadership in relation to the SADC Free Trade Area; however, its neighbors perceive it as a self-interested, almost coercive actor. The findings suggest that the motivations for regional powers’ behavior vary across time and policy sectors, and that inconsistent behavior is driven by a change in the priority granted to different drivers.
Accepted: 2018-06-08T11:13:32Z https://refubium.fu-berlin.de/handle/fub188/21860

Foreign Direct Investments and Economic Growth of African Regions: A Comparative Study - Igbinosa, Sunday O.; Ikponmwosa, Noruwa Abu (UNILAG Journal of Humanities, 2016)
The paper examines the impact of Foreign Direct Investments (FDIs)on economic growth in the five regions of Africa, as well as identifies their respective drivers of growth. It employs the Ordinary Least Squares (OLS) multiple regression analysis to examine the relative impact of Foreign Direct Investments, balance of payments, trade openness, technology and quality of labour force on economic growth in each of the five regions between 1980 and 2012. The study finds that foreign Direct Investments (FDIs) have no significant impact on economic growth in the five regions of Africa. The impact of FDI on growth is positive in Eastern, Middle and Western Africa but negative in Northern and Southern Africa. Similarly, there are differentials in the drivers of growth in the five regions. While trade openness is a negative driver of growth in all regions of Africa except in Northern Africa, both balance of payments and quality of labour force have mixed impacts on economic growth in Africa. In addition, technological progress impacted growth in Middle, Southern Africa and Western Africa but it appears that lack of it retarded growth in Eastern and Northern Africa. The study calls for policy reform frameworks that encourage and boost foreign Direct Investment flows to all regions of Africa, particularly Direct Investments in critical sectors of the economies, as well as check the negative effects of foreign Direct Investments. Furthermore, it recommends that regional economic blocks in Africa should be resuscitated and supported to develop and promote intra-Africa trade and Investments.
Keywords: African regions; Drivers of growth; Economic growth; FDI; Foreign direct investment; Investments

Contracts Governing the Use of Websites - Mik, Eliza (Singapore Journal of Legal Studies, 2016)
With the progressive transformation of the Internet from a romanticised instrument of freedom and self-expression into a commercial platform for digital distribution, most websites must be recognised as access interfaces to a wide range of content and services. This paper examines the contracts purportedly governing the use of such content and services. It explores the difficulties of establishing legal intention in a context that is not unambiguously commercial or transactional and contrasts popular beliefs with the basic principles of contract law. It draws a clear distinction between contracts governing traditional e-commerce exchanges, such as buying books on Amazon.com, and contracts governing the very use of websites. In the latter instance, the website (ie the resources made available thereon) constitutes the subject matter of the transaction. Equal importance must be attributed to the fact that such contracts are formed on websites and to the fact that they govern their use. The website user will question the existence of a contract on the basis that he did not have an intention to be legally bound, or had no awareness that a transaction was taking place. The website operator will argue that, objectively, all prerequisites of a legally enforceable agreement have been met. The outcome of the discussion will, to a large extent, depend on whether the user’s beliefs and expectations can be regarded as reasonable and on whether it is the user or the operator who deserves the protection of the objective theory of contract.

Democracy and Accountable Governance in the SADC Region - Omede, Jolade; Akindola, Rufus; Ngwube, Arinze (African Journal of Politics and Administrative Studies, 2016)
The call for democracy worldwide is based on the assumption that it allows citizens involvement on how they are governed. Being a representative system of government, democracy is projected to make political leadership responsive and responsible to the entire citizenry of the state. Southern Africa region has the most animated economy in sub –Sahara Africa, and democratic ideals appear more firmly established in the region compared to other regions in Africa. This has made the region, among others in the continent, the preferred choice of many migrants from different parts of the world. It is believed that the region has reached its Eldorado. However, a close observation of the politics of that region tends to suggest there has been the institutionalization of democratic rule without commensurate enthronement of responsible and accountable governance. This study systematically examined the political configurations of the region to concretely determine how the practice of liberal democracy in the sub-region has translated to accountable and responsible governance and its overall impact of the living standard of the citizens of the countries of that region. The paper examined accountable governance in the sense that leaders will be able to mange resource of the state for the well being of the populace. The reverse has been the case for the region. Southern Africa needs a developmental and capable state for socio-economic progress and sustainable democracy. This cannot be achieved without responsible political leadership, which would be responsive to the yearnings of the people. The mode of analysis was based on secondary sources and observation method. The paper adopted secondary and observation techniques as the mode of analysis
Keywords: Accountability; Democracy; Development; Governance; Leadership

International Trade, WTO and Economic Development - Siddiqui, Kalim (World Review of Political Economy, 2016)
This article examines the existing literature on trade liberalisation and its effect on the economies of developing countries. It will also briefly examine the theory of comparative advantage which is seen as justification for global trade liberalisation under the auspices of the World Trade Organization. This process is also associated with greater openness, economic interdependence and deepening economic integration with the world economy. The study is important because once again the international institutions strongly advocate trade and financial liberalisation in developing countries. The proponents of trade liberalisation argue that multilateral trade negotiations would achieve these goals, and poor countries particularly would benefit from it. However, such policies may increase vulnerability and make developing countries further hostages of international finance capital. Adoption of open market policies in agriculture would also mean the abandoning of self-reliance and food sovereignty, which may have wider consequences in terms of food shortages, food prices and rural employment.

Due Process of Law in International Commercial Arbitration with Special Reference to Production of Documents - Zaheeruddin, Mohammed (Journal of Law and Criminal Justice, 2016)
Arbitration provides speedy mode of settlement of disputes between the parties. In the course of arbitration, the arbitration tribunal has an obligation to give a fair opportunity to the parties to present their case. The fair hearing or due process of law in arbitration requires that both parties must be treated equally and given opportunity to be heard, which include a party may request the other party for production of documents, which are relevant to the case. Hence, the international arbitration rules contained the provisions to order a party, on its own or on the request of a party, to produce the documents relevant to the outcome of the case. Unless otherwise agreed by the parties, any denial of this opportunity may be considered as a violation of due process of law, consequently a party may challenge the enforcement of the award.
Keywords: Arbitrage; Arbitragem; Arbitration; Discovery; Due process of law; Production of document; UNCITRAL

Online dispute resolution: The future of justice - Mania, Karolina (International Comparative Jurisprudence, 2015)
The purpose of this study is to present the main facets of online dispute resolution, including a definition of the term, the types of resolution available, and the most recent legal regulations in this area. The article is an in-depth study of this field, discussing online mediation and electronic arbitration, their uses and their relationships with e-commerce. The strengths and weaknesses of online dispute resolution are identified and used to help formulate de lege ferenda stipulations. The paper is divided into three parts. Part I looks at preliminary aspects of online dispute resolution (ODR), including a definition of the term and an examination of its phases of development, implementation examples and the relationship between ODR and technology. Part II is devoted to examining the two most frequent forms of ODR: online mediation and electronic arbitration. Part III is an analysis of consumer disputes arising from commercial transactions made using electronic communications. As an example of the implementation of ODR, the author emphasises the importance of new European regulations on that and alternative dispute resolution (ADR): Directive 2013/11/EU of the European Parliament and of the Council of 21 May 2013 on alternative dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Directive on consumer ADR), and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21 May 2013 on online dispute resolution for consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC (Regulation on consumer ODR).
Keywords: ADR; Alternative dispute resolution; Consumer dispute; E-commerce; Electronic arbitration; ODR; Online Dispute Resolution; Online mediation

The Modern Travelling Merchant: Mobile Communication in International Contract Law - Schroeter, Ulrich G. (Journal of Law, Society and Development, 2015)
The use of mobile communication devices such as mobile phones, smartphones, tablet computers or notebooks with access to the internet has become an everyday phenomenon in today's business world. However, whenever mobile communications are used for the purposes of contract formation, that is, the mobile dispatch of offers or acceptances, the mobility of the communicating parties raises important difficulties for the application of traditional legal rules: The fact that messages transmitted via phone, email or SMS can be dispatched and received Â at virtually any Â place on Â earth challenges the categories of private international law and international contract law, which are based on the (unspoken) assumption that parties communicate from their home country. The existing legal framework for cross-border contracts therefore hardly takes into account the possibility that parties may move across borders, and that the place of their communications may accordingly vary.The present article addresses the legal difficulties and uncertainties that crossÂ border Â mobile communication Â raises under international rules of law. It elaborates on the traditional role of the site of communication in this context before scrutinising how 'mobility friendly' the provisions Â of the relevant Â conventions Â developed Â by the United Nations, the Hague Conference for Private International Law and other organisations Â are. In doing Â so, Â it critically Â discusses Â in particular article 10(3) of the UN Electronic Communications Convention of 2005, the most recent attempt at regulating mobile communications. Finally, it identifies a number of problems that have hitherto been overlooked (as notably the interaction of article 10(3) of the UN Electronic Communications Convention with traditional private international law rules on the formal validity of contracts) and proposes appropriate solutions.
Keywords: Conflict of laws; Contract law; Electronic communication; Electronic contract formation; Mobile communication; Place of contracting; UN Electronic Communications Convention; m-commerce

Policy Options for Promoting Foreign Direct Investment in the Least Developed Countries - Sauvant, Karl P.; Mallampally, Padma (Transnational Corporations Review, 2015)
Foreign direct investment (FDI) plays an important role in the world economy and has the potential to contribute towards accelerating the process of economic growth and sustainable development in the least developed countries (LDCs). The paper provides a brief overview of recent trends and patterns in FDI flows to the LDCs, and then takes stock of the policies, programmes and measures pursued by host and home countries and by international organizations to stimulate FDI flows to LDCs and increase their benefits for these countries. It then lays out a number of policy proposals on how flows to LDCs, and the benefits associated with them, can be enhanced. Finally, it outlines some options for international action to strengthen such efforts – proposals and options that are also relevant to other developing countries.
Keywords: Development; Foreign direct investment; Least Developed Countries; policy options

BRICS and Sub-Saharan Africa Trade Interdependence and Peace: Evidence Based on Revealed Comparative Advantages - Beyene, Hailay Gebretinsae (Journal of Law, Society and Development, 2015)
This study examined economic integration through trade between BRIGS (Brazil, Russia, India, China and South Africa) countries and sub-Saharan Africa. The study examines the comparative advantages of the two economic blocks with respect to the exportation of merchandise (food, agricultural raw materials, fuels, ores and metals, and manufactures). The findings of this study reveal the actual status of these two regions as economic partners in each of the five subsectors of merchandise exports.The Â trend Â shows Â that, Â with Â the Â exception Â of Â manufactures Â exports, the competitiveness of all subsectors of the merchandise Â exports ofÂ BRIGS is characterised by a Â declining Â trend. Â BRIGS has Â a Â comparativeÂ advantage in the world in the exportation of manufactures and fuels, and comparative disadvantage in the export of food, agricultural raw materials, and ores and metals. Â Interestingly, manufactures are Â continuously Â and consistently Â in a steadily rising trend. This is evidence that BRIGS's structural transformation towards higher valued-added commodities is proceeding well, which means that policy makers should be considering ways of enhancing it further.In the case of sub-Saharan Africa,Â with the exception of manufactures exports, it is found to have comparative advantages in all merchandise exports. Sub- Saharan Africaâ€™s competitive advantage is the highest in the exportation of ores and metals, followed by fuels, agricultural raw materials and food. Sub-Saharan Africa has a comparative disadvantage in the export of manufactures throughout the period considered in this study. This implies that the prospects of structural transformation to downstream of the higher value-added commodities export part of the supply chain are good: the slow pace of transformation towards higher value-added goods should therefore be demanding the attention of policy makers. The study has revealed that sub-Saharan Africa is more competitive than BRICS in the exportation of ores and metals, fuel, agricultural raw materials and food. On the other hand, BRICS is more competitive than sub-Saharan Africa in the export of manufactures.The study has also revealed that significant economic integration can be sustained Â between Â BRICS Â and Â sub-Saharan Â Africa Â in Â the Â exportation Â of all merchandise subsectors. Specifically, sub-Saharan Africa is a potential destination market for BRICSâ€™s exports of manufactures. Conversely, BRICS is also a potential destination market for sub-Saharan Africaâ€™s exports of ores and metals, fuel, agricultural raw materials and food.Economic integration between BRICS and sub-Saharan Africa favourably influences peace and stability in the regions. Sustaining peace and stability in these regions also favourably influences the wellbeing of the communities.
Keywords: BRICS; Economic integration; Sub-Saharan Africa; merchandise exportation; peace and stability; revealed comparative advantage; structural transformation

CISG and Regional Sales Law: Friends or Foes? - Coetzee, Juana (Journal of Law, Society and Development, 2015)
Economic co-operation and integration brings with it a need to harmonise mechanisms for the regulation of international trade, not only at a public-law level between states but also at a private-law level between traders inter partes. It is often forgotten that differences in the substantive law applicable to a contract function as a non-tariff barrier to trade. Because international trade facilitates economic development, the focus in this article is on the harmonisation of sales laws. Traditionally, private law harmonisation has been conducted by international private or inter-state organisations that specialise in the harmonising of law at a global level. Today, private organisations and groups devoted to harmonising business laws, as well as regional economic integration organisations, are also pursuing legal harmonisation. Global, regional and domestic laws now all exist in the same area of the law, which can give rise to duplication of efforts and problems with the co-existence of global and regional sales law. This article will discuss these issues with reference to the United Nations Convention on Contracts for the International Sale of Goods (CISG) and selected regional laws in considering whether regional harmonisation can act as a stepping stone towards increased harmonisation at a global level or whether it is to be viewed as a threat to global integration and harmonisation.
Keywords: CESL; CISG; Global harmonisation; Harmonisation of sales laws; OHADA; PACL; SADC; regional harmonisation

Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

Cooperative Movements in the Western Highlands of Cameroon - Jiotsa, Albert; Okia, Timothy Musima; Yambene, Henri (Revue de géographie alpine, 2015)
Cooperative societies in the Western Highlands (West and North West regions) of Cameroon is an age old institution which started with the arrival of the European colonialists towards the end of the nineteenth century. The fertile soils of this region favors agricultural activities thereby giving rise to many cooperatives in the region. The cooperative societies that have been developed in these areas are the type found in sub Saharan Africa which has stood the test of time more than half a century whereby the other cooperatives elsewhere in the same country have failed. The question this article is about to provide answers is to what has made these cooperatives in the Western Highlands of Cameroon able to stand the test of time when others are quitting the scene. To come out with this scientific article we have implored the active participatory research methodology. The analysis shows that these cooperatives since their creation have been imploring certain innovative measures to make them adapt to the many constraints in their sector.
Number: 103-1
Keywords: Cameroon; adaptation strategies; constraints; cooperative movements; highlands

Law and Development in West and Central Africa OHADA - Winship, Peter (SMU Dedman School of Law Legal Studies Research Paper, 2015)
This seminar paper considers whether OHADA - an experiment in unifying business law in African countries - has been a success. Following a prologue that explains the origins of the paper, the first part of the paper sets out basic information about the Organisation pour l’Harmonisation du Droit des Affaires en Afrique (“Organization for the Harmonization of Business Law in Africa,” known by the acronym OHADA). This part is followed by a review of law and development literature to assess the value of this literature for an evaluation of the success (or not) of OHADA. A third part then focuses on one specific uniform law, the law of secured transactions. The paper concludes that notwithstanding challenges the OHADA institutions exist and have produced uniform business laws for the formal business sector. Whether OHADA has been the cause of increased investment and trade requires studies that have not been carried out.
Keywords: African law; Secured transactions; commercial law; law and development; law reform; unification of law

Toward an Elaboration of a More Pluralistic Legal Landscape for Developing West African Countries: Organization for the Harmonization of Business Law in Africa (OHADA) and Law and Development - Hiez, David; Menétrey, Séverine (The Law and Development Review, 2015)
In Europe and especially in France, the African business law landscape, as well as the legal discourse, for developing West African countries is almost exclusively dedicated to OHADA, the Organization for the Harmonization of Business Law in Africa, created in 1993. While economic development in the Member States is the obvious underlying reason for the modernization and unification of African business law, the exact nature of such development remains uncertain, as does the manner in which a such result can or will be achieved. OHADA’s Uniform Acts are, with some minor exceptions, a carbon copy of French business law. The only goal is to increase international investment, which, in turn, is expected to generate economic development, but all without taking any notice of equality or social justice issues. That, without a doubt, is the reason why OHADA is constantly criticized as a law that benefits foreign investors, while remaining ineffective, even illusory, for local traders. To go beyond the criticism, the authors have decided to focus on the relationship between law and the informal sector and to draw lines between formal and informal rules in the business sector.
Keywords: Informal rules informal sector; OHADA (Harmonized Business Law in Africa); informal rules; informal sector

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Challenges of Transnational Trademark Law Practice: The Case of Nigerian Companies’ Brands in OAPI States - Nwabueze, Caroline (Revue générale de droit, 2015)
Nigeria industrial growth has turned the country into an indispensable economic support for its neighbours. Only for the case of Cameroon, Nigeria has been the leading supplier with respectively 22% and 17.8% of imports in 2011 and 2012 with trade amounting to 328 billion FCFA per annum. This results in part from Nigerian companies’ exportations in local markets. Nigerian trademarks related to cosmetics, furniture, electronics, and pharmaceutical goods abound in neighbouring countries. However, a strengthening of Nigerian companies in regional markets encompasses strategies to avoid infringing on the trademark rights. Such strategies should include the consideration of special trademarks features by different institutions of the intellectual property (IP) system in the relevant neighbour export markets. This is by the mere fact that the legal status of those goods, although physical property, relies mainly on the material law applicable, which is trademark in the present case. Because the principle of territoriality requires that trademark protection be sought in the place where the goods are sold—and trademark applications filed in each country in which protection is sought—, Nigerian companies planning to outsource some business activity in neighbour markets will seek compliance with trademarks norms applicable in the Organisation africaine de la propriété intellectuelle (OAPI) of which those countries—Benin, Cameroon, Chad, and Guinea—are part. The trade partnership between companies from a common law trademark background on one hand, and civil law intellectual property community on the other, inevitably raises some frictions and trademarks issues. This article analyses the trademark challenges arising from Nigerian companies’ business decision to enter OAPI markets and export goods and services. The article firstly underlines the issues to be taken into consideration, including registration and enforcement of the companies’ marks in OAPI. Then the paper simultaneously reviews the dissimilarities issues between the Nigerian Trademark Act and the OAPI Trademark System to which the Nigerian companies are confronted. If trademark protection makes it easier for an enterprise to access transnational markets, the establishment of a Trademark Community with neighbouring countries helps for sure national industries to establish partnerships with other firms for sustainable development in the areas such as production, marketing, distribution or delivery of goods and services. In light of the trademark harmonisation in the European Union internal market, the present paper concludes by recommending the creation of a Trademark Community in the West and Central African region between Nigeria and its neighbouring countries. La croissance industrielle du Nigeria a fait de ce pays un soutien économique indispensable pour ses voisins. Pour ne citer que l’exemple du Cameroun, le Nigeria en a été le principal fournisseur avec respectivement 22 % et 17,8 % des importations en 2011 et 2012 et des importations dont la valeur s’élève à 328 milliards fr. cfa par année. Ceci résulte en partie des exportations des compagnies nigérianes vers les marchés locaux. Les marques de commerce nigérianes dans le domaine des cosmétiques, des meubles et des produits électroniques et pharmaceutiques abondent dans les pays voisins. Cependant, le renforcement des compagnies nigérianes dans les marchés régionaux englobe des stratégies pour éviter d’enfreindre les droits de propriété industrielle et commerciale. Dans le cadre de ces stratégies, les différentes institutions qui régissent la propriété intellectuelle (PI) dans les marchés d’exportation des pays voisins pertinents devraient prendre en compte des caractéristiques particulières relatives aux marques de commerce. Ne serait-ce que du simple fait que le statut juridique de ces produits, bien qu’ils soient des biens physiques, repose principalement sur le droit substantiel applicable, le droit de la marque de commerce dans ce cas. Parce que le principe de territorialité nécessite que la protection de la marque de commerce soit demandée dans le territoire où les biens sont vendus, et que cette protection doit être demandée dans chaque pays individuellement, les compagnies nigérianes qui prévoient externaliser des activités commerciales dans des marchés voisins chercheront à se conformer aux normes en matière de marques de commerce qui sont applicables au sein de l’Organisation africaine de la propriété intellectuelle (OAPI), dont font partie le Bénin, le Cameroun, le Tchad et la Guinée. Le partenariat commercial entre des entreprises soulève inévitablement, et ce, tant du point de vue de la common law que celui du droit civil, des frictions et des problèmes lorsqu’il s’agit de marques de commerce. Le présent article analyse les défis relatifs aux marques de commerce découlant de la décision commerciale des entreprises nigérianes de faire leur entrée dans les marchés de l’OAPI et d’y exporter des biens et services. L’article souligne premièrement les problèmes qui doivent être pris en considération, dont l’inscription et la mise en application des marques des entreprises membres de l’OAPI. Ensuite, ce texte examine simultanément les problèmes résultant des différences entre la Nigerian Trademark Act et le système de marques de commerce de l’OAPI, système auquel les entreprises nigérianes sont confrontées. Si la protection des marques de commerce facilite l’accès aux marchés transnationaux pour les entreprises, la mise en place, avec les pays voisins, d’une communauté en matière de marques de commerce aide assurément les industries nationales à établir des partenariats avec d’autres entreprises dans le but d’assurer un développement durable dans des domaines tels que la production, la commercialisation, la distribution ou la livraison de biens et services. À la lumière de l’harmonisation des marques de commerce dans le marché intérieur de l’Union européenne, le présent article conclut en recommandant la création d’une communauté de marques de commerce dans la région de l’Afrique occidentale et centrale, et qui réunirait le Nigeria et ses pays voisins.
Keywords: Afrique occidentale; Commerce transnational; Communauté de marques de commerce; Community trademark; Compagnies nigérianes; Enforcement; Intellectual property; Marque déposée; Mise en oeuvre; Nigerian companies; OAPI; Principe de territorialité; Principle of territoriality; Propriedade intelectual; Propriété intellectuelle; Trademark practice; Transnational trade; Western Africa

Corporate Social Responsibility , Oil Exploration and the Niger Delta Question - Obi, Emeka Anthony (Oman Chapter of Arabian Journal of Business and Management Review, 2015)
The intricate relationship between corporate organizations and their environment is one that is supposed to be based on mutual interdependence. This is because the organization depends on the environment for its inputs, while the environment also needs the organization for its sustenance. This therefore calls for a symbiotic relationship between them. It is this realization that gave birth to the concept of Corporate Social Responsibility (CSR). This paper tries to look at the application of the concept as it concerns the oil companies operating in the Niger Delta region of Nigeria within the ambit of the Niger Delta question. The study employs the systems theory as an analytical framework. It tries to situate the concept of CSR within the general neglect by successive governments of this region that sustains the entire Nigerian state. The implication of the above is that a better understanding of the problem of CSR in the Niger Delta region becomes easier when juxtaposed with the attitude of the Nigerian state towards the region over the years. It is the summation of the paper that the oil companies have not been very proactive in this regard and as such have been perceived by their host communities as enemies and exploiters instead of partners. The study concludes by insisting that while the oil companies should be more proactive, the government on her part should step up the tempo in ameliorating the deplorable condition of the golden goose.
Keywords: CSR; Corporate Social Responsibility; RSE; Responsabilité Sociale de l'Entreprise

Stuck in a time warp: security interests in chattel mortgages and the bills of sale legislation in Nigeria - Otabor-Olubor, Iyare (International Company and Commercial Law Review, 2015)
IRep - Nottingham Trent University's open access institutional research repository
Number: 11

CISG and the freedom of form principle vs. reservations under Article 96 of the CISG - Pohl, Małgorzata (Transformacje Prawa Prywatnego, 2015)
This article aims to present the consequences of a state’s declaration to opt-out from the freedom of form principle, under article 96 of the united nations Convention on Con tracts for the international sale of goods 1980 (CISG). In practice, problems have developed as whether or not to apply the freedom of form when a contract is concluded between two business entities, where one has its place of business in an article 96 CISG reservation state, and the other does not. The issue concerning the reservation’s effects has led to the creation of “two schools of thought” established by the doctrine and case law in this respect. it is the author’s intention to present the proper methodology of the interpretation and application of articles 12 and 96 CISG bearing in mind the various opinions in this respect. In the author’s opinion, in such situations the court should follow the rules of private international law to seek an answer as to whether or not the obligation of written form applies. Some of the CISG Contracting states that currently maintain an article 96 Cisg dec laration, refrain from withdrawal of their declaration despite the fact that the prerequisites for such a reservation are no longer met, as their domestic legal systems do not impose a written form requirement, as was the case at the time when the Cisg was negotiated. In the author’s opinion, in cases where the rules of private international law point to the law of such a state, the courts should, in practice, refrain from following the article 96 Cisg reservation, i.e. no freedom of form, and should instead apply the less formal domestic law as to the form.

More than 25 years of the contracts for the international sale of goods (CISG): Rethinking the role of the CISG in the SADC region - Shumba, Tapiwa (Speculum Juris, 2015)
The Convention on Contracts for the International Sale of Goods (CISG) has proved popular, particularly outside Africa. However, only a few States have adopted it in Africa, with only two in the Southern African Development Community (SADC). Taking into account the role that African countries have played in the United Nations Commission on International Trade Law (UNCITRAL) and the creation of the CISG, it has always been pertinent to look at whether SADC Member States should adopt the CISG as an instrument for harmonising the law of international sales in the region. Since it came into force, only two SADC Member States (Lesotho and Zambia) have ratified the convention. There is apparent reluctance from the rest of SADC Member States to ratify the convention despite calls to that effect and the genuine need for legal harmonisation. The article revisits the call for the ratification of the CISG in SADC and considers other realistic alternatives to ratification.

A Standing Question: Mortgages, Assignment, and Foreclosure - Zacks, Eric A; Zacks, Dustin A (The Journal of Corporation Law, 2015)
“Banks are neither private attorneys general nor bounty hunters, armed with a roving commission to seek out defaulting homeowners and take away their homes in satisfaction of some other bank’s deed of trust.” This Article examines the judicial treatment of mortgage assignments across various jurisdictions in the foreclosure context. Although some courts do permit debtors to challenge suspicious or problematic assignments, most have ignored such problems and denied standing to debtors attempting to assert assignment-based defenses. This is particularly surprising given the widespread and well-documented problems with foreclosure “robo-litigation,” including backdated documents, fraudulent notarizations, and unauthorized signatures. Despite the abuse of process by foreclosing entities, courts have permitted foreclosures to continue unabated and, in some instances, have even precluded the possibility of discovery to debtors seeking to ensure that title and assignments are legally valid. Judicial ambivalence about formal compliance by mortgage assignors and assignees in the foreclosure context is somewhat ironic given most courts’ routine enforcement of instruments against debtors who do not formally comply with all contractual terms. Current adjudicative approaches to mortgage assignment are seemingly disconnected from the devastating reality of the home mortgage crisis and its causes. Moreover, there are several rationales that would support a more robust enforcement of technical compliance with assignment procedures, including the need for procedural equity, title certainty, and public records integrity. Thus, as evidence exists that banks are still making many of the same problematic mistakes regarding transfer documentation, courts can perform an essential monitoring role as an important spur towards reform. Although it would not address all of the underlying causes of the housing crisis, an adjudicative approach that liberally permits challenges to mortgage assignments would encourage lenders and servicers to be more circumspect in their foreclosure processes.

Law and Development à L'Africaine: Evidence from the OHADA's Harmonization Process - Simo, Regis Yann (African Yearbook of International Law, 2014)
Until recently, doing business in developing countries, and in Sub-Saharan Africa in particular, was associated with high risk. Although each investment decision is associated with some risk, there are always obligations incumbent on host States in that regard. However, when domestic law is too obsolete to match the requirements of an evolving investment and commercial environment which it is supposed to regulate, and when its effects are unpredictable, one of the fundamental conditions for attracting investment goes missing. This eventually underscores the need for a legal reform. The phenomenon of 'globalisation' on the one hand, and the need for (developing) countries to integrate their economies into the global market, on the other hand, considerably accentuated the postulate of development through law.Against this background, some African countries, at the dawn of the 1990s, felt a need to 'modernise' their legal systems for the major part inherited from colonialism. In this vein, they entrusted a supranational organ, the OHADA, to perform that legal reform. This paper is an attempt to test the OHADA against the discourse of law as a development engine. Furthermore, this is an assessment of the extent to which OHADA, as a legal tool, could be useful in serving the purpose of regional integration and economic growth in Africa.
Keywords: Africa; Comparative Law; Law and Development; Law and economics; Law and finance; OHADA

The effects of the South African anti-dumping and competition measures upon foreign direct investment - Sibanda, Omphemetse S. (Journal of Business and Retail Management Research, 2014)
Since the dawn of democracy South Africa has embarked in a process of dismantling protectionist business and trade policies, and made the country’s stream of commerce one of the preferred globally. The country’s sound competition and trade policies, natural resource endowments, market size and regional influence, attracted foreign businesss and foreign direct invetsment (FDI). Equally the country has been under pressure to protect the domestic industries from injurious competition and business, through sector specific laws, anti-dumping and countervailing duties laws, investment and competition regime. The concern has been the likilelihood of the introduction of trade and competition barriers, and the allienation of FDI. This paper critically examines the impact the country’s antidumping and competition law and practice upon foreign direct investment. Domestic industries have never been shy to file anti-dumping and anti-competition suits against foreign companies, sometimes even when there might be a public outcry. Relevant examples of these suits include the famous Wal-Mart anti-competition case, and recently the Brazilian frozen fowl meat anti-dumping case.
Keywords: Anti-Dumping; Competition; Consumers; Divestment; Domestic Industry; Investments; Protection; Tariffs

Harmonising Public Procurement in the SADC - Harpe, Stephen de la (Journal of Law, Society and Development, 2014)
The promotion of international trade is seen as one of the important instruments to ensure development in developing nations and regions. The history of the World Trade Organisation (WTO) and the drafting of many regional and similar international trade agreements are evidence of this. The Southern African Development Community (SADC) is no exception.1 It is therefore strange that many states that are members of the WTO and actively encourage the opening up of international borders to free trade do not include public procurement2 in such free trade arrangements. This is particularly evident in developing states. If the WTO Government Procurement Agreement (GPA), which is a plurilateral agreement, is considered it is clear that many states do not wish to open their internal markets to competition in the public procurement sphere. It is therefore not surprising that public procurement has been described as the last rampart of state protectionism (Ky, 2012). Public procurement is an important segment of trade in any country (Arrowsmith & Davies, 1998). It is estimated that public procurement represents between 10% and 15% of the gross domestic product (GDP) of developed countries and up to 25% of GDP in developing states (Wittig, 1999). Unfortunately, governments often expect private industry to open up national markets for international competition but do not lead the way. Except for the limited use of pooled procurement,3 no specific provision is at present made for the harmonisation and integration of public procurement in the SADC. In view of the proximity of the member states, the interdependency of their economies and the benefits that can be derived from opening up their boundaries to regional competition in public procurement, the possibility of harmonisation and deeper integration in this sphere needs to be given more attention. The importance of public procurement in international trade and regional integration is twofold: first, it forms a substantial part of trade with the related economic and developmental implications; secondly, it is used by governments as an instrument to address socio-economic issues. Public procurement spending is also important because of its potential influence on human rights, including aspects such as the alleviation of poverty, the achievement of acceptable labour standards and environmental goals, and similar issues (McCrudden, 1999). In this article the need to harmonise public procurement in the SADC in order to open up public procurement to regional competition, some of the obstacles preventing this, and possible solutions are discussed. Reference is made to international instruments such as the United Nations Commission on International Trade Law (UNCITRAL), the Model Law on Public Procurement and the GPA. In particular, the progress made in the Common Market for Eastern and Southern Africa (COMESA) with regard to the harmonisation of public procurement, which was based on the Model Law, will be used to suggest possible solutions to the problem of harmonising public procurement in the SADC.

Political and Economic Integration in the SADC: Reforming the Energy Sector Regulatory System - Jobodwana, Z. Ntozintle (Journal of Law, Society and Development, 2014)
The Southern Africa Development Community (SADC), the African Union (AU) and other African regional economic communities (RECs) have as their ultimate objective the political and economic integration of the African continent. The SADC is home to a number of countries, all of them striving to improve their investment climate to attract foreign investors by reducing the costs of doing business in the region. One way of achieving this is by setting targets for and speeding up political and economic integration, improving interconnectivity and thereby enlarging the market size and enhancing its attractiveness. The SADC region still suffers from high levels of energy poverty through low access levels in all countries except South Africa and Mauritius. Numerous studies have shown that greater regional trading and cooperation on power development within the SADC could substantially reduce investment and operational costs as well as carbon emissions. The need for a regional power trading pool and regional cooperation grew out of the power utilities’ recognition of the vulnerability of individual countries if each continued to pursue a policy of self-sufficiency rather than out of a desire to minimise the social or financial costs of the region’s power. The power sector in southern Africa is undergoing tremendous reforms, more especially since the establishment of the Southern African Power Pool (SAPP) in August 1995. The SADC, however, faces serious challenges that include diminishing surplus generation capacity and the need to ensure that SADC citizens have equitable access to electricity at affordable prices. To meet these challenges, treaties and protocols have been adopted but are failing to deliver at the implementation stage. This article reviews the SADC energy-electricity regulatory framework in the context of economic and political integration and recommends the establishment of an independent regional regulatory authority to oversee the implementation of integrated holistic energy and air pollution control and prevention, and a common climate change policy. Such a regulator would be a highly resourced regional institution that will liaise with international institutions. This independent regional authority will serve as a catalyst for regional economic integration. It will also have a mandate to introduce and coordinate the establishment of an SADC regional emissions trading scheme that will contribute to managing the mitigation of greenhouse gases (GHGs) and the implementation of global warming adaptation strategies in the region.
Keywords: Climate change; Economic integration; Energy regulation; GHGs; Global warming; Political integration; Regional independent regulatory authority; SADC; SAPP; Treaty regime; UNFCCC

Employees Contract of Employment and Wrongful Dismissal From Service - Ugbele, Sunday; Utobo, O. J. (African Journal of Politics and Administrative Studies, 2014)
Contract of employment was long acknowledged as a subject of genuine and voluntary agreement whose construction or determination should be founded on due notice of the parties thereto. Action for wrongful dismissal would lie if an employment was disturbed, interfered or meddled with, in defiance of the rights of the parties under the contract. The objective of this study was, among others, to determine what constituted a valid contract of employment and remedies for wrongful dismissal. The qualitative and documentary method of data collection was adopted by reference to relevant literature and statutory authorities. From the data gathered, and content analyzed, we found that no law could foreclose an employment from determination, nor could an irregular or wrongful dismissal stand. It was recommended, inter alia, that beside the need to repeal the Public Officers (Protection) Act, both the employer and employee should, in their official dealings, respect the sanctity of their contract, and permit reasonable future modifications thereto as could lawfully enhance the life of the contract and their legitimate desires.

The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration

Modernizing and harmonizing international contract law: the CISG and the Unidroit Principles continue to provide the best way forward - Dennis, Michael J. (Uniform Law Review, 2014)

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

Globalization and Private International Law in Commonwealth Africa - Oppong, Richard (University of Arkansas at Little Rock Law Review, 2014)

Alternative Dispute Resolution (ADR): An Overview of Some Common Mechanisms, and their Strengths and Weaknesses in Context - Perrin, Harry (The Plymouth Law & Criminal Justice Review, 2014)
Alternative Dispute Resolution, or ’ADR’, offers parties in dispute an alternative to traditional court-based litigation, which is often seen as slow, costly and ineffective. ADR frequently involves a neutral third party who will settle or facilitate resolution of the dispute. This paper examines three common ADR mechanisms, adjudication, arbitration and mediation, and explores their relative advantages and disadvantages in different contexts.
Keywords: ADR; Adjudication; Alternative dispute resolution; Arbitration; Construction adjudication; Mediation; Negotiation

Three theories of Lex Mercatoria - Cuniberti, Gilles (Columbia Journal of Transnational Law, 2014)

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE

The advent of OHADA Cooperatives companies - An Insight into management control - Monkam, Cyrille (Revue de l'ERSUMA, 2013)
The stability of a cooperative society depends in part on the effectiveness of its leaders. To maintain this efficiency, management actions are always subjected to control by a number of people and structures that have been assigned by the legislature. They have a preventive control (consisting of an alert procedure and management expertise) and accounting control whose main goal remains the search for transparency in the management of social affairs. The guarantee of this transparency is achieved by the various sanctions that threaten managerial leaders in both their personal property and their freedom. This threat will make the cooperative a viable economic entity and also protects the interests of its members.
Keywords: Control; Cooperatives leaders; Interest; Management; Sanctions; Transparency

The Proposal for a Common European Sales Law And the Convention on the International Sale of Goods: Friends or Foes? - Calomme, Caroline (Europeanisation of Private Law, 2013)
This essay examines the relationship between the proposal for a Common European Sales Law and the Convention on the International Sale of Goods in B2B transactions and its future outcome on the law applicable to international commercial transactions: friends or foes? In order to do so, the analysis is comprised of six elements. The first section asks what threat the legal relationship between the two instruments poses. The second section evaluates how and to which extent business behaviour plays a role in the reliance on optional instruments. The next section inspects the level of achievement of the CISG from a diplomatic, legal and business perspective. Subsequently, the consequences of the European instrument on the legal environment are explored. Next, a series of examples illustrate whether the relationship between the two instruments is one of competition or of cooperation. Lastly, the future prospects for both instruments are looked at. In the end of this research, it is submitted that the CISG will enhance the chances of success of the CESL in the long term even though it is likely to affect its popularity for commercial transactions in the short term. Reversely, the CESL will pose a threat to the CISG in the beginning but it will progressively encourage the modernisation of international trade law instruments.

Law harmonization and local specificities – a case study: OHADA and the law of contracts - Fontaine, Marcel (Uniform Law Review, 2013)
Unifying or harmonizing the laws of different countries means replacing, to respective degrees, the existing national laws with common rules.1 The merits of law unification or harmonization may seem to be obvious. They have been repeatedly described. Law diversity is an obstacle to trade between countries. Engaging in a commercial operation with a partner of another legal system immediately raises the question of which law will govern the relationship, with the consequence that, for one of the parties, the contract will be subject to unfamiliar rules (perhaps even for both parties if the law of a third party is determined to be applicable).

Some reflections on the prospects for the harmonization of international business laws in Africa : OHADA and beyond - Fombad, Charles Manga (Africa Today, 2013)
The evidence of developments in the harmonization of international business laws shows that Africa is lagging seriously behind. There are still some skeptical voices about the need for and the value of harmonization of international business laws, but such voices are now in a minority. The aim of this paper is to assess the prospects for harmonizing international business laws in Africa. The main contention is that the debate today in Africa is not whether or not there should be harmonization of international business laws, but how this should be done. The paper reviews the imperatives for harmonization and the options that exist and then focuses on the present approach to harmonizing business laws in Africa under the auspices of the Organization for the Harmonization of Business Laws in Africa, better known under its French acronym, OHADA. Based on the critical review of the weaknesses and strengths of the OHADA regulatory framework, the paper suggests ways in which the agenda to develop a harmonized and modern set of business laws in Africa can be achieved.

Some perspectives on durability and change under modern African constitutions - Fombad, Charles Manga (International Journal of Constitutional Law, 2013)
A major cause of political and constitutional instability in post-independence Africa was the ease with which political leaders subverted constitutionalism by arbitrarily changing constitutions to suit their political agendas. During the constitutional reforms of the 1990s many provisions were introduced in most African constitutions aimed at limiting the ability of governments to abusively change constitutions. Because of the critical importance of controlling the process of constitutional change to entrenching constitutionalism, this paper attempts to critically examine and analyze some of the different control devices that have been introduced. The objective is to see to what extent they may help not only to promote constitutionalism but also enhance constitutional durability and stability. The first part considers why it is important for constitutional designers to include special procedures to regulate and control the constitutional amendment process. The second part examines the different amendment patterns in a number of selected African countries. The third part considers the practical implications of the various control devices in terms of their actual and potential impact on the nurturing and growth of constitutionalism on the continent. The paper concludes that although there has been some progress, more changes still need to be introduced to check the problem of arbitrary constitutional change in Africa.

Investment Protection in the Framework of the Treaty of Harmonizing Business Law in Africa (OHADA) - Houanye, Paulin; Shen, Sibao (Beijing Law Review, 2013)
A few years ago, African contribution of the world trade was only around 2%. The investors, except those who are exploiting natural resources, never want to dare dispensing their fund in Africa. The reason of this situation was very simple. The majority of investors denounce the juridical insecurity and also the political preponderance across the African continent. With human and natural resources abundant, Africa is regarded as a continent equipped with a great potential of development. The years of independences in Africa saw being born in many States, of the organizations trying to solve these difficulties and to reinforce their capacities by the constitution of international organizations acting in all the fields. But it is only in the year 1990; some organizations appeared in the continent and knew of real rise thanks to the liberal and democratic economic policies. This article wishes to present an assessment of seventeen years implementation of the African Harmonization of Business Law Treaty of 1993. Firstly, it will describe the system from an institutional point of view and hence from a normative point of view. Secondly, during the course of this essay, there will be a focus on analysis of OHADA’s laws, its system and its potential impact. In addition, the article will concentrate on OHADA’s appropriateness in the business sector and necessary guarantees it must offer for a successful investment partnership with foreign investment.
Keywords: African Development; Harmonization; Harmonization Business Law; Investment Law; Investments; Regional integration; Rule of Law

Common Court of Justice and Arbitration: A Supranational Institution for the Administration of Commercial Disputes in Africa - Ogwezzy, Michael C. (Nordic Journal of Commercial Law, 2013)
Due to the expansion of business transaction across the globe, the private sector demands an adequate legal framework that is sufficiently clear, modern, predictable and transparent to permit investment with a sense of security. The Organisation for the Harmonisation of Business Law in Africa (Organisation pour l’harmonisation en Afrique du Droit des Affaires) is generally known by its French acronym OHADA. As long-standing idea, the foundation of the OHADA Treaty was first laid during a meeting of finance ministers of the members of the franc CFA1 area held in Ouagadougou, Burkina Faso, in April 1991. A group of experts, led by Senegalese Justice Keba Mbaye, was appointed to conduct a feasibility study on a form of legal collaboration designed to promote economic integration and attract investments.2 Identifying low investment as a major obstacle to economic growth, Keba Mbaye presented his report to the French-speaking African summit in Libreville, Gabon, in October 1992, recommending the creation of a supranational organization comprising the entire franc area. The recommendation was adopted and a steering committee of three experts were appointed and tasked with drafting an international instrument as well as identifying the areas of law to be harmonized. The OHADA was established through the treaty of Port Louis in Mauritius on 17th October, 19933 The treaty is open to any Member State of the Organization of African Unity (AU) as well as any other non-member of the AU invited to join with the common agreement of all the Member States.4 The OHADA has progressively become the common business law in anglophone and francophone African countries, taking the best from the civil law and the common law systems.5 The OHADA provides its Member States with 1) a single, modern, flexible and reliable business law adapted to each country’s economy; 2) arbitration as an appropriate and trustworthy way to settle disputes; and 3) an opportunity for training judges and judicial staff and ensuring their specialisation. In May 2003, the uniform OHADA business law came into force in the sub-Saharan African States of Benin, Burkina Faso, Cameroon, Central African Republic, Comoros, Congo, Ivory Coast, Gabon, Guinea, Guinea Bissau, Equatorial Guinea, Mali, Niger, Senegal, Chad, Togo and later the Democratic Republic of the Congo. The OHADA Treaty secures a legal framework for the conduct of business in Africa.6 Pursuant to Article 53 of the OHADA Treaty, any member State of the African Union may become a member, if it wishes to do so.7 Many countries are currently giving active consideration to joining the OHADA common system of business law.8 Most of the countries have a French colonial heritage, with the exception of the Democratic Republic of the Congo (former Belgian colony), Guinea-Bissau (former Portuguese colony), Equatorial Guinea (former Spanish colony), and Togo and Cameroon (formerly under partly British and partly French colonial rule). French is also an official language in most of the countries and many OHADA sources are only available in French. 9 It is interesting to know that the Council of Ministers of the OHADA organisation which is the legislative organ of the organisation have adopted the following uniform business law: the general commercial laws, corporate laws and rules concerning different types of joint ventures, laws concerning secured transactions, debt recovery and enforcement laws, bankruptcy laws, arbitration law, accountability law, and law regulating contract for the carriage of goods by roads.10 The OHADA treaty established the Common Court of Justice and Arbitration (CCJA) which is a supranational11 judicial institution based in Abidjan, Ivory Coast.12 2.
Number: 2

The Problem of the Taxation of Internet Transactions - Asada, Dominic (Current Jos Law Journal, 2013)
Accepted: 2017-08-16T12:06:13Z

Common Problems Affecting Supranational Attempts in Africa: An Analytical Overview - Fagbayibo, Babatunde Olaitan (Potchefstroom Electronic Law Journal, 2013)
Ever since the colonial era, attempts have been made throughout the various regions of Africa at building supranational units chiefly for administrative and legal convenience. Examples of such attempts include the Federation of Rhodesia and Nyasaland, the East African High Commission and the federations in former French West and Equatorial Africa, all of which were attempts at forging a supranational nation state. These experiments laid the foundation for further supranational initiatives in post-colonial Africa. In this respect, every region in Africa has either experimented with or is currently experimenting with the idea of supranational regional organisations. This article aims at investigating selected attempts at supranationalism on the continent, the successes and failures of such experiments, and the lessons to be learnt from them. As Africa embarks on the journey of solidifying its unity through the establishment of leviathan continental institutions, efforts should be geared towards building on the experiences of past and present experiments at the sub-regional level. Such experiments offer instructive lessons as they are rooted in similar historical and social contexts.
Keywords: African integration; Central African Economic and Monetary Community; East African Community; Economic Community of West African States; OHADA; Southern Africa Customs Union; Supranationalism; West African Economic and Monetary Union

Development of a uniform insolvency law in SADC : lessons from OHADA - Leno, Ngaundje Doris (Journal of African Law, 2013)
This article argues that, with the global or cross-border nature of many corporate activities, there is an increasing need for a uniform insolvency law approach to the financial distress of a corporation in the Southern African Development Community. In doing so, the article highlights lessons the community may learn from the Insolvency Act of the Organisation for the Harmonization of Business Law in Africa. Emphasis is given to that organization’s success in developing a uniform insolvency act (ie one which is directly applicable in its contracting states). The article also proposes a number of recommendations.
Accepted: 2014-02-28T11:57:54Z
Keywords: Africa; Bankruptcy; Business law; Financial distress; Insolvency Act; Insolvency law

The Quest for a Supranational Entity in West Africa: Can the Economic Community of West African States attain the Status? - Lokulo-Sodipe, Jadesola O.; Osuntogun, Abiodun J. (Potchefstroom Electronic Law Journal, 2013)
To reflect the growing trends in the international scene and in furtherance of the objective of its Revised 1993 Treaty, the Economic Community of West African States (ECOWAS) summit in December 2006 revolutionised the structure of ECOWAS by re-designating the Executive Secretariat into a quasi-independent commission headed by a President with a Vice President and seven commissioners. The rationale behind the revision was to make ECOWAS a supranational entity. This article considers whether or not a supranational system is essential for the attainment of ECOWAS' objectives. It asks if the conditions for an effective supranational system are in place in the West African sub-region which could provide a solid foundation for its success and why the quest for a supranational system has not yielded any fruitful result in West Africa. It argues that a retreat from the quest for supranationalism and a return to an inter-governmental system would be a retreat rather than the way forward, and expresses the need for the course of action to be sustained courageously till the impact of integration begins to emerge, and the disguised, patriotic impulse of states to protect their national sovereignty gives way to the full manifestation of ECOWAS as a supranational entity.
Number: 3
Keywords: Community Court of Justice; ECOWAS Commission; Intergovermental organisation; Regional integration; Supranational entity

Written Arbitration Agreements: What Written Arbitration Agreements? - Yu, Hong-Lin (Civil Justice Quarterly, 2013)
First paragraph: This article considers the issue of an oral arbitration agreement in relation to the New York Convention. As Townsend once said "[a]rbitration offers a means to an end, and the end is to the resolution of disputes." This end would be extremely difficult to achieve without the approval of national courts. Fortunately, with 146 signatory countries signed on the New York Convention on the Recognition and Enforcement of Arbitral Awards 1958 (The New York Convention), the success of this Convention has attracted businessmen into using arbitration to resolve their disputes. Nevertheless, a voluntary arbitration cannot be commenced without a valid arbitration agreement. Setting out to achieve harmonisation in the enforcement of arbitration agreements, art.II of the New York Convention provides the written requirements to be followed by all 146 signatory countries. Accordingly, written requirements for arbitration are imposed upon all signatory countries and they are obliged under the convention to recognise all arbitration agreements which are made in writing.
Keywords: Arbitration agreements; Comparative law; Convention d'arbitrage; France; New York Convention awards; New Zealand; Oral contracts; Scotland

New Frontiers on Legal Enforceability of Collective Agreements in Nigeria - Zechariah, Matthias (Current Jos Law Journal, 2013)
The objectives of this research paper are: to examine the status of collective agreements under the common law; highlight impacts of statutory intervention on common law perception of collective agreements, and discuss how the National industrial Court (NIC) and the Constitution of the Federal Republic of Nigeria 1999 (as altered) have broadened the horizon of enforceability of collective agreements in Nigeria. Reliance is placed principally on statutes, judicial decisions, textbooks written by learned authors as well as international best standard and practices championed by the International Labour Organization (ILO) and practices in some foreign jurisdictions. The ﬁndings of the research were that under the common law, collective agreements are ordinarily not binding, they are considered as a ‘gentleman's agreement‘, a product of a trade unionist's pressure, binding only in honour or on the goodwill of the parties thereto, unless and until it is incorporated expressly or impliedly into the contract of employment. However, statutory intervention has slightly altered the common law notion of collective agreements, e.g. where the Minister of Labour and Productivity is empowered to declare, by order, that part or the whole of an agreement deposited in his ofﬁce is binding on the parties. Furthermore, with the enactment of the NIC Act and the listing of the NIC in the 1999 Constitution as a superior court of record (following the alteration of the Constitution, necessitated by the N.U.E.E. V BPE case), the Court now has exclusive jurisdiction to adjudicate on a wide range of labour matters, industrial relations and application of international best practices such as the standard and principles of the International Labour Organization (ILO), and practices in foreign jurisdictions. It has been argued that the enforceability of collective agreements is in tandem with international best practices, which the NIC can readily give effect to, if it is pleaded and established/ proved as a fact. This has invariability expanded the frontiers of enforceability of such agreements. Therefore, the common law position on the status of collective agreements has been rendered otiose and obsolete, giving way to the sparkling provisions of enforceability guaranteed by the NIC Act and the Constitution respectively. Notwithstanding, it is highly recommended that parties to a collective agreement should expressly state their intention whether or not to be bound; the duration of the agreement should be stated and whether, and when, it should, be reviewed; experts and other stakeholders should be properly consulted before an agreement is entered into; an arbitration clause may be included in case a party breaches its own part of the agreement. Industrial democracy ought to be promoted in all sectors. Strikes and lock outs should be used only as a last resort for enforcing compliance with a collective agreement, because these industrial actions cause devastating effects on the economy and on the lives of the citizenry generally.
Accepted: 2017-08-16T13:03:49Z

From Port Louis to Panama and Washington DC: Two Regional Approaches to International Commercial Arbitration - Bashi Rudahindwa, Jonathan (European Journal of Law Reform, 2012)
In recent decades, regional efforts have been made to reform and harmonize the rules governing international arbitration. These efforts have resulted in the adoption of regional instruments governing commercial arbitration in specific areas. This paper analyzes the arbitration regimes created at a regional level in Africa and America, and particularly focuses on arbitral institutions that were created within the Organization for Harmonization of Business Law in Africa (OHADA) and within the Organization of American States (OAS). The objective of the paper is to identify any advantages provided by either regime, which can help improve regional and international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Political Economy of the Harmonisation of Business Law in Africa - Ntongho, Rachael (Journal of Politics and Law, 2012)
This paper examines the current dynamics of regulatory reforms in Africa and its implication on the continent. It analyses the highly political struggle for regulatory dominance of business law in Africa and how this interacts with the preferences and power of select international actors. It illustrates that the struggle between Francophone and Anglo-Saxon sections of society for OHADA to reflect their ideological stance is having a negative effect on the harmonisation process.

Regionalism : lessons the SADC may learn from OHADA - Leno, Ngaundje Doris (THRHR, 2012)
Meeste Afrikastate is klein en het nie die vermoë om effektief aan prosesse van die Wêreldhandelsorganisasie deel te neem nie. Hierdie onvermoë, saam met ander faktore, is die hoofrede vir die voortgesette marginalisering van die kontinent in die globale ekonomie en handel. Ten einde effektief aan genoemde prosesse deel te neem en in die voordele van die geglobaliseerde wêreld te deel, moet Afrikastate integreer. Regionalisme of integrasie is nie ’n doel op sigself nie maar is nodig vir die ekonomiese groei van Afrikastate. Dit skep groter markte vir handel en belegging en is ’n aansporing tot groter effektiwiteit, produktiwiteit en mededingendheid. In die lig hiervan stel die artikel drie kernargumente. Die eerste is dat regionalisme voordele bied wat Afrikastate kan ontgin ten einde marginalisering op globale vlak te oorkom. Die tweede argument is dat, terwyl die Suider-Afrikaanse Ontwikkelingsgemeenskap (SAOG) poog om besigheidsreg te harmoniseer, die Organisation for the Harmonisation of Business Law in Africa (OHADA) (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) as voorbeeld kan dien aangesien dit reeds die grondslag gelê het vir die harmonisering van besigheidsreg in Afrika. Die derde argument is dat die SAOG-tribunaal verbeter moet word ten einde ’n meer regionale regsraamwerk binne die SAOG daar te stel. In hierdie verband belig die artikel sommige voordele van regionalisme in Afrika, die lesse wat die SAOG by OHADA kan leer, die voordele van ’n geharmoniseerde besigheidsreg teen die agtergrond van die OHADA-ondervinding en die moontlike wyses waarop die SAOGtribunaal verbeter kan word.

Arbitrability in the context of Ghana's new arbitration law. - Mante, Joseph; Ndekugri, Issaka (International arbitration law review, 2012)
Examines the approach of Ghana's Alternative Dispute Resolution Act 2010 to the question of arbitrability. Reflects on the concept of arbitrability under international law, the relevant trends emerging from case law, and the approach adopted by the Ghanaian High Court in Attorney General v Balkan Energy LLC. Reviews the Act's arbitrability exemptions, their implications for international arbitration in Ghana, the potential jurisdictional challenges under the legislation and how its provisions could be amended to increase its conformity with international trends on arbitrability.
https://rgu-repository.worktribe.com/output/246672/arbitrability-in-the-context-of-ghanas-new-arbitration-law
Keywords: Arbitrability; Arbitrage; Arbitragem; Arbitration; Comparative law; Ghana; International commercial arbitration; Jurisdiction

Reflections on finality in arbitration - Roodt, Christa (De Jure, 2012)
Ondersoek na die Finaliteit van 'n Arbitrasiebevel Hierdie artikel oorweeg die Telcordia- en Lufuno-sake vanuit die oogpunt van die finaliteit van 'n arbitrasiebevel. Die vraag wat te berde kom, is wanneer 'n arbitrasiebevel finaliteit bereik waar 'n saak voor meer as een forum (arbitrasie en staatlike howe), in meer as een jurisdiksie gevoer word. Die prosedurele meganismes wat Amerikaanse en Suid-Afrikaanse howe tydens die Telcordia-dispuut toegepas het asook hul onderskeie benaderings tot res iudicata, het 'n groot mate van ooreenstemming getoon. Dit is te verstane dat die afhandeling van 'n internasionale proses vertraag kan word deur bepaalde grondwetlike regte wat die spoed van die afhandeling van 'n saak kan beïnvloed. Nietemin, indien die reg op 'n billike verhoor op enige stadium in die verrigtinge gepleit mag word, word 'n geleentheid geskep vir die dispuut om vryelik te eskaleer gedurende die verhoor. Dit kan die hofproses oopstel vir misbruik en die afhandeling van die geskil vertraag. Die minderheidsbeslissing in Lufuno skenk 'n mate van oorweging aan die potensiële negatiewe implikasies hiervan. Die finaliteit van die geskilbeslegtingsproses kan na behore bestuur word aan die hand van 'n wyer interpretasie van res iudicata in internasionale dispute en 'n meer geredelike ondersoek hierna, op die hof se inisiatief. Die moontlikheid dat die Telcordia-dispuut verder bespoedig sou kon word, word ondersoek met verwysing na die New York Konvensie op die Erkenning en Afdwing van Arbitrasiebevele van 1958, en aan die hand van aanbevelings wat deur ander gerekende internasionale liggame uitgereik is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Theory of Choice of Law and Party Autonomy - Basedow, Jürgen (SungKyunKwan Law Review, 2012)

Codification of Contract Law: Some Lessons From History - Swain, Warren (University of Queensland Law Journal, 2012)

Duty of Confidentiality: Myth or Reality? - Yu, Hong-Lin (Civil Justice Quarterly, 2012)
Explores the extent to which there is a duty of confidentiality in relation to the information used in arbitration proceedings. Considers how the duty is regulated by arbitration rules in different countries and whether there is a sufficient consensus to develop an internationally accepted principle of duty of confidentiality. Discusses which jurisdictions have an implied duty of confidentiality in the parties' arbitration agreement. Looks at how confidential information is defined in different jurisdictions, who is bound by the duty of confidentiality and the exceptions to the duty.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Confidential information; Confidentiality; Confidentialité; Information confidentielle

A Brief Analysis of the Disputes Arising from China-African Civil and Commercial Transactions - Zhu, Weidong (Journal of Cambridge Studies, 2012)
Keywords: Arbitrage; Arbitragem; Arbitration; China-African civil transactions; China-African commercial transactions; Disputes; Litigation

A Comparative Study of Contract Formation and Breach of Contract and Liability in China and OHADA Space Contract Laws - Traoré, Moussa Sékou; Xiao, Yongping (Journal of Politics and Law, 2011)
Chinese politicians and businessmen and their African counterparts are improving economic and commercial relations between them. This manifest interest of partnership needs a legal framework which guarantees equal and fair advantages to both parties. To reach this global aim, China and Africa must develop their collaboration in the domain of law. In the 80s China has adopted laws to reflect the country's economic and social demands such as Economic Contract Law (1981), Foreign Economic Contract Law (1985), General Principles of Civil Law (1987). Now, to better facilitate economic growth the National People's Congress (NPC) has unified China's various national specialized contract laws to obtain the “Uniform” Contract Law 1999. OHADA is a system that aims the harmonization of business law in Africa. This study aims to compare the two systems contract formation, breach of contract and liability for breach in order to have a legal frame more appropriate for business between China and this part of African Continent.

Effectiveness and Remedies of the Arbitral Awards in OHADA’s System and in People’s Republic of China. - Samassekou, Mamoudou; Lianbin, Song (Journal of Politics and Law, 2011)
Today the arbitral justice has experienced an exceptional development. It is a universal phenomenon which requires the involvement of all economic and legal players of developed and developing countries.OHADA is a common business law and wish to secure legal security for regional and foreign economic agents by offering a vast economic space. The People’s Republic of China (PRC) is an emerging country which increases its economic outlets in a context of globalization. This natural interdependence will increase the scope of economic exchanges, which may generate some disputes in businesses. This article aims to compare two legal systems in the international commercial arbitration field: the legal system of OHADA and the PRC’s legal system; especially in the effectiveness and the remedies of the arbitrators’ decisions.
Number: 1

A Taxonomy of International Rule of Law Institutions - Romano, Cesare P.R. (Journal of International Dispute Settlement, 2011)
This article revises and updates a seminal article written by the author in 1998, which was the first attempt to tally how many and what kind of international courts and tribunals existed at that point in time. It contained a chart that placed international courts and tribunals in a larger context, listing them alongside quasi-judicial bodies, implementation-control and other dispute settlement bodies. The present article has three aims. The first is to provide an update, since several new bodies have been created or have become active in the last decade. The second aim is a bit more ambitious. It is time to revise some of the categories and criteria of classification used back in 1998. More than a decade of scholarship in the field by legal scholars and political scientists has made it possible to gain a better understanding of the phenomenon. The abundance of data over a sufficiently long time-span is making it possible to start moving away from a mere ‘folk taxonomy’ towards a more rigorous scientific classification. The hallmark of truly scientific classifications is that classifying is only the final step of a process, and a classification only the means to communicate the end results. Besides making it possible to discover and describe, scientific classifications crucially enable prediction of new entities and categories. Thus, the third aim of this article is to attempt to discern some trends and make some predictions about future developments in this increasingly relevant field of international law and relations.

Dispute Resolution in International Electricity Trade - Han, Baoqing (Energy Procedia, 2011)
International electricity trade disputes can arise at three key levels: state to state; investor to state; private party to private party. Parties may be more open to submission of their disputes to international arbitration. However, they should make proper arbitration options according to the types of disputes. At the same time, considering the risks facing dispute resolution, it is imperative to specifically design effective tools to mitigate these risks.
Keywords: Dispute resolution; Disputes; International Arbitration; International electricity trade; Risk mitigation

Comparative regionalism: a new research agenda - Börzel, Tanja A. (KFG The Transformative Power of Europe, 2011)
After the end of the Cold War, students of International Relations observed an expansion of inter-state activities at the regional level. Regional and sub-regional groupings appeared to gain momentum as the way in which countries cooperate and should cooperate to pursue peace, stability, wealth and social justice. The surge and resurgence of regionalism has triggered the proliferation of concepts and approaches. The focus of this paper will be on processes and structures of state-led regionalism driven by the delegation of policies and political authority to regional institutions. Based on this understanding of regionalism, the existing literature will be reviewed with regard to three general questions. These questions do not only require research across regions but also allow developing a common research agenda to accumulate knowledge generated about specific regions. First, what are the outcomes of regionalism? How can we describe and compare the results of the delegation of policies and political authority? Second, what are the drivers of regionalism? Why do some governments choose to delegate policies and political authority while others do not? Finally, what are the internal effects of regionalism? How does the delegation of policies and political authority impact back on the domestic structures of the states involved?
Accepted: 2018-06-08T07:36:10Z

Exploring the limits of Western Corporate Social Responsibility Theories in Africa - Dartey-Baah, Kwasi; Amponsah-Tawiah, Kwesi (International Journal of Business and Social Science, 2011)
Corporate Social Responsibility (CSR) is about the relationship of organisations with society as a whole, and the need for organisations to align their values with societal expectations. Generally, CSR practice in Africa is thought to be adopted from Western business theories although there is evidence to suggest that Western CSR theories are not totally applicable in Africa. This is due to differences in drivers or causes of CSR in the West and in Africa, as well as cultural and managerial traits in Africa. This paper explores the limits of Western CSR Theories in Africa and argues that improved ethical responsibilities, incorporating good governance should be assigned the highest CSR priority in developing countries. It further adds that increased legislation, change in CSR priorities and the application of indigenous CSR theories such as Ubuntu, African Renaissance and Omuluwabi are means of countering the limits of Western CSR theories in Africa. Keywords: CSR, Western CSR Theory, Africa, Ubuntu, African Renaissance, Omuluwabi
Keywords: Africa; CSR; RSE; Renaissance; Ubuntu; Western CSR Theory

OHADA's Proposed Uniform Act on Contract Law: Formal Law for the Informal Sector - Dickerson, Claire Moore (European Journal of Law Reform, 2011)
The draft uniform act on contracts proposed for adoption by the Organization for the Harmonization of Business Laws in Africa ("OHADA") is a combination of continental and common-law concepts. To be effective in parts of the world where the informal sector is particularly important, for example in the 16 West and Central African states where OHADA currently operates, contract law must be particularly attentive to avoiding traps for the unwary. For this reason, enforcing gratuitous contracts may well be defensible, but requiring registration of commercial actors is not. The complexity of two OHADA laws applicable to contracts, however, increases the risk that law and norms will not overlap, creating just such a trap.
Keywords: Comparative law; contracts; norms

Arbitration: One Size Does Not Fit All: Necessity of Developing Institutional Arbitration in Developing Countries - Namrata Shah, Niyati Gandhi (Journal of International Commercial Law and Technology, 2011)
Litigation in developing countries has many defects which has prompted a need for the development of alternative dispute resolution mechanisms. Arbitration, being one such substitutive mechanism as a type of private litigation is the most suitable for the same. This paper deals with the need to develop institutional arbitration to co-exist with ad hoc arbitration and scale it down to be available for dispute resolution in developing countries using an illustration of India. Certain recommendations to make institutional arbitration, which is considered to be appropriate for International commercial dispute resolution, suitable for domestic disputes in developing countries have been highlighted.
https://www.neliti.com/publications/28786/
Keywords: Arbitrage; Arbitragem; Arbitration; Developing countries; Institutional arbitration

Intellectual Property Law and Competition Law - Patel, Atul; Panda, Auro Aurobinda; Deo, Akshay; Khettry, Siddhartha; Mathew, Sujith Philip (Journal of International Commercial Law and Technology, 2011)
Competition law and intellectual property rights (IPRs) have evolved historically as two separate systems of law. There is a considerable overlap in the goals of the two systems of law because both are aimed at promoting innovation and economic growth. Yet there are also potential conflicts owing to the means used by each system to promote those goals. IP laws generally offer a right of exclusive use and exploitation to provide a reward to the innovator, to provide an incentive to other innovators and to bring into the public domain innovative information that might otherwise remain trade secrets. Competition authorities regulate near monopolies, mergers and commercial agreements with the aim of maintaining effective competition in markets. This article introduces the concept of IPRs and Competition law. It highlights important areas of conflict between the two laws and also deals with the Indian antitrust law. It concludes by trying to harmonize the conflicts.
Keywords: Competencia; Competition law; Intellectual property

A comparative study: Arbitration agreement in OHADA and People's Republic of China arbitration laws - Samassekou, Mamoudou; Song, Lianbin (Journal of Politics and Law, 2011)
This article aims to compare the arbitration agreement of the OHADA legal system to that of the People's Republic of China. In the Chinese legal system the parties to a contract are required to have an arbitration agreement written before the occurrence of any incident in the execution of their contract. The parties must specify in advance, in the said agreement, the chosen arbitration institution for potential disputes. In the OHADA legal system, the parties are free to decide before or during execution of the contract of an arbitration agreement. They may also decide whether in case of a dispute, they would want to refer to an institutional arbitration or an ad hoc arbitration. According to the chosen legal system the consequences are different.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; China-OHADA

Revisiting the Depoliticization of Investment Disputes - Schneiderman, David (Yearbook on International Investment Law and Policy, 2011)
The chapter challenges claims about depoliticization in two different aspects. The first examined claim is that home states are disenfranchised from pursuing investment claims once they are lodged with ICSID. Is it the case that home states simply stay home? This chapter examines instances where home states may have played a role in investment disputes between contracting states. What the record generally reveals, however, is that home states involve themselves in disputes where ICSID hearings are imminent but not yet in play. The second, broader, reading of depoliticization maintains that disputes now are resolved without recourse to lowly politics but to ‘higher’ law. This more extravagant claim is vulnerable to the critique that investor-state dispute resolution is not emptied of political content but, instead, spills over with politics. As the regime implicates the capacity of public authority to act in a wide variety of regulatory contexts, the separation of law from politics is hard to credibly maintain. Not only are investor-state disputes embedded within regimes of political discourse and political power, the ambit of investment arbitrator discretion is so capacious that it can be said of arbitrators, as it has been said of the U.S. Supreme Court, that they can sensibly be regarded as political actors.
Accepted: 2024-06-14T19:55:42Z

National legislative systems and foreign standards and regulations: The case of International Financial Reporting Standards adoption - Dima, Bogdan; Dima (Cristea), Stefana Maria; Moldovan, Nicoleta; Pirtea, Marilen Gabriel (MPRA Paper, 2010)
This study is focused on the linkages between the legislative families as descriptors of national legislative systems and International Financial Reporting Standards (IFRSs) issued by the International Accounting Standards Board (IASB). We consider such analysis as a case study for the more general issue of explaining the preferences of national regulators in the adoption of foreign norms, rules, standards and practices. By using a dataset of 162 jurisdictions and dummy variables designed to capture the current stage of IFRSs adoption and, respectively, the taxonomy of their legislative systems, we find that a full IFRSs adoption is more likely to occur in countries which have principles-based on legislative mono-systems. In addition, we observe that a strong rule of law, with an effective mechanism of property rights reinforcement, as well as the pre-adoption existence of a pro-growth set of public policies can contribute to the encouragement of IFRSs adoption.
Keywords: IFRSs adoption; Legislative families

The New African Law: Beyond the Difference Between Common Law and Civil Law - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Trends on the Harmonization of Contract Law in Africa - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Legal Challenges and Strategies for Comparison Shopping and Data Reuse - Zhu, Hongwei; Madnick, Stuart E. (Journal of Electronic Commerce Research, 2010)
New technologies have been continuously emerging to enable effective reuse of an ever-growing amount of data on the Web. Innovative firms can leverage the available technologies and data to provide useful services. Comparison-shopping services are an example of reusing existing data to make bargain-finding easier. Certain reuses have caused conflicts with the firms whose data has been reused. Countries in the European Union have implemented the Database Directive to provide legal protection for database creators, but the impact and the interpretation of the new law are unclear and still evolving. Lawmakers in the U.S. have not decided on a policy concerning database protection and data reuse. Both data creating and data reusing firms need to develop strategies to operate effectively in this uncertain environment. Comparison-shopping and other data reuse services face similar legal and strategic challenges. Thus we address these challenges in the broader data reuse context. We use economic reasoning to formulate strategies in anticipation of the likely policy choices and interpretations of existing legislation. Both data creating firms and data reusing firms should focus on innovative ways of using or reusing data to create differentiated products and services. For firms that gather data from multiple sources, they can also use the insights gained from integrated data to provide other value-added services.

On the Development of West African Accounting System - Moussa, Boka (International Journal of Business and Management, 2010)
The authorities of the West African Economic and Monetary Union UEMOA fully understand that accounting plays the significant role in the process of economic development and regional integration in the member states. They decided to establish a common new accounting system, called West African Accounting System (SYSCOA). The accounting system has been developed on the initiative of the Central Bank of West African States
Number: 5

International Investment Law and Media Disputes: A Complement to WTO Law - Peterson, Luke Eric (Transnational Corporations Review, 2010)
The recent high-stakes dispute between Google and China over censorship and cyber-security has spawned renewed discussion of the international trade law protections that internet and media companies may enjoy. Less recognized, however, is a perhaps more powerful legal tool in the arsenal of internet and media companies engaging in cross-border investments, namely international investment law.
Keywords: China; international investment; law; media

The Role of South Africa in SADC Regional Integration: the Making or Braking of the Organization - Amos, Saurombe (Journal of International Commercial Law and Technology, 2010)
Read on Neliti

Enforcement of Arbitral Awards in Sub-Sahara Africa - Onyema, Emilia (Arbitration International, 2010)
As the world celebrated the fiftieth anniversary of the New York Convention in 2008 it became necessary to examine the enforcement regimes for arbitration awards in Sub-Sahara Africa. This article examines the provisions for the recognition and enforcement, and requirements for the setting aside of both domestic and international arbitral awards under the arbitration laws of OHADA member states, Nigeria and Sudan, as representative of the legal regimes in Sub-Sahara African countries. The New York Convention applies to Convention awards in half of the countries of Sub-Sahara Africa. It is therefore relevant to examine the requirements for the enforcement of non-Convention awards in those states that are members of the New York Convention, and also in those states that are not members of the New York Convention. Different arbitration laws and regimes apply in the three representative jurisdictions chosen for this comparative analysis and these are also representative of the legal regimes in those countries with arbitration laws in the region. Though a generally supportive tendency towards the enforcement of arbitral awards can be gleaned from the examination of some arbitration-related judgments, this article again highlights the importance for the remaining countries in the region yet to sign up to and implement the New York Convention to consider adopting it, and for more arbitration hearings to be held within the region.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Enforcement of Arbitral Awards; Sub-Sahara

Future Directions of Legal Harmonisation and Law Reform : Stormy Seas or Prosperous Voyage ? - Faria, José Angelo Estrella (Uniform Law Review, 2009)

The need to harmonise trade-related laws within countries of the African Union: an introduction to the problems posed by legal divergence - Dlagnekova, Polina (Fundamina : A Journal of Legal History, 2009)
It is widely accepted that inter-state relationships have entered an era of globalisation. The economic theory of convergence explains that it is this phenomenon which has spearheaded, amongst others, the development of international rules in the field of trade, finance and taxation.

E-Commerce and Mobile Commerce in South Africa: Regulatory Challenges - Jobodwana, Z. Ntozintle (Journal of International Commercial Law and Technology, 2009)
E-commerce refers to all forms of commercial transactions that involve individuals and organizations based on the electronic processing of data. Mobile commerce (M-commerce) is the buying and selling of goods and services using mobile telephones or personal digital assistants (PDA). M-commerce is emerging in Africa and South Africa especially as either a complement or an alternative to e-commerce as originally conceived, though there are arguments that mobile telephone technology â€œm-commerceâ€ will surpass â€œe-commerceâ€ as the method of choice for digital commerce transactions. This paper identifies the challenges in adopting e-commerce/m-commerce practices for economic development and competition in International trade. The liberalisation of the telecommunications sector on which e-commerce and m-commerce practices depend is being given priority by the majority of African governments. Despite advances in e-commerce and m-commerce practices in Africa, the growth of e-commerce and m-commerce has been slow. Impediments include low levels of internet penetration and limited communication infrastructure. To meet this problem, the UN adopted through the UN Commission on International Trade (UNCITRAL), Model Law on E-Commerce to help in the harmonisation of e-commerce/m-commerce related laws. Challenges are identified and recommendation made on how to improve the regulatory framework and create an environment conducive to investment and economic development.
https://www.neliti.com/publications/28783/

Executive Remuneration as an Aspect of Corporate Governance under OHADA's Corporate System - Kelong, Richard William Ngwa (MPRA Paper, 2009)
With growing importance attached to the notion of executive remuneration, OHADA’s policy makers have also considered the concept as a fundamental element in any corporate governance system. In this regard, they have put in place a policy framework that regulates executive remuneration within OHADA’s corporate system to ensure that executive benefits are appropriate and lawful to enable directors remain objective in respect of their fiduciary duties towards the company. This paper discusses executive remuneration as an aspect of corporate governance under OHADA's corporate system. In doing so, the paper describes the executive remuneration policy under OHADA's corporate system and makes an appraisal of the abovementioned policy with the goal of stating its potential and limitation as well as proposing a reform that will guarantee its effectiveness as a mechanism in ensuring good corporate governance.

On formation of a share company in Ethiopia - Tesfay, Seyoum Yohannes (Journal of Ethiopian Law, 2008)
Keywords: Attributes; Ethiopian law; Formation; Share company

Reforming Legal Reform in Francophone Africa: World Bank' Project Experience - Wabnitz, Hans-Werner (Islamic Law and Law of the Muslim World Paper, 2008)
You don't plant water lilies in the desert - The keystone of civilized society is justice. Without justice, neither peace nor development. A prerequisite is the populations' trust in legal institutions: the law and the courts. The alienation of the people with imposed legal institutions is the reason for Francophone Africa's lack of justice. To remedy the situation, this paper proposes to reconnect the people with the law through: (1) respecting local values in Village tribunals; (2) reforming lawmaking to comply with custom, accessible (also) in vernacular languages; (3) accessibility of law through the Internet. It is argued that the people, as client of justice, need to regain control over their law in order to respect it. Only then the necessary change of traditions and values is feasible. Women lawyer associations are identified as agents for such change. To redress modern courts, the paper suggests a concentration of tribunals, a tightening of procedure and rigorous control, in order to foster peer pressure for professionalism. The constitutional values are to serve as common bond.
Keywords: ACCESS TO JUSTICE; Africa; Colonial law; Corruption; Court administration; Culture; Customary law; Drafting; Equality; Fatwa; Gender; Honor; Human rights; Institutions; Justice; Law; Legal reform; OHADA; Paralegals; Participation; Reform; Tradition; Uniform Act; Village courts; Worldbank

Some preliminary thoughts on a comparative law model for harmonisation of laws in Africa - Nicholson, Caroline (Fundamina : A Journal of Legal History, 2008)
This paper is premised upon acceptance of the view that some form of harmonisation of laws in Africa is a desirable objective and that comparative legal research is a tool that might effectively be applied in order to further the objective of harmonisation. That said, the time has come for comparatists in Africa to think afresh on the issues of globalisation and the need for harmonisation of laws in Africa, with a view to promoting peace, stability and scope for increased development in the region through greater regional economic co-operation.

NEPAD and African Development: Towards a New Partnership between Development Actors in Africa - Tawfik, Rawia M. (African Journal of International Affairs, 2008)
The model required to drive socio-economic development in Africa, and the relationship between the state and the private sector based on that model, have sparked much controversy among African analysts. Some question the relevance of other successful models of development, such as in the liberal West or in East-Asia, to the African context. Others criticise all models of development that are “alien” to African cultures and conditions hence rejecting the NEPAD model on this basis. This paper argues that although NEPAD does not present a detailed model of the relationship between the state, the private sector and civil society in Africa, some of its theoretical underpinnings suggest a balanced framework that should prompt African scholars to search for new models that do not necessarily imitate already successful ones but respect the particularities of each African state

The Harmonization of Business Law in Africa: Is Article 42 of the OHADA Treaty a Problem? - Enonchong, Nelson (Journal of African Law, 2007)
OpenAlex: https://openalex.org/W2023472476
Keywords: Harmonization; Investment; Member state

Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.
https://www.neliti.com/publications/28634/

Accounting for financial instruments: An analysis of the determinants of disclosure in the Portuguese stock exchange - Lopes, Patrícia Teixeira; Rodrigues, Lúcia Lima (The International Journal of Accounting, 2007)
In this paper we analyse the determinants of disclosure level in the accounting for financial instruments of Portuguese listed companies. Considering the mandatory adoption of International Accounting Standards after 2005, our ultimate objective is to analyse the characteristics of companies that are closest to the disclosure requirements of IAS 32 and IAS 39. We have constructed an index of disclosure comprising 54 items based on IAS 32 and 39 disclosure requirements and computed the index score for each Portuguese listed company based on the analysis of the companies’ annual reports. We tested the relation between the index score and several firm-specific characteristics: size, industry, auditor type, listing status, multinationality degree, relationship shareholders/creditors and importance of shareholders. We conclude that larger companies and companies listed in more than one exchange market show higher levels of disclosure, meaning that they are closer to IAS 32 and 39 requirements. We argue that the agency theory, the signalling theory and the political costs theory do not fully explain Portuguese reality, where there is a large degree of family ownership and bank-oriented financing policies. We therefore advocate that the introducing variables related to specific characteristics of Portuguese companies and managers, in the context of other theoretical frameworks, notably the contingency theory, brings important insights to this type of analysis.

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.
Télécharger l'article: https://www.austlii.edu.au/au/journals/UNSWLRS/2007/29.rtf

Re-Imagining International Law: An Examination of Recent Trends in the Reception of International Law Into National Legal Systems in Africa - Oppong, Richard (Fordham International Law Journal, 2006)
This article suggests that the trend of accepting the supremacy and direct application of international law represents a rethinking of the relationship between international and national law, and that its full implications are yet to be explored. The Article seeks to build on current writings on the subject by analyzing certain regional arrangements and judicial approaches relevant to, but often ignored in the discussion. It attempts not to situate these arrangements or approaches within or outside of the monist/dualist paradigm, but to assess the practical significance of these arrangements for international law, national law, and their respective subjects.

The Role of International Arbitrators - Franck, Susan D. (ILSA Journal of International & Comparative Law, 2006)

The Contractarian Model of Arbitration and Its Implications for Judicial Review of Arbitral Awards - Kirgis, Paul F. (Oregon Law Review, 2006)

Harmonizing Business Laws in Africa: Ohada Calls the Tune - Dickerson, Claire Moore (Columbia Journal of Transnational Law, 2005)
OHADA (in English, Organization for Harmonization in Africa of Business Laws) is a system of business laws and implementing institutions. Sixteen West African nations adopted this regime in order to increase their attractiveness to foreign investment. Because most of the member states are former French colonies, the OHADA laws are based on the French legal system. Despite certain economists’ recent, well-publicized assertions that any French-based legal system is incompatible with development, other studies challenge those claims and in doing so outline characteristics that a pro-development system of business laws should possess. This Article reviews selected provisions from OHADA’s corporate law and of OHADA’s institutions, revealing that they correspond to those pro-development characteristics. Interviews conducted with legal professionals in Senegal, Côte d’Ivoire, and Cameroon highlight the local perception that the OHADA regime, while still
Keywords: Africa; Claire Moore Dickerson; Harmonizing Business Laws; OHADA; SSRN

Worldwide Harmonisation of Private Law and Regional Economic Integration - General Report - Basedow, Jürgen (Uniform Law Review, 2003)

Trade Liberalization and Regulatory Diversity - Trebilcock, Michael (Third EnviReform Conference, 2002)
This is the version of record of a paper presented at the Third EnviReform Conference, authored by Michael Trebilcock.
Accepted: 2023-08-02T20:29:27Z
Keywords: Domestic Policy; GATT; NGOs; Non-tariff barriers; Trade Policy; WTO

The Commercial Lease: Property or Contract - Brock, Jason; Phillips, Jim (Alberta Law Review, 2001)
The commercial lease has historically been treated as a conveyance of an interest in land which creates a property-based relationship between the lessor and lessee, despite the fact that the relationship is created by contract and could be seen as a contract for the ongoing use of the land. Some Canadian cases, however, have applied "partial contractualization " — using both property and contract rules and concepts to interpret leases. The article examines the historical development of the lease and its treatment in Canadian courts, as well as in other common law courts. The authors argue that the property/contract hybrid should be eliminated in favour of "complete contractualization " — using pure contract principles to interpret the commercial lease. The article points out how contract principles would serve the parties to the lease just as well, or better, than property principles and offers solutions for the anticipated problem area of security of tenure for the tenant.

African Legal Developments in the United States and Sub-Saharan Africa - Eisenfeld, Jamie; Serres, Francois (The International Lawyer, 2001)
https://scholar.smu.edu/til/vol35/iss3/3

Cross-Border Insolvency and Structural Reform in a Global Economy - Garzon, Paula; Vassallo, Anthony; Carruth, Jeff (The International Lawyer, 2000)